3D printing for sizing left atrial appendage closure device: head-to-head comparison with computed tomography and transoesophageal echocardiography. - Hell, Michaela M.; Yoo, In Seong; Achenbach, Stephan; Franke, Jörg; Blachutzik, Florian; Röther, Jens; Graf, Verena; Raaz-Schrauder, Dorette; Marwan, Mohamed; Schlundt, Christian (EuroIntervention, 2017)
AIMS Device sizing for LAA closure using transoesophageal echocardiography (TEE) can be challenging due to complex LAA anatomy. We investigated whether the use of 3D-printed left atrial appendage (LAA) models based on preprocedural computed tomography (CT) permits accurate device sizing. METHODS AND RESULTS Twenty-two (22) patients (73±8 years, 55% male) with atrial fibrillation requiring anticoagulation at high bleeding risk underwent LAA closure (WATCHMAN device). Preprocedurally, LAA was sized by TEE and third-generation dual-source CT. Based on CT, 3D printing models of LAA anatomy were created for simulation of device implantation. Device compression was assessed in a CT scan of the 3D model with the implanted device. Implantation was successful in all patients. Mean LAA ostium diameter based on TEE was 22±4 mm and based on CT 25±3 mm (p=0.014). Predicted device size based on simulated implantation in the 3D model was equal to the device finally implanted in 21/22 patients (95%). TEE would have undersized the device in 10/22 patients (45%). Device compression determined in the 3D-CT model corresponded closely with compression upon implantation (16±3% vs. 18±5%, r=0.622, p=0.003). CONCLUSIONS Patient-specific CT-based 3D printing models may assist device selection and prediction of device compression in the context of interventional LAA closur

Accuracy of dual-source CT to identify significant coronary artery disease in patients with uncontrolled hypertension presenting with chest pain: Comparison with coronary angiography - Marwan, Mohamed; Pflederer, Tobias; Schepis, Tiziano; Seltmann, Martin; Klinghammer, Lutz; Muschiol, Gerd; Ropers, Dieter; Daniel, Werner; Achenbach, Stephan (International Journal of Cardiovascular Imaging, 2012)
It has been previously reported that the sensitivity and specificity of multislice CT for detecting significant CAD (coronary artery disease) is high. Chest pain is a common presentation in patients with uncontrolled hypertension. We investigated the sensitivity and specificity of Dual-Source CT to detect and rule out significant CAD in patients presenting with uncontrolled hypertension accompanied by chest pain. 260 consecutive patients presenting with acute chest pain in the context of stage 2 hypertension (systolic pressure ≥160 and/or diastolic pressure ≥100) were enrolled in the study. After admission, control of blood pressure and risk stratification, 82 patients were excluded due to renal insufficiency, prior coronary revascularisation or refused participation in the study. 90 further patients with low pre-test probability of CAD were also excluded. 88 remaining patients were subjected to CT coronary angiography using Dual-Source CT (Definition, Siemens Medical Solutions, Forchheim, Germany) within 24 h before invasive coronary angiography. A contrast-enhanced volume dataset was acquired (120 kV, 400 mAs/rot, collimation 2 × 64 × 0.6 mm, retrospective ECG gating). Data sets were evaluated concerning the presence or absence of significant coronary stenoses and validated against invasive coronary angiography. A significant stenosis was assumed if the diameter reduction was ≥50%. 88 patients (mean age 66 ± 11 years, mean heart rate 61 ± 9 bpm) were evaluated regarding the presence or absence of significant CAD (at least one stenosis ≥50% diameter reduction). Mean systolic blood pressure on presentation was 203 ± 20 mmHg and mean diastolic blood pressure was 103 ± 13 mmHg. On a per patient basis, the sensitivity and specificity for Dual-Source CT to detect significant CAD in vessels > 1.5 mm diameter was 100% (36/36, 95% CI 90-100) and 90% (47/52, 95% CI 79-97), respectively with a negative predictive value (NPV) of 100% (47/47, 95% CI 92-100) and a positive predictive value (PPV) of 88% (36/41, 95% CI 74-96). On a per artery basis, 352 vessels were evaluated (left main, left anterior descending, left circumflex and right coronary artery in 88 patients, 12 vessels could not be assessed due to either motion artefacts or heavy calcification and were considered positive for stenoses) with a sensitivity of 84% (54/64, 95% CI 72-95) and specificity of 94% (272/288, 95% CI 88-100); NPV was 96% (272/282, 95% CI 90-100) and PPV was 77% (54/70, 95% CI 62-91). Our study demonstrates high sensitivity, specificity and negative predictive value of Dual- Source CT to detect significant CAD in patients presenting with uncontrolled hypertension accompanied by chest pain. Dual-Source CT angiography may be useful to safely rule out coronary artery stenoses and avoid invasive angiograms in these patients. © Springer Science+Business Media, B.V. 2011.
CRIS-Team Scopus Importer:2023-07-10
Keywords: CT; Stenosis; Uncontrolled hypertension

Analysis of left ventricular function, left ventricular outflow tract and aortic valve area using computed tomography: Influence of reconstruction parameters on measurement accuracy - Hell, Michaela; Steinmann, Bettine; Scherkamp, Tassilo; Arnold, Martin; Achenbach, Stephan; Marwan, Mohamed (British Journal of Radiology, 2021)
Objectives: Computed tomography (CT) allows reproducible assessment of left ventricular (LV) function, left ventricular outflow tract area (LVOTarea) and aortic valve area (AVA). We evaluated the influence of image reconstruction parameters on these measurements.
CRIS-Team WoS Importer:2021-08-06

A novel machine learning-derived radiotranscriptomic signature of perivascular fat improves cardiac risk prediction using coronary CT angiography - Oikonomou, Evangelos K.; Williams, Michelle C.; Kotanidis, Christos P.; Desai, Milind Y.; Antonopoulos, Alexios S.; Thomas, Katharine E.; Thomas, Sheena; Akoumianakis, Ioannis; Fan, Lampson M.; Kesavan, Sujatha; Herdman, Laura; Alashi, Alaa; et al. (European Heart Journal, 2019)
BACKGROUND: Coronary inflammation induces dynamic changes in the balance between water and lipid content in perivascular adipose tissue (PVAT), as captured by perivascular Fat Attenuation Index (FAI) in standard coronary CT angiography (CCTA). However, inflammation is not the only process involved in atherogenesis and we hypothesized that additional radiomic signatures of adverse fibrotic and microvascular PVAT remodelling, may further improve cardiac risk prediction. METHODS AND RESULTS: We present a new artificial intelligence-powered method to predict cardiac risk by analysing the radiomic profile of coronary PVAT, developed and validated in patient cohorts acquired in three different studies. In Study 1, adipose tissue biopsies were obtained from 167 patients undergoing cardiac surgery, and the expression of genes representing inflammation, fibrosis and vascularity was linked with the radiomic features extracted from tissue CT images. Adipose tissue wavelet-transformed mean attenuation (captured by FAI) was the most sensitive radiomic feature in describing tissue inflammation (TNFA expression), while features of radiomic texture were related to adipose tissue fibrosis (COL1A1 expression) and vascularity (CD31 expression). In Study 2, we analysed 1391 coronary PVAT radiomic features in 101 patients who experienced major adverse cardiac events (MACE) within 5 years of having a CCTA and 101 matched controls, training and validating a machine learning (random forest) algorithm (fat radiomic profile, FRP) to discriminate cases from controls (C-statistic 0.77 [95%CI: 0.62-0.93] in the external validation set). The coronary FRP signature was then tested in 1575 consecutive eligible participants in the SCOT-HEART trial, where it significantly improved MACE prediction beyond traditional risk stratification that included risk factors, coronary calcium score, coronary stenosis, and high-risk plaque features on CCTA (Δ[C-statistic] = 0.126, P < 0.001). In Study 3, FRP was significantly higher in 44 patients presenting with acute myocardial infarction compared with 44 matched controls, but unlike FAI, remained unchanged 6 months after the index event, confirming that FRP detects persistent PVAT changes not captured by FAI. CONCLUSION: The CCTA-based radiomic profiling of coronary artery PVAT detects perivascular structural remodelling associated with coronary artery disease, beyond inflammation. A new artificial intelligence (AI)-powered imaging biomarker (FRP) leads to a striking improvement of cardiac risk prediction over and above the current state-of-the-art.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Adipose tissue; Computed tomography; Coronary artery disease; Machine learning; Radiomics; Risk stratification

Aortic annulus eccentricity before and after transcatheter aortic valve implantation: Comparison of balloon-expandable and self-expanding prostheses - Schuhbaeck, Annika; Weingartner, Christina; Schmid, Jasmin; Pflederer, Tobias; Rixe, Johannes; Nef, Holger; Schneider, Christian; Lell, Michael; Uder, Michael; Ensminger, Stephan; Feyrer, Richard; Weyand, Michael; et al. (European Journal of Radiology, 2015)
The geometry of the aortic annulus and implanted transcatheter aortic valve prosthesis might influence valve function. We investigated the influence of valve type and aortic valve calcification on post-implant geometry of catheter-based aortic valve prostheses.Eighty consecutive patients with severe aortic valve stenosis (mean age 82 ± 6 years) underwent computed tomography before and after TAVI. Aortic annulus diameters were determined. Influence of prosthesis type and degree of aortic valve calcification on post-implant eccentricity were analysed.Aortic annulus eccentricity was reduced in patients after TAVI (0.21 ± 0.06 vs. 0.08 ± 0.06, p<0.0001). Post-TAVI eccentricity was significantly lower in 65 patients following implantation of a balloon-expandable prosthesis as compared to 15 patients who received a self-expanding prosthesis (0.06 ± 0.05 vs. 0.15 ± 0.07, p<0.0001), even though the extent of aortic valve calcification was not different. After TAVI, patients with a higher calcium amount retained a significantly higher eccentricity compared to patients with lower amounts of calcium.Patients undergoing TAVI with a balloon-expandable prosthesis show a more circular shape of the implanted prosthesis as compared to patients with a self-expanding prosthesis. Eccentricity of the deployed prosthesis is affected by the extent of aortic valve calcification.
EVALuna2:12030

Applicability and procedural success rate of bioresorbable-vascular scaffolds for percutaneous coronary intervention in an all-comer cohort of 383 consecutive patients - Schlundt, Christian; Achenbach, Stephan; Felten, Fabiola; Röther, Jens; Nef, Holger; Ludwig, Josef; Tröbs, Monique; Marwan, Mohamed (Acta Cardiologica, 2017)
Objectives The purpose of this study was to determine applicability and procedural success of bioresorbable vascular scaffolds (BVS) for percutaneous coronary intervention (PCI) in an all-comer cohort. Background BVS use in bifurcations and severely calcified lesions is not recommended, and a relatively large crossing profile may cause limitations. It is has never been studied how widely BVS can be applied in all-comer cohorts. Methods In 383 consecutive patients (acute coronary syndrome: 124, stable coronary disease 259), a BVS (Absorb) was used as first-line device unless any of the following contraindications were present: bifurcation with side branch >2.0 mm, reference diameter <2.5 mm or >4.0 mm, required device length <12 mm, in-stent stenosis, or contraindications to 6 months of DAPT. Patients and lesions were evaluated regarding suitability for BVS treatment, procedural success (successful BVS placement and residual stenosis <30%), and outcome. Results Of 588 lesions, 303 (52%) were unsuitable for BVS placement due to presence of a bifurcation (30% of unsuitable lesions), reference -diameter >4.0 mm (13%) or <2.5 mm (12%), contraindication to 6 months DAPT (13%), in-stent stenosis (14%), and desired device length <12 mm (4%). If BVS use was attempted, procedural success with a scaffold was 95% (271/285). Crossing failure occurred in 14 cases (5%), affected lesions were significantly more calcified. After a mean follow-up period of 259 days, definite/probable scaffold thrombosis occurred in 1.1% of patients. Conclusions Approximately one-half of lesions in an all-comer population can successfully be treated with BVS. Crossing failure is rare.
EVALuna2:33655

A randomized controlled trial of the effect of spironolactone on left ventricular mass in hemodialysis patients - Hammer, Fabian; Malzahn, Uwe; Donhauser, Julian; Betz, Christoph; Schneider, Markus; Grupp, Clemens; Pollak, Nils; Störk, Stefan; Wanner, Christoph; Krane, Vera; Berweck, Susanne; Biggar, Patrick; et al. (Kidney International, 2019)
Mineralocorticoid receptor antagonists have beneficial effects on left ventricular remodeling, cardiac fibrosis, and arrhythmia in heart failure, but efficacy and safety in dialysis patients is less clear. We evaluated the effect of spironolactone on left ventricular mass (LVM), an independent predictor of all-cause and cardiovascular mortality, in hemodialysis patients. In this placebo-controlled, parallel-group trial, 97 hemodialysis patients (23% female; mean age 60.3 years) were randomized to spironolactone 50 mg once daily (n=50) or placebo (n=47). The primary efficacy endpoint was change in LVM index (LVMi) from baseline to 40 weeks as determined by cardiac magnetic resonance imaging. Safety endpoints were development of hyperkalemia and change in residual renal function. There was no significant change in LVMi in participants randomized to spironolactone compared to placebo (-2.86±11.87 vs. 0.41±10.84 g/m2). There was also no difference in the secondary outcomes of mean 24-hour systolic or diastolic ambulatory blood pressure, left ventricular ejection fraction, 6-minute walk test distance, or New York Heart Association functional class. Moderate hyperkalemia (pre-dialysis potassium levels of 6.0-6.5 mmol/L) was more frequent with spironolactone treatment (155 vs. 80 events), but severe hyperkalemia (≥6.5 mmol/L) was not (14 vs. 24 events). Changes in residual urine volume and measured glomerular filtration rate did not differ between groups. There were no deaths in the spironolactone group and 4 deaths in the placebo group. Thus, treatment with 50 mg spironolactone did not change left ventricular mass index, cardiac function, or blood pressure in hemodialysis patients. Spironolactone increased the frequency of moderate hyperkalemia, but did not increase severe hyperkalemia.
EVALuna2:36276

Artificial Intelligence-based quantification of atherosclerotic plaque and stenosis from coronary computed tomography angiography using a novel method - Lin, Andrew; Manral, Nipun; McElhinney, Priscilla; Killekar, Aditya; Matsumoto, Hidenari; Kwiecinski, Jacek; Pieszko, Konrad; Razipour, Aryabod; Grodecki, Kajetan; Park, Caroline; Doris, Mhairi; Kwan, Alan; et al. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2022)
Background: Coronary computed tomography angiography (CCTA) allows non-invasive assessment of luminal stenosis and coronary atherosclerotic plaque. We aimed to develop and externally validate an artificial intelligence-based deep learning (DL) network for CCTA-based measures of plaque volume and stenosis severity. Methods: This was an international multicenter study of 1,183 patients undergoing CCTA at 11 sites. A novel DL convolutional neural network was trained to segment coronary plaque in 921 patients (5,045 lesions). The DL architecture consisted of a novel hierarchical convolutional long short-term memory (ConvLSTM) Network. The training set was further split temporally into training (80%) and internal validation (20%) datasets. Each coronary lesion was assessed in a 3D slab about the vessel centrelines. Following training and internal validation, the model was applied to an independent test set of 262 patients (1,469 lesions), which included an external validation cohort of 162 patients Results: In the test set, there was excellent agreement between DL and clinician expert reader measurements of total plaque volume (intraclass correlation coefficient [ICC] 0.964) and percent diameter stenosis (ICC 0.879; both p<0.001, see tables and figure). The average per-patient DL plaque analysis time was 5.7 seconds versus 25-30 minutes taken by experts. There was significantly higher overlap measured by the Dice coefficient (DC) for ConvLSTM compared to UNet (DC for vessel 0.94 vs 0.83, p<0.0001; DC for lumen and plaque 0.90 vs 0.83, p<0.0001) or DeepLabv3 (DC for vessel both 0.94; DC for lumen and plaque 0.89 vs 0.84, p<0.0001). Conclusions: A novel externally validated artificial intelligence-based network provides rapid measurements of plaque volume and stenosis severity from CCTA which agree closely with clinician expert readers.
CRIS-Team Scopus Importer:2022-06-10
Keywords: artificial intelligence; atherosclerosis; coronary computed tomography angiography; deep learning

Association of systemic inflammation with epicardial fat and coronary artery calcification - Gauss, Soeren; Klinghammer, Lutz; Steinhoff, Alina; Raaz-Schrauder, Dorette; Achenbach, Stephan; Garlichs, Christoph D.; Marwan, Mohamed (Inflammation Research, 2015)
Increased epicardial fat volume (EFV) has been shown to be associated with coronary atherosclerosis. While it is postulated to be an independent risk factor, a possible mechanism is local or systemic inflammation. We analyzed the relationship between coronary atherosclerosis, quantified by coronary calcium in CT, epicardial fat volume and systemic inflammation.Using non-enhanced dual-source CT, we quantified epicardial fat volume (EFV) and coronary artery calcium (CAC) in 391 patients who underwent coronary computed tomography for suspected coronary artery disease. In addition to traditional risk factors, serum markers of systemic inflammation were measured (IL-1?, IL-2, IL-4, IL-6, IL-7, IL-8, IL-10,IL-12, IL-13, IL-15, IL-17, IFN-?, TNF-?, hs-CRP, GM-CS, G-CSF, MCP-1, MIP-1, Eotaxin and IP-10). In 94 patients follow-up data were obtained after 1.9 ± 0.5 years.The 391 patients had a mean age of 60 ± 10 years, and 69 % were males. Mean EFV was 116 ± 50 mL. Median CAC was 12 (IQR 0; 152). CAC and EFV showed a significant correlation (? = 0.37; P < 0.001). EFV and CAC were significantly correlated with the traditional risk factors like age, male gender, diabetes, smoking and hypertension. With regard to biomarkers, CAC was significantly associated (negatively) to G-CSF and IL-13. EFV (median binned) was significantly associated (positively) with IP-10 (P = 0.002) and MCP-1 (? = 0.037). In follow-up, EFV showed a mean annualized progression of 6 mL (IQR 3; 9) (P < 0.001); CAC progressed by a mean of six Agatston Units (IQR 0; 30). The progression of CAC was significantly correlated with the extent of EFV (P < 0.001) while there was no significant correlation between progression of EFV or CAC with systemic inflammation markers.Epicardial fat volume and the baseline extent as well as progression of coronary atherosclerosis-measured by the calcium score-are significantly correlated. While both baseline EFV and CAC displayed significant correlations with systemic inflammation markers, biomarkers were not predictive of the progression of CAC or EFV.
EVALuna2:12060

A systematic report on non-coronary cardiac computed tomography angiographies in 1,097 patients from the German cardiac CT registry - Gitsioudis, Gitsios; Achenbach, Stephan; Schneider, S.; Schmermund, A.; Korosoglou, G.; Hausleiter, J.; Schroeder, S.; Rixe, R.; Leber, A.; Bruder, O.; Senges, J.; Marwan, Mohamed (2017)
EVALuna2:36028

A systematic report on non-coronary cardiac CTA in 1097 patients from the German cardiac CT registry - Gitsioudis, Gitsios; Schneider, Steffen; Schmermund, Axel; Korosoglou, Grigorios; Hausleiter, Jörg; Schroeder, Stephen; Rixe, Johannes; Leber, Alexander; Bruder, Oliver; Katus, Hugo A.; Senges, Jochen; Achenbach, Stephan; et al. (European Journal of Radiology, 2020)
Purpose: To prospectively evaluate contemporary indications, safety and diagnostic impact of cardiac CTA in patients undergoing cardiac CTA examinations for non-coronary clinical indications. Method: We analyzed 1097 consecutive patients from the German Cardiac CT Registry who underwent cardiac CTA between 2009 and 2014 due to clinically indicated non-coronary reasons using 64-slice or newer CT systems in twelve tertiary German heart centers in order to evaluate the impact of clinical indications on procedure-associated parameters. All participating centers electronically submitted patient and examination data including detailed indications, clinical symptoms, procedural parameters, complications and diagnostic results in a predefined template. Results: The most frequent indication for non-coronary cardiac CTA was the evaluation of pulmonary vein anatomy (65.9 %, 723/1097). In the remaining cases, most frequent indications were planning before TAVI (44.5 %, 69/155), evaluation of valvular disease (31.6 %, 49/155), and evaluation of implants (5.8 %, 9/155). Non-coronary cardiac CTA required a median amount of iodinated contrast agent of 100.0 mL (IQR 95.0–110.0 mL). Prospectively ECG-triggered acquisition was the most frequently used protocol (74.0 %), followed by retrospectively ECG-gated acquisition with and without tube current modulation (19.9 % and 6.0 %, respectively), resulting in a mean estimated effective dose of 5.2 mSv (IQR 2.9−9.5 mSv, average conversion factor k = 0.026). Overall, complication rate was very low (1.5 %). Non-coronary cardiac CTA revealed a new clinical diagnostic aspect in 3.2 % of all patients, and a new main clinical diagnosis in 2.2 %. Conclusions: Non-coronary cardiac CTA as a routinely applied diagnostic modality is associated with a very low procedure-related rate of complications and reasonably low radiation exposure using contemporary CT systems.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Non-coronary CTA; Pulmonary veins; TAVI; Valvular disease

Automated attenuation-based selection of tube voltage and tube current for coronary CT angiography: Reduction of radiation exposure versus a BMI-based strategy with an expert investigator - Layritz, Christian; Muschiol, Gerd; Flohr, Thomas; Bietau, Christian; Marwan, Mohamed; Schuhbaeck, Annika; Schmid, Jasmin; Ropers, Dieter; Achenbach, Stephan; Pflederer, Tobias (Journal of Cardiovascular Computed Tomography, 2013)
Background: Recently developed automated algorithms use the topogram and the corresponding attenuation information before coronary CT angiography (CTA) to allow for an individualized anatomic-based selection of tube current (mAs) and voltage (kV). Objectives: The value of these algorithms in reducing the associated radiation exposure was evaluated. Methods: One hundred patients underwent coronary CTA with dual-source CT with prospectively electrocardiogram-triggered axial data acquisition. In all patients, tube parameters (current and voltage) were suggested by both an experienced investigator according to the patient's body mass index (BMI; calculated as weight divided by height squared; kg/m2) and by an automated software according to attenuation values of the initial topogram. The first 50 consecutive patients (group 1) underwent coronary CTA with dual-source CT with tube parameters suggested by the experienced investigator (BMI-based tube parameters), whereas in another 50 consecutive patients (group 2) CT data acquisition was performed with tube settings of the automated software. Subsequently, subjective image quality (4-point rating score from 0= nondiagnostic to 3= excellent image quality), image noise (SD of CT number within the aortic root), as well as signal- and contrast-to-noise ratios and mean effective radiation doses, were compared between both groups. Results: Both groups showed comparable image quality parameters (group 1 vs 2: noise, 28.1± 6.0 HU vs 29.9 ± 5.4 HU, P= .12; signal-to-noise ratio, 16.4 ± 3.9 vs 16.8 ± 4.1, P= .54; contrast-to-noise ratio, 18.6 ± 4.1 vs 19.2 ± 4.3, P= .49; 4-point rating score, 2.8 ± 0.3 vs 2.9± 0.3, P= .81). Tube voltage, current, and mean effective radiation dose for groups 1 and 2 were 111 ± 12 kV and 108 ± 12 kV (P= .18), 361 ± 32 mAs and 320 ± 48 mAs (P < .001), and 2.3 mSv (25th; 75th percentile, 1.5; 2.8 mSv) and 1.4 mSv (25th; 75th percentile, 1.1; 1.9 mSv) (P < .001), respectively. Conclusions: Automated attenuation-based selections of individualized tube parameters are superior to BMI-based selections with expert oversight and show a potential for reduction of radiation exposure in coronary CTA, and image quality is maintained. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Automated software; Coronary CT angiography; Radiation dose; Tube current; Tube voltage

Automated quantification of epicardial adipose tissue from non-contrast CT on multi-center and multi-vendor data using deep learning - Commandeur, F.; Göller, Markus; Razipour, A.; Cadet, S.; Hell, Michaela; Kwiecinski, J.; Chen, X.; Chang, H. J.; Achenbach, Stephan; Berman, D. S.; Slomka, P. J.; Tamarappoo, B. K.; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Cardiac CT for Quantification of Epicardial Fat: Where to Measure and Why? - Marwan, Mohamed; Achenbach, Stephan (Current Cardiovascular Imaging Reports, 2015)
Epicardial adipose tissue has been attracting increasing attention over the last decade with a large body of evidence pointing towards significant associations between the volume of epicardial fat and atherosclerotic and non-atherosclerotic heart diseases. On the other hand, recent data from relatively large studies question the hypothesis of epicardial fat as an independent risk factor for atherosclerosis. This article reviews the available literature concerning imaging and quantification of epicardial adipose tissue and its potential clinical significance.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac CT; Epicardial; Intrathoracic; Paracardiac; Pericardial

Changes of tricuspid valve geometry after interventional implantation of an anuloplasty band - Landendinger, M.; Smolka, S.; Haug, J.; Tröbs, Monique; Ammon, Fabian; Achenbach, Stephan; Arnold, Martin; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Chronic Kidney Disease and Coronary Artery Disease: JACC State-of-the-Art Review - Sarnak, Mark J.; Amann, Kerstin Ute; Bangalore, Sripal; Cavalcante, João L.; Charytan, David M.; Craig, Jonathan C.; Gill, John S.; Hlatky, Mark A.; Jardine, Alan G.; Landmesser, Ulf; Newby, L. Kristin; Herzog, Charles A.; et al. (Journal of the American College of Cardiology, 2019)
Chronic kidney disease (CKD) is a major risk factor for coronary artery disease (CAD). As well as their high prevalence of traditional CAD risk factors, such as diabetes and hypertension, persons with CKD are also exposed to other nontraditional, uremia-related cardiovascular disease risk factors, including inflammation, oxidative stress, and abnormal calcium-phosphorus metabolism. CKD and end-stage kidney disease not only increase the risk of CAD, but they also modify its clinical presentation and cardinal symptoms. Management of CAD is complicated in CKD patients, due to their likelihood of comorbid conditions and potential for side effects during interventions. This summary of the Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference on CAD and CKD (including end-stage kidney disease and transplant recipients) seeks to improve understanding of the epidemiology, pathophysiology, diagnosis, and treatment of CAD in CKD and to identify knowledge gaps, areas of controversy, and priorities for research.
CRIS-Team Scopus Importer:2019-10-01
Keywords: acute coronary syndromes; calcification; chronic kidney disease; coronary artery disease; revascularization

Chronic kidney disease and valvular heart disease: conclusions from a Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference - Marwick, Thomas H.; Amann, Kerstin Ute; Bangalore, Sripal; Cavalcante, João L.; Charytan, David M.; Craig, Jonathan C.; Gill, John S.; Hlatky, Mark A.; Jardine, Alan G.; Landmesser, Ulf; Newby, L. Kristin; Herzog, Charles A.; et al. (Kidney International, 2019)
Chronic kidney disease (CKD) is a major risk factor for valvular heart disease (VHD). Mitral annular and aortic valve calcifications are highly prevalent in CKD patients and commonly lead to valvular stenosis and regurgitation, as well as complications including conduction system abnormalities and endocarditis. VHD, especially mitral regurgitation and aortic stenosis, is associated with significantly reduced survival among CKD patients. Knowledge related to VHD in the general population is not always applicable to CKD patients because the pathophysiology may be different, and CKD patients have a high prevalence of comorbid conditions and elevated risk for periprocedural complications and mortality. This Kidney Disease: Improving Global Outcomes (KDIGO) review of CKD and VHD seeks to improve understanding of the epidemiology, pathophysiology, diagnosis, and treatment of VHD in CKD by summarizing knowledge gaps, areas of controversy, and priorities for research.
CRIS-Team Scopus Importer:2019-09-24
Keywords: aortic stenosis; chronic kidney disease; end-stage kidney disease; mitral annular calcification; valvular heart disease

Clinical application of cardiac computed tomography: Current recommendations Klinische Anwendung der kardialen Computertomographie: Aktuelle Empfehlungen - Tesche, Christian; Marwan, Mohamed; Hell, Michaela; Schmermund, Axel; Loßnitzer, Dirk; Möhlenkamp, Stefan; Ropers, Dieter; Achenbach, Stephan; Korosoglou, Grigorios (Herz, 2025)
Cardiac computed tomography (CT) is suitable for use in patients with a low to intermediate pretest probability for risk stratification and for a clear exclusion of coronary heart disease. Furthermore, in addition to a purely anatomical depiction of coronary stenosis it enables the morphological assessment of the underlying plaques and a functional assessment of the hemodynamic relevance. The clinical value of cardiac CT is taken into account in the guidelines of the European Society of Cardiology (ESC) on chronic coronary syndrome with a class 1 recommendation. Cardiac CT therefore has an essential gatekeeper function with respect to the indications for coronary interventions. In the field of structural heart diseases cardiac CT is a core element in the preprocedural planning of heart valve interventions and is the first choice procedure in the postinterventional assessment of unclear findings. Therefore, for interventional heart valve replacement CT-based planning is nowadays the established standard in the clinical diagnostics.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Calcium scoring; Cardiac imaging; Coronary artery disease; Myocardial ischemia; Structural heart diseases

Commissural misalignment independently predicts leaflet thrombosis after transcatheter aortic valve implantation - Jung, Susanne; Ammon, Fabian; Smolka, Silvia; Moshage, Maximilian; Marwan, Mohamed; Achenbach, Stephan (Clinical Research in Cardiology, 2023)
Aims: Transcatheter aortic valve implantation (TAVI) has become a minimally invasive alternative to surgical aortic valve replacement. Hypo-attenuated leaflet thickening (HALT)—a marker of subclinical leaflet thrombosis commonly detected by cardiac computed tomography (CT) after TAVI—may influence valve durability and function. The purpose of this study was to compare commissural alignment of the native and prosthetic aortic valves in cardiac CT in subjects with and without HALT and thereby identify commissural misalignment as potential predictor for leaflet thrombosis after TAVI. Methods and results: In 170 subjects, 85 with and 85 without HALT in post-TAVI CT, commissural orientation of the prosthesis was determined comparing native and prosthetic aortic valve orientation in cardiac CT by measuring the commissural angle relative to the right coronary ostium in the aortic valve plane. For the prosthetic valve, any deviation ≤ 15° compared to the native valve was classified as “aligned”; 16–30° as “mild”, 31–45° as “moderate” and ≥ 45° as “severe” misalignment. Among subjects with HALT, median angular deviation was higher (36°, IQR 31°) than in the control group (29°, IQR 29°, p = 0.042). “Severe” misalignment was more frequent in subjects who developed HALT (n = 31, 37%) compared to the control group (n = 17, 20%, p = 0.013). In logistic regression analysis, more severe deviation (p = 0.015, OR = 1.02 per 1° deviation) and “severe” misalignment (p = 0.018, OR = 2.2) represented independent predictors for the occurrence of HALT after TAVI. Conclusion: Subclinical leaflet thrombosis after TAVI is associated with commissural misalignment. Potential clinical advantages of obtaining commissural alignment remain to be systematically assessed. Graphical abstract: [Figure not available: see fulltext.] Association of HALT with commissural misalignment after TAVI. HALT hypo-attenuated leaflet thickening, IQR interquartile range, TAVI transfemoral aortic valve replacement
CRIS-Team Scopus Importer:2023-04-21
Keywords: Commissural misalignment; HALT; Leaflet thrombosis; TAVI

Comparison of adenosine-independent pressure indices to fractional flow reserve in stent-jailed bifurcation side branches - Altstidl, Johannes Michael; Achenbach, Stephan; Marwan, Mohamed; Tröbs, Monique; Schacher, Nora; Ferstl, Paul; Gerlach, Andreas; Schlundt, Christian; Gaede, Luise (Catheterization and Cardiovascular Interventions, 2022)
Objectives and Background: This study aims to evaluate whether the high correlation and classification agreement of the instantaneous wave-free ratio (iFR) and the resting distal coronary to aortic pressure ratio (Pd/Pa) with the fractional flow reserve (FFR) can be confirmed in stent-jailed side branches (J-SB). Methods: Consecutive patients (n = 49) undergoing provisional stenting were prospectively enrolled and a physiological assessment of the J-SB (n = 51) was performed. FFR, iFR, and Pd/Pa were measured and the hemodynamic relevance was determined using cutoff values of ≤0.80, ≤0.89, and ≤0.92, respectively. Results: Both iFR (r = 0.75) and Pd/Pa (r = 0.77) correlated closely with FFR. Classification agreement with FFR was 78% for iFR (81% sensitivity, 77% specificity) and 75% for Pd/Pa (63% sensitivity and 80% specificity). However, angiographic diameter stenosis and pressure indices correlated poorly. For a threshold of ≥70% stenosis, agreement concerning hemodynamic relevance was found in 59% for FFR, 69% for iFR, and 61% for Pd/Pa. Conclusion: As reported for other lesion types, FFR and the adenosine-independent pressure indices iFR and Pd/Pa show close correlation and a high classification agreement of approximately 75%–80% in J-SB. Therefore, iFR can be regarded as a recommendable alternative to FFR for the guidance of provisional stenting in bifurcation lesions.
CRIS-Team Scopus Importer:2022-07-01
Keywords: catheterization diagnostic; coronary artery disease; fractional flow reserve

Comparison of direct oral anticoagulants to vitamin-K antagonists as treatment for leaflet thrombosis after Transcatheter Aortic Valve Implantation (TAVI) - Ferstl, Paul; Marwan, Mohamed; Achenbach, Stephan; Bittner, Daniel (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Comparison of Dual-Source Computed Tomography for the Quantification of the Aortic Valve Area in Patients With Aortic Stenosis Versus Transthoracic Echocardiography and Invasive Hemodynamic Assessment - Ropers, Dieter; Ropers, Ulrike; Marwan, Mohamed; Schepis, Titiano; Pflederer, Tobias; Wechsel, Martin; Klinghammer, Lutz; Flachskampf, Frank A.; Daniel, Werner; Achenbach, Stephan (American Journal of Cardiology, 2009)
We compared the measurements of the aortic valve area (AVA) using dual-source computed tomography (DSCT) in patients with mid to severe aortic stenosis to measurements using transthoracic echocardiography (TTE) and invasive hemodynamic assessment. A total of 50 patients (mean age 73 ± 10 years) with suspected aortic stenosis were included. The computed tomographic data were acquired using DSCT with standardized scan parameters (2 × 64 × 0.6 mm collimation, 330-ms rotation, 120-kV tube voltage, 560 mA/rot tube current). After injection of 35 ml contrast agent (flow rate 5 ml/s), a targeted volume data set, ranging from the top of the leaflets to the infundibulum, was acquired. Ten cross-sectional data sets (slice thickness 1 mm, no overlap, increment 0.6 mm) were reconstructed during systole in 5% increments of the R-R interval. The AVA determined in systole by planimetry was compared to the calculated AVA values using the continuity equation on TTE and the Gorlin formula on catheterization. DSCT allowed the planimetry of the AVA in all patients. The mean AVA using DSCT was 1.16 ± 0.47 cm2 compared to a mean AVA of 1.04 ± 0.45 cm2 using TTE and 1.06 ± 0.45 cm2 using catheterization, with a significant correlation between DSCT/TTE (r = 0.93, p <0.001) and DSCT/cardiac catheterization (r = 0.97, p <0.001). However, DSCT demonstrated a slight, but significant, overestimation of the AVA compared to TTE (+0.12 ± 0.17 cm) and catheterization (+0.10 ± 0.12 cm2). In conclusion, DSCT permits one to assess the AVA with a high-image quality and diagnostic accuracy compared to TTE and invasive determination. © 2009 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10

Comparison of fractional flow reserve and instantaneous wave-free ratio for the hemodynamic assessment of jailed side branches in bifurcation stenting - Altstidl, J. M.; Tröbs, Monique; Achenbach, Stephan; Gaede, L.; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Comparison of invasively measured FFR with FFR derived from coronary CT angiography for detection of lesion-specific ischemia: Results from a PC-based prototype algorithm - Röther, Jens; Moshage, Maximilian; Dey, Damini; Schwemmer, Chris; Tröbs, Monique; Blachutzik, Florian; Achenbach, Stephan; Schlundt, Christian; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: We evaluated the diagnostic accuracy of a novel prototype for on-site determination of CT-based FFR (cFFR) on a standard personal computer (PC) compared to invasively measured FFR in patients with suspected coronary artery disease. METHODS: A total of 91 vessels in 71 patients (mean age 65 ± 9 years) in whom coronary CT angiography had been performed due to suspicion of coronary artery disease, and who subsequently underwent invasive coronary angiography with FFR measurement were analyzed. For both cFFR and FFR, a threshold of ≤0.80 was used to indicate a hemodynamically relevant stenosis. The mean time needed to calculate cFFR was 12.4 ± 3.4 min. A very close correlation between cFFR and FFR could be shown (r = 0.85; p < 0.0001) with Bland-Altman analysis showing moderate agreement between FFR and cFFR with mild systematic overestimation of FFR values in CT (mean difference 0.0049, 95% limits of agreement ±2SD -0.007 to 0.008). Compared to FFR, the sensitivity of cFFR to detect hemodynamically significant lesions was 91% (19/21, 95% CI: 70%-99%), specificity was 96% (67/70, 95% CI: 88%-99%), positive predictive value 86% (95% CI: 65%-97%) and negative predictive value was 97% (95% CI: 90%-100%) with an accuracy of 93%. CONCLUSION: cFFR obtained using an on-site algorithm implemented on a standard PC shows high diagnostic accuracy to detect lesions causing ischemia as compared to FFR. Importantly, the time needed for analysis is short which may be useful for improving clinical workflow.
EVALuna2:36006

Comparison of oral anticoagulation by vitamin-K antagonists and non-vitamin-K antagonists for treatment of leaflet thickening after transcatheter aortic valve implantation (TAVI) - Ferstl, Paul; Achenbach, Stephan; Marwan, Mohamed; Bittner, Daniel O. (International Journal of Cardiology, 2023)
Introduction: Hypoattenuated leaflet thickening (HALT), as identified by CT imaging, is not infrequent after transcatheter aortic valve implantation (TAVI). The best choice of oral anticoagulation is unknown. We compared the effectiveness of Direct Oral AntiCoagulants (DOAC) and Vitamin-K Antagonists (VKA) to resolve HALT in patients with serial CT aquisitions. Methods: A total of 46 consecutive TAVI patients in whom anticoagulation had been initiated because of HALT and who underwent follow-up CT were identified. Indication and type of anticoagulation was according to physician discretion. Patients on DOAC were compared to VKA therapy regarding resolution of HALT. Results: Mean age of the 46 patients was 80 ± 6 years (59% men), and the mean duration of anticoagulation was 156 days. Overall, 41 patients (89%) showed resolution of HALT with anticoagulation therapy, whereas HALT persisted in 5 patients (11%). Resolution of HALT was seen in 26 out of 30 (87%) patients receiving VKA and in 15 out of 16 (94%) patients receiving DOAC, respectively. Groups did not differ regarding age, cardiovascular risk factors, TAVI prosthesis type and size or duration of anticoagulation (all p > 0.05). Conclusion: Anticoagulation therapy resolves leaflet thickening after TAVI in most patients. Non-Vitamin-K antagonists seem to be an effective alternative to Vitamin-K antagonists. This finding needs to be confirmed in larger prospective trials.
CRIS-Team Scopus Importer:2023-06-09
Keywords: Anticoagulation; HALT; Leaflet thickening; TAVI

Comparison of quantitative atherosclerotic plaque burden from coronary CT angiography in patients with first acute coronary syndrome and stable coronary artery disease - Dey, Damini; Achenbach, Stephan; Schuhbaeck, Annika; Pflederer, Tobias; Nakazato, Ryo; Slomka, Piotr J.; Berman, Daniel S.; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2014)
Coronary CTA allows characterization of non-calcified and calcified plaque and identification of high-risk plaque features.We aimed to quantitatively characterize and compare coronary plaque burden from CTA in patients with a first acute coronary syndrome (ACS) and controls with stable coronary artery disease.We retrospectively analyzed consecutive patients with non-ST-segment elevation myocardial infarction (NSTEMI) or unstable angina with a first ACS, who underwent CTA as part of their initial workup before invasive coronary angiography and age- and gender-matched controls with stable chest pain; controls also underwent CTA with subsequent invasive angiography (total n = 28). Culprit arteries were identified in ACS patients. Coronary arteries were analyzed by automated software to quantify calcified plaque (CP), noncalcified plaque (NCP), and low-density NCP (LD-NCP, attenuation <30 Hounsfield units) volumes, and corresponding burden (plaque volume × 100%/vessel volume), stenosis, remodeling index, contrast density difference (maximum percent difference in attenuation/cross-sectional area from proximal cross-section), and plaque length.ACS patients had fewer lesions (median, 1), with higher total NCP and LD-NCP burdens (NCP: 57.4% vs 41.5%; LD-NCP: 12.5% vs 8%; P <= .04), higher maximal stenoses (85.6% vs 53.0%; P = .003) and contrast density differences (46.1 vs 16.3%; P < .006). Per-patient CP burden was not different between ACS and controls. NCP and LD-NCP plaque burden was higher in culprit vs nonculprit arteries (NCP: 57.8% vs 9.5%; LD-NCP: 8.4% vs 0.6%; P <= .0003); CP was not significantly different. Culprit arteries had increased plaque lengths, remodeling indices, stenoses, and contrast density differences (46.1% vs 10.9%; P <= .001).Noninvasive quantitative coronary artery analysis identified several differences for ACS, both on per-patient and per-vessel basis, including increased NCP, LD-NCP burden, and contrast density difference.
EVALuna2:11863

Comparison of standard- and high-dose intracoronary adenosine for the measurement of coronary fractional flow reserve (FFR) - Röther, Jens; Achenbach, Stephan; Tröbs, Monique; Blachutzik, Florian; Nef, Holger; Schlundt, Christian; Marwan, Mohamed (Clinical Research in Cardiology, 2016)
BACKGROUND: Measurement of fractional flow reserve (FFR) by intravenous infusion or intracoronary injection of adenosine is the reference method to determine the hemodynamic relevance of coronary artery stenoses. The goal of this prospective study was to compare standard (40 µg adenosine for the right and 80 µg for the left coronary artery) to high doses of intracoronary adenosine for FFR measurement. METHODS AND RESULTS: In 130 intermediate coronary artery stenoses, two sequential FFR measurements were performed with standard-dose intracoronary application of adenosine (40 µg for the right and 80 μg for the left coronary artery), followed by one FFR measurement with a bolus of 200 μg for the right and 400 μg for the left coronary artery. There was strong correlation (r = 0.97, p < 0.001) between FFR values determined with standard-dose adenosine (0.86 ± 0.08) versus high-dose adenosine (0.85 ± 0.08). High-dose adenosine did not yield FFR values ≤0.80 or ≤0.75 significantly more frequently than standard-dose adenosine. Patients reported more discomfort after high-dose adenosine application compared to standard-dose adenosine (p < 0.001). CONCLUSIONS: For FFR measurements with intracoronary adenosine injection, results achieved with doses of 40 µg adenosine for the right and 80 µg for the left coronary artery display no clinically relevant difference to doses of 200 and 400 µg, respectively.
EVALuna2:33662

Comparison of Two Contemporary Quantitative Atherosclerotic Plaque Assessment Tools for Coronary Computed Tomography Angiography: Single-Center Analysis and Multi-Center Patient Cohort Validation - Weichsel, Loris; Giesen, Alexander; André, Florian; Renker, Matthias; Baumann, Stefan; Breitbart, Philipp; Beer, Meinrad; Maurovitch-Horvat, Pal; Szilveszter, Bálint; Vattay, Borbála; Buss, Sebastian J.; Marwan, Mohamed; et al. (Diagnostics, 2024)
Background: Coronary computed tomography angiography (CCTA) provides non-invasive quantitative assessments of plaque burden and composition. The quantitative assessment of plaque components requires the use of analysis software that provides reproducible semi-automated plaque detection and analysis. However, commercially available plaque analysis software can vary widely in the degree of automation, resulting in differences in terms of reproducibility and time spent. Aim: To compare the reproducibility and time spent of two CCTA analysis software tools using different algorithms for the quantitative assessment of coronary plaque volumes and composition in two independent patient cohorts. Methods: The study population included 100 patients from two different cohorts: 50 patients from a single-center (Siemens Healthineers, SOMATOM Force (DSCT)) and another 50 patients from a multi-center study (5 different > 64 slice CT scanner types). Quantitative measurements of total calcified and non-calcified plaque volume of the right coronary artery (RCA), left anterior descending (LAD), and left circumflex coronary artery (LCX) were performed on a total of 300 coronaries by two independent readers, using two different CCTA analysis software tools (Tool #1: Siemens Healthineers, syngo.via Frontier CT Coronary Plaque Analysis and Tool #2: Siemens Healthineers, successor CT Coronary Plaque Analysis prototype). In addition, the total time spent for the analysis was recorded with both programs. Results: The patients in cohorts 1 and 2 were 62.8 ± 10.2 and 70.9 ± 11.7 years old, respectively, 10 (20.0%) and 35 (70.0%) were female and 34 (68.0%) and 20 (40.0%), respectively, had hyperlipidemia. In Cohort #1, the inter- and intra-observer variabilities for the assessment of plaque volumes per patient for Tool #1 versus Tool #2 were 22.8%, 22.0%, and 26.0% versus 2.3%, 3.9%, and 2.5% and 19.7%, 21.4%, and 22.1% versus 0.2%, 0.1%, and 0.3%, respectively, for total, noncalcified, and calcified lesions (p < 0.001 for all between Tools #1 and 2 both for inter- and intra-observer). The inter- and intra-observer variabilities using Tool #2 remained low at 2.9%, 2.7%, and 3.0% and 3.8%, 3.7%, and 4.0%, respectively, for total, non-calcified, and calcified lesions in Cohort #2. For each dataset, the median processing time was higher for Tool #1 versus Tool #2 (459.5 s IQR = 348.0–627.0 versus 208.5 s; IQR = 198.0–216.0) (p < 0.001). Conclusion: The plaque analysis Tool #2 (CT-guided PCI) encompassing a higher degree of automated support required less manual editing, was more time-efficient, and showed a higher intra- and inter-observer reproducibility for the quantitative assessment of plaque volumes both in a representative single-center and in a multi-center validation cohort.
CRIS-Team Scopus Importer:2024-02-02
Keywords: calcified; composition; inter- and intra-observer variabilities; non-calcified; plaque quantification; plaque volume; serial studies

Complete recovery after out-of-hospital cardiac arrest with prolonged (59 min) mechanical cardiopulmonary resuscitation, mild therapeutic hypothermia and complex percutaneous coronary intervention for ST-elevation myocardial infarction - Zimmermann, Stefan; Rohde, Doris; Ludwig, Josef; Achenbach, Stephan; Marwan, Mohamed (Heart & Lung, 2014)
We report on a 68 years old survivor of an out-of-hospital cardiac arrest with favorable neurological outcome following prolonged cardiopulmonary resuscitation (CPR 59 min) until return of spontaneous circulation (ROSC) due to ST-elevation myocardial infarction (STEMI). The case demonstrates the beneficial effect of an optimal rescue chain including basic life support performed by trained bystanders, short response time of the emergency medical service, uninterrupted CPR during transportation using a mechanical chest compression system (LUCAS®), in combination with optimal intensive care management of cardiogenic shock after ROSC including multivessel emergency percutaneous coronary intervention (PCI) and intravascular therapeutic hypothermia (Coolgard®-System).
EVALuna2:11884

Computational fluid dynamics: can computed tomography imaging compete with cath-lab physiology? - Marwan, Mohamed (Cardiovascular Research, 2019)
CRIS-Team WoS Importer:2019-04-12

Computed tomography-derived characterisation of pericoronary,epicardial and paracardial adipose tissue and its association with myocardial ischemia as assessed by computed and invasive fractional flow - Göller, Markus; Duncker, Hendrik; Moshage, Maximilian; Dey, D.; Bittner, Daniel; Ammon, Fabian; Achenbach, Stephan; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Computed Tomography-derived Characterization of Pericoronary, Epicardial, and Paracardial Adipose Tissue and Its Association with Myocardial Ischemia as Assessed by Computed Fractional Flow Reserve - Duncker, Hendrik; Achenbach, Stephan; Moshage, Maximilian; Dey, Damini; Bittner, Daniel O.; Ammon, Fabian; Marwan, Mohamed; Oeller, Markus (Journal of Thoracic Imaging, 2023)
Background: Increased pericoronary adipose tissue (PCAT) attenuation derived from coronary computed tomography (CT) angiography (CTA) relates to coronary inflammation and cardiac mortality. We aimed to investigate the association between CT-derived characterization of different cardiac fat compartments and myocardial ischemia as assessed by computed fractional flow reserve (FFRCT). Methods: In all, 133 patients (median 64 y, 74% male) with coronary artery disease (CAD) underwent CTA including FFRCT measurement followed by invasive FFR assessment (FFRINVASIVE). CT attenuation and volume of PCAT were quantified around the proximal right coronary artery (RCA), left anterior descending artery (LAD), and left circumflex artery (LCX). Epicardial adipose tissue (EAT) and paracardial adipose tissue (PAT; all intrathoracic adipose tissue outside the pericardium) were quantified in noncontrast cardiac CT datasets. Results: Median FFRCT was 0.86 [0.79, 0.91] and median FFRINVASIVE was 0.87 [0.81, 0.93]. Subjects with the presence of myocardial ischemia (n=26) defined by an FFRCT-threshold of ≤0.75 showed significantly higher RCA PCAT attenuation than individuals without myocardial ischemia (n=107) (-75.1±10.8 vs. -81.1±10.6 HU, P=0.011). In multivariable analysis adjusted for age, body mass index, sex and risk factors, increased RCA PCAT attenuation remained a significant predictor of myocardial ischemia. Between individuals with myocardial ischemia compared with individuals without myocardial ischemia, there was no significant difference in the volume and CT attenuation of EAT and PAT or in the PCAT volume of RCA, LAD, and LCX. Conclusions: Increased RCA PCAT attenuation is associated with the presence of myocardial ischemia as assessed by FFR, while PCAT volume, EAT, and PAT are not.
CRIS-Team Scopus Importer:2023-01-06
Keywords: computed tomography attenuation; coronary computed tomography angiography; epicardial adipose tissue; fractional flow reserve; myocardial ischemia; paracardial adipose tissue; pericoronary adipose tissue

Computed tomography imaging in the context of transcatheter aortic valve implantation (TAVI) / transcatheter aortic valve replacement (TAVR): An expert consensus document of the Society of Cardiovascular Computed Tomography. - Blanke, Philipp; Weir-Mccall, Jonathan R.; Achenbach, Stephan; Delgado, Victoria; Hausleiter, Joerg; Jilaihawi, Hasan; Marwan, Mohamed; Norgaard, Bjarne L.; Piazza, Niccolo; Schoenhagen, Paul; Leipsic, Jonathon A. (Journal of Cardiovascular Computed Tomography, 2019)
EVALuna2:213035

Computed Tomography Imaging in the Context of Transcatheter Aortic Valve Implantation (TAVI)/Transcatheter Aortic Valve Replacement (TAVR): An Expert Consensus Document of the Society of Cardiovascular Computed Tomography - Blanke, Philipp; Weir-Mccall, Jonathan R.; Achenbach, Stephan; Delgado, Victoria; Hausleiter, Joerg; Jilaihawi, Hasan; Norgaard, Bjarne L.; Piazza, Niccolo; Schoenhagen, Paul; Leipsic, Jonathon A.; Marwan, Mohamed (Journal of the American College of Cardiology : Cardiovascular imaging, 2019)
EVALuna2:35956

Computer-aided evaluation of low-dose and low-contrast agent third-generation dual-source CT angiography prior to transcatheter aortic valve implantation (TAVI) - Dankerl, Peter; Hammon, Matthias; Seuß, Hannes; Tröbs, Monique; Schuhbaeck, Annika; Hell, Michaela M.; Achenbach, Stephan; Uder, Michael; Marwan, Mohamed; Cavallaro, Alexander Josef (International Journal of Computer Assisted Radiology and Surgery, 2016)
To evaluate the performance of computer-aided evaluation software for a comprehensive workup of patients prior to transcatheter aortic valve implantation (TAVI) using low-contrast agent and low radiation dose third-generation dual-source CT angiography.We evaluated 30 consecutive patients scheduled for TAVI. All patients underwent ECG-triggered high-pitch dual-source CT angiography of the aortic root and aorta with a standardized contrast agent volume (30 ml Imeron350, flow rate 4 ml/s) and low-dose (100 kv/350 mAs) protocol. An expert (10 years of experience) manually evaluated aortic root and iliac access dimensions (distance between coronary ostia and aortic annulus, minimal/maximal diameters and area-derived diameter of the aortic annulus) and best CT-predicted fluoroscopic projection angle as the reference standard. Utilizing computer-aided software (syngo.via), the same pre-TAVI workup was performed and compared to the reference standard.Mean CTDI[Formula: see text] was 3.46 mGy and mean DLP 217.6 ± 12.1 mGy cm, corresponding to a mean effective dose of 3.7 ± 0.2 mSv. Computer-aided evaluation was successful in all but one patient. Compared to the reference standard, Bland-Altman analysis indicated very good agreement for the distances between aortic annulus and coronary ostia (RCA: mean difference 0.8 mm; 95 % CI 0.4-1.2 mm; LM: mean difference 0.9 mm; 95 % CI 0.5-1.3 mm); however, we demonstrated a systematic overestimation of annulus- derived diameter using the software (mean difference 44.4 mm[Formula: see text]; 95 % CI 30.4-58.3 mm[Formula: see text]). Based on respective annulus dimensions, the recommended prosthesis size (Edwards SAPIEN 3) matched in 26 out of the 29 patients (90 %). CT-derived fluoroscopic projection angles showed an excellent agreement for both methods. Out of 58 iliac arteries, 15 (25 %) arteries could not be segmented by the software. Preprocessing time of the software was 71 ± 11 s (range 51-96 s), and reading time with the software was 118 ± 31 s (range 68-201 s).In the workup of pre-TAVI CT angiography, computer-aided evaluation of low-contrast, low-dose examinations is feasible with good agreement and quick reading time. However, a systematic overestimation of the aortic annulus area is observed.
EVALuna2:14602

Contrast volume reduction using third generation dual source computed tomography for the evaluation of patients prior to transcatheter aortic valve implantation - Bittner, Daniel O.; Klinghammer, Lutz; Schuhbaeck, Annika; Hell, Michaela M.; Muschiol, Gerd; Gauss, Soeren; Lell, Michael; Uder, Michael; Hoffmann, Udo; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (European Radiology, 2016)
Chronic renal failure is common in patients referred for transcatheter aortic valve implantation (TAVI). CT angiography is recommended and provides crucial information prior to TAVI. We evaluated the feasibility of a reduced contrast volume protocol for pre-procedural CT imaging.Forty consecutive patients were examined with prospectively ECG-triggered high-pitch spiral acquisition using a novel third-generation dual-source CT system; 38 ml contrast agent was used. Image quality was graded on a visual scale (1-4). Contrast attenuation was measured at the level of the aortic root and at the iliac bifurcation.Mean patient age was 82 ± 6 years (23 males; 58 %). Mean attenuation/average image quality was 285 ± 60 HU/1.5 at the aortic annulus compared to 289 ± 74 HU/1.8 at the iliac bifurcation (p = 0.77/p = 0.29). Mean estimated effective radiation dose was 2.9 ± 0.3 mSv. A repeat acquisition was necessary in one patient due to image quality. Out of the 35 patients who underwent TAVI, 31 (89 %) patients had no or mild aortic regurgitation. Thirty-two (91 %) patients were discharged successfully.Pre-procedural CTA with a total of 38 ml contrast volume is feasible and clinically useful, using third-generation dual-source CT, allowing comprehensive imaging for procedural success.o Reduction of contrast agent volume is crucial in patients with chronic renal failure. o Novel third-generation computed tomography helps to reduce contrast agent volume. o Pre-procedural CT allows comprehensive imaging for procedural success before heart valve implantation. o A low-contrast CT protocol is feasible for pre-procedural TAVI planning.
EVALuna2:14600

Coronary Artery Disease Burden in Patients with Stable Angina and Symptoms of Heart Failure: A Coronary Computed Tomography Angiography Study from the German Cardiac CT Registry - Gitsioudis, Gitsios; Achenbach, Stephan; Schneider, S.; Schmermund, A.; Korosoglou, G.; Hausleiter, J.; Schroeder, S.; Rixe, J.; Leber, A.; Bruder, O.; Senges, J.; Marwan, Mohamed (2017)
EVALuna2:36029

Coronary computed tomography angiography (CCTA) in patients with suspected stable coronary artery disease (CAD): diagnostic impact and clinical consequences in the German Cardiac CT Registry depending on stress test results - Barth, Sebastian; Hausleiter, Joerg; Moshage, Werner; Korosoglou, Grigorios; Leber, Alexander; Schmermund, Axel; Gohlke, Helmut; Bruder, Oliver; Dill, Thorsten; Schroeder, Stephen; Kerber, Sebastian; Hamm, Karsten; et al. (International Journal of Cardiovascular Imaging, 2019)
To evaluate diagnostic impact of clinical use of coronary computed tomography angiography (CCTA) in patients with suspected stable coronary artery disease (CAD) and its consequences in daily practice for patient management, depending on stress test results in daily practice. Between 2009 and 2014 of a total population of 1352 patients of the German Cardiac Computed Tomography (CT) Registry who had previously undergone stress tests, CCTA visualizations were carried out on the coronary arteries with suspected stable CAD. Patients were divided into three groups according to stress test results: Group 1 with inconclusive (n = 178, 13.2%), Group 2 with ischemia in stress test (n = 372, 27.5%) and Group 3 without ischemia in stress test (n = 802, 59.3%). The test of preference was the stress electrocardiogram (ECG), which was performed more frequently in patients without ischemia in stress test as compared to those with ischemia (96.3% vs. 93.0%, p = 0.015). The incidence of detected obstructive CAD was lower in patients with suggested ischemia in stress test as compared to patients with inconclusive results (14.1% vs. 21.1%, p = 0.037). There was no difference in the incidence of an obstructive CAD in patients with and without ischemia in stress test (14.1% vs. 15.8%, p = 0.440). CCTA is a reliable, non-invasive option for ruling-out obstructive CAD irrespective of the stress test result.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Coronary computed tomography angiography; Pre-test probability; Stable coronary artery disease; Stress test

Coronary plaque volume and composition assessed by computed tomography angiography in patients with late-onset major depression - Devantier, Torben Albert; Norgaard, Bjarne Linde; Ovrehus, Kristian Altem; Poulsen, Mikael Kjaer; Achenbach, Stephan; Dey, Damini; Videbech, Poul; Marwan, Mohamed (Psychosomatics, 2014)
Depression is a stronger predictor for the onset of or death from clinical coronary artery disease than traditional cardiovascular risk factors. The association between depression and coronary artery disease has previously been investigated in non-contrast enhanced computed tomography studies with conflicting results. The aim of this study was to further elucidate the depression-coronary artery disease relation by use of coronary computed tomography angiography.The calcified and noncalcified coronary plaque volumes were determined by semiautomatic volumetric quantification in 28 patients with late-onset major depression and 27 controls. The calcified plaque proportion, i.e., the calcified plaque volume divided by the total plaque volume, was used to assess the plaque composition.There was no statistically significant difference in the total (p = 0.48), calcified (p = 0.15), and noncalcified (p = 0.62) plaque volume between patients and controls, and the total plaque volume did not predict depression, odds ratio = 1.001 [95% confidence interval: 0.999-1.003; p = 0.23]. However, the calcified plaque proportion was twice as high in patients compared with controls (14% vs. 7%, p = 0.044). Correspondingly, having depression was associated with an increased calcified plaque proportion of 11.3 [95% confidence interval: 2.63-20.1; p = 0.012] percentage points after adjustment for demographics and cardiovascular risk factors.The proportion of the total coronary plaque volume that was calcified was significantly higher in patients with late-onset major depression than in controls, indicating a difference in plaque composition.
EVALuna2:11983

CT analysis of left ventricular function predicts short term survival in patients following transcatheter aortic valve implantation: 1-year outcome data - Ijgua, Mohamed; Arnold, Martin; Eckstein, Markus; Smolka, S.; Bittner, Daniel O.; Ammon, Fabian; Kondruweit, Markus; Moshage, Maximilian; Achenbach, Susanne; Marwan, Mohamed (European Heart Journal, 2022)
CRIS-Team WoS Importer:2023-03-03

CT Attenuation of Pericoronary Adipose Tissue in Normal Versus Atherosclerotic Coronary Segments as Defined by Intravascular Ultrasound - Hell, Michaela; Schuhbaeck, Annika; Gauss, Soeren; Bittner, Daniel; Pflederer, Tobias; Achenbach, Stephan; Marwan, Mohamed (Journal of Computer Assisted Tomography, 2017)
BACKGROUND: The factors influencing genesis of atherosclerosis at specific regions within the coronary arterial system are currently uncertain. Local mechanical factors such as shear stress as well as metabolic factors, including inflammatory mediators released from epicardial fat, have been proposed. We analyzed computed tomographic (CT) attenuation of pericoronary adipose tissue in normal versus atherosclerotic coronary segments as defined by intravascular ultrasound (IVUS). PATIENTS AND METHODS: We evaluated the data sets of 29 patients who were referred for invasive coronary angiography and in whom IVUS of 1 coronary vessel was performed for clinical reasons. Coronary CT angiography was performed within 24 hours from invasive coronary angiography. Computed tomographic angiography was performed using dual-source CT (Siemens Healthcare; Forchheim, Germany). A contrast-enhanced volume data set was acquired (120 kV, 400 mA/rot, collimation 2 × 64 × 0.6 mm, 60-80 mL intravenous contrast agent). Intravascular ultrasound was performed using a 40-MHz IVUS catheter (Atlantis; Boston Scientific Corporation, Natick, Mass) and motorized pullback at 0.5 mm/s. Sixty corresponding coronary artery segments within the coronary artery system were identified in both dual source computed tomography and IVUS using bifurcation points as fiducial markers. In dual source computed tomography data sets, 8 serial parallel cross sections (2-mm slice thickness) were rendered orthogonal to the center line of the coronary artery for each segment. For each cross section, pericoronary adipose tissue within a radius of 3 mm from the coronary artery and enclosed within the epicardium (excluding coronary veins and myocardium) was manually traced and mean CT attenuation values were obtained. Intravascular ultrasound was used to define coronary segments as follows: presence of predominantly fibrous atherosclerotic plaque (hyperechoic), presence of predominantly lipid-rich atherosclerotic plaque (hypoechoic), and absence of atherosclerotic plaque. RESULTS: In IVUS, 20 coronary segments with fibrous plaque, 20 segments with lipid-rich plaque, and 20 coronary segments without plaque were identified. The mean CT attenuation of pericoronary adipose tissue for segments with any coronary atherosclerotic plaque was -34 ± 14 Hounsfield units (HU), as compared with -56 ± 16 HU for segments without plaque (P = 0.005). The density of pericoronary fat in segments with fibrous versus lipid-rich plaque as defined by IVUS was not significantly different (-35 ± 19 HU vs -36 ± 16 HU, P = 0.8). CONCLUSIONS: Mean CT attenuation of pericoronary adipose tissue is significantly lower for normal versus atherosclerotic coronary segments. This supports a hypothesis of different types of pericoronary adipose tissue, the more metabolically active of which might exert local effects on the coronary vessels, thus contributing to atherogenesis.
EVALuna2:33619

CT-based analysis of pericoronary adipose tissue density: Relation to cardiovascular risk factors and epicardial adipose tissue volume - Hell, Michaela M.; Achenbach, Stephan; Schuhbaeck, Annika; Klinghammer, Lutz; May, Matthias; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2016)
Pericoronary adipose tissue (PCAT) can promote atherosclerosis. Metabolically active and inactive PCAT may display different CT densities. However, CT density could be influenced by partial volume effects and image interpolation.To investigate whether PCAT density values in CT displays differences that are larger than those attributable to interpolation and partial volume effects, which would manifest themselves through the relationship between PCAT density and distance from the contrast-enhanced coronary lumen.PCAT density analysis was performed (417 non-atherosclerotic segments, 63 patients) using dual-source CT with a threshold-based measurement method. Changes in PCAT density values depending on distance from the contrast-enhanced coronary lumen and the influence of cardiovascular risk profile were analyzed.Mean PCAT density was -78.1 ± 5.6 HU. PCAT density decreased from proximal to distal segments in the LAD (-78.0 ± 7.3 vs. -82.4 ± 7.7 HU; p < 0.001). PCAT density was higher close to the lumen compared to more peripheral locations (-76.0 ± 6.7 vs. -78.5 ± 5.4 HU; p < 0.001). Decreasing PCAT density was significantly associated with higher epicardial adipose tissue (EAT) volume and body mass index. There was a trend of lower PCAT values with a family history of coronary artery disease.CT-measured attenuation of PCAT is influenced by EAT volume and body mass index. A decrease of PCAT attenuation with increasing distance from the vessel and from proximal to distal segments may suggest variations in CT density of PCAT due to partial volume effects and image interpolation rather than solely due to differences in tissue composition or metabolic activity.
EVALuna2:12033

CT-derived left ventricular global strain: a head-to-head comparison with speckle tracking echocardiography - Ammon, Fabian; Bittner, D.; Hell, M.; Mansour, H.; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (International Journal of Cardiovascular Imaging, 2019)
We assessed CT-derived left ventricular strain in a cohort of patients referred for transcatheter aortic valve implantation (TAVI) and validated it against 2 dimensional speckle tracking echocardiography as the gold standard. 65 consecutive patients with symptomatic aortic valve stenosis referred for CT imaging prior to TAVI were included in this analysis. For all patients, retrospectively ECG-gated multi-phase functional CT data sets acquired with identical reconstruction parameters were available. All data sets were acquired using a third generation dual source system. In all patients, multiphase reconstructions in increments of 10% of the cardiac cycle were rendered (slice thickness 0.75, increment 0.5 mm, medium smooth reconstruction kernel) and transferred to a dedicated workstation (Ziostation2, Ziosoft Inc., Tokyo, Japan). Additional functional reconstructions for dynamic assessment and quantification of strain were processed. Multiplanar reconstructions (MPR) of the left ventricle similar to standard echocardiographic 4, 2 and apical 3 chamber views were rendered in CT. Similar to echocardiographic longitudinal strain, the perimeter of the left ventricle was manually traced within the myocardium and peak maximal shortening as a parameter representing longitudinal strain was calculated for each view and averaged to obtain a marker for global longitudinal strain (CT perimeter-derived strain). Furthermore, for quantification of 3-dimensional strain, endocardial and epicardial borders of myocardium were marked in six short axis views and peak maximum 3- dimensional strain of the myocardium was calculated in standard six basal, six mid and four apical segments. 3-dimensional strain values of the 16 standard segments as well as perimeter-derived strain values in the three standard windows were averaged to obtain global strain. Echocardiography was performed in all patients before CT data acquisition. Digital loops were acquired from three apical views (four-, two-, and three chamber views). For assessment of 2 dimensional global longitudinal strain (GLS), recordings were processed with acoustic-tracking software allowing offline semiautomated speckle-based strain analyses. The mean age of all 65 patients was 81 ± 5 years. The mean echocardiographic ejection fraction and mean echocardiographic GLS were 50 ± 12% and −13.6 ± 4.5%, respectively. The mean CT-derived peak 3-dimensional global strain and mean peak strain derived by perimeter was 43.2 ± 13.5% and −11.2 ± 3.5%, respectively. Both CTderived global 3D-strain and perimeter derived strain showed a significant correlation to GLS derived by echocardiography (r = −0.8, p < 0.0001 for 3D strain and r = 0.71, p < 0.0001 for perimeter-derived strain). Bland-Altman analysis showed a systematic underestimation (i. e. worse strain values) of CT perimeter-derived strain compared to GLS by echocardiography (mean difference −2.4% with 95% limits of agreement between 4% to −9%). ROC Curve analysis assuming a normal GLS when less than −18% showed that a CT-derived peak 3-dimensional global strain cut-off-value of 45% has a sensitivity of 91% and a specificity of 60% for detecting normal left ventricular strain (AUC 0.81, p = 0.001). For CT perimeter-derived strain, a cut-off value of −12%—assuming a normal echocardiographic GLS when less than −18%—achieved a sensitivity of 82% and a specificity of 61% (AUC of 0.82, p = 0.001) for detecting abnormal left ventricular strain. Using dedicated software, assessment of CT-derived left ventricular strain is feasible and comparable to strain derived by echocardiographic 2 dimensional speckle tracking.
CRIS-Team Scopus Importer:2019-05-07
Keywords: Cardiac CT angiography; Echocardiography; Left ventricular global strain; Speckle tracking

CT-derived left ventricular global strain in aortic stenosis patients referred for transcatheter aortic valve implantation: a head-to-head comparison with echocardiography - Ammon, Fabian; Bittner, D.; Hell, M.; Schuhbaeck, A.; Röther, Jens; Feyrer, R.; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

CT-derived left ventricular global strain in aortic stenosis patients referred for transcatheter aortic valve replacement: a comparative study pre and post intervention - Bittner, D.; Hell, M.; Gitsioudis, Gitsios; Röther, Jens; Schuhbaeck, A.; Feyrer, R.; Arnold, M.; Achenbach, Stephan; Marwan, Mohamed (2017)
EVALuna2:36027

CT-derived left ventricular global strain in aortic valve stenosis patients: A comparative analysis pre and post transcatheter aortic valve implantation - Ammon, Fabian; Bittner, D.; Röther, Jens; Mekkhala, N.; Hell, M.; Schuhbaeck, A.; Gitsioudis, Gitsios; Feyrer, R.; Schlundt, Christian; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (Journal of Cardiovascular Computed Tomography, 2018)
INTRODUCTION: We assessed the potential of CT strain to detect changes in myocardial function in patients referred for TAVI pre and post intervention. PATIENTS AND METHODS: 25 consecutive patients with symptomatic aortic valve stenosis in whom TAVI had been performed were included in this analysis. Functional CT data sets acquired before and 3 to 6 months after TAVI were available. Multiphase reconstructions in increments of 10% of the cardiac cycle were rendered and transferred to a dedicated workstation (Ziostation2, Ziosoft Inc., Tokyo, Japan). For quantification of left ventricular strain, multiplanar reconstructions of the left ventricle in standard 4 chamber, 2 chamber as well as apical 3 chamber views were rendered. The perimeter of the left ventricle was traced dynamically through the cardiac cycle. Peak strain was calculated for each patient pre and post intervention. Furthermore, for quantification of 3-dimensional maximum principal strain, 2 volumetric regions of interests (VOI) were placed per each basal, mid and apical segment of the previously mentioned MPRs and peak maximal principal strain was calculated. Maximum principal strain as well as perimeter-derived longitudinal strain values in the three standard windows were averaged to obtain global strain. RESULTS: 25 patients were included in this analysis (mean age 78 ± 9 years, 13 males). Peak global maximum principal strain was significantly higher at follow-up compared to baseline (0.46 ± 0.19 vs. 0.59 ± 0.18, respectively, p = 0.001). Similarly global longitudinal strain derived by perimeter was significantly lower - implying better contraction - compared to baseline (-8.6% ± 2.8% vs. -9.8% ± 2.6%, respectively, p = 0.006). CONCLUSION: Using dedicated software, assessment of CT derived left ventricular strain is feasible. In patients treated with transcatheter aortic valve replacement, CT-derived parameters of global myocardial strain improve onshort-term follow-up.
EVALuna2:35994

CT-FFR in predicting future cardiovascular events - Smolka, S.; Fava, A.; Moshage, Maximilian; Marwan, Mohamed; Desai, M. Y.; Achenbach, Stephan (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

CT predictors of post-procedural aortic regurgitation in patients referred for transcatheter aortic valve implantation: An analysis of 105 patients - Marwan, Mohamed; Achenbach, Stephan; Ensminger, Stefan M.; Pflederer, Tobias; Ropers, Dieter; Ludwig, Josef; Weyand, Michael; Daniel, Werner; Arnold, Martin (International Journal of Cardiovascular Imaging, 2013)
Cardiac computed tomography (CT) allows accurate and detailed analysis of the anatomy of the aortic root and valve, including quantification of calcium. We evaluated the correlation between different CT parameters and the degree of post-procedural aortic regurgitation (AR) after transcatheter aortic valve implantation (TAVI) using the balloon-expandable Edwards Sapien prosthesis. Preintervention contrast-enhanced dual source CT data sets of 105 consecutive patients (48 males, mean age 81 ± 6 years, mean logEuroSCORE 34 ± 13 %) with symptomatic severe aortic valve stenosis referred for TAVI using the Edwards Sapien prosthesis (Edwards lifesciences, Inc., CA, USA) were analysed. The degrees of aortic valve commissural calcification and annular calcification were visually assessed on a scale from 0 to 3. Furthermore, the degree of aortic valve calcification as quantified by the Agatston score, aortic annulus eccentricity, aortic diameter at the level of the sinus of valsalva and at the sinotubular junction were assessed. Early post-procedural AR was assessed using aortography. Significant AR was defined as angiographic AR of at least moderate degree (AR ≥ 2). Visual assessment of the degree of aortic annular calcification as well as the Agatston score of aortic valve calcium correlated weakly, yet significantly with the degree of post-procedural AR (r = 0.31 and 0.24, p = 0.001 and 0.013, respectively). Compared to patients with AR<2, patients with AR ≥ 2 showed more severe calcification of the aortic annulus (mean visual scores 1.9 ± 0.6 vs. 1.5 ± 0.6, p = 0.003) as well as higher aortic valve Agatston scores (1,517 ± 861 vs. 1,062 ± 688, p = 0.005). Visual score for commissural calcification did not differ significantly between both groups (mean scores 2.4 ± 0.5 vs. 2.5 ± 0.5, respectively, p = 0.117). No significant correlation was observed between the degree of AR and commissural calcification, aortic annulus eccentricity index or aortic diameters. The extent of aortic valve annular calcification, but not of commissural calcification, predicts significant post-procedural AR in patients referred for TAVI using the balloon-expandable Edwards Sapiens prosthesis.
CRIS-Team Scopus Importer:2023-03-08
Keywords: AR; CT; TAVI

Current status of cardiac CT for the detection of myocardial ischemia - Schuhbaeck, A.; Marwan, Mohamed; Cury, R. C.; Achenbach, Stephan (Herz, 2013)
Stress and rest myocardial perfusion imaging using computed tomography (CT) can be accurately and safely performed. CT angiography allows for the anatomic visualization of coronary lesions and the components of atherosclerotic plaque, whereas according to currently available data, CT perfusion imaging improves the diagnostic accuracy for detecting ischemic lesions. However, the radiation exposure and contrast load that are involved cannot be neglected. Owing to the limited number of trials that have been published so far, and the fact that they used a wide variety of image acquisition and stress protocols, a standard acquisition protocol for CT perfusion imaging still needs to be found and evaluated in larger multicenter trials. Therefore, CT perfusion imaging, as opposed to other modalities such as magnetic resonance perfusion, SPECT, or positron emission tomography, cannot yet be regarded as clinical routine, but may be considered in patients with contraindications for other imaging modalities. © 2013 Urban & Vogel.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac computed tomography; Myocardial ischemia; Myocardial perfusion imaging; Pharmacologic stress; Significant coronary stenoses

Declining radiation dose of coronary computed tomography angiography: German cardiac CT registry experience 2009-2014 - Schmermund, Axel; Hausleiter, Joerg; Barth, Sebastian; Bruder, Oliver; Kerber, Sebastian; Korosoglou, Grigorius; Leber, Alexander; Moshage, Werner; Schroeder, Stephen; Schneider, Steffen; Senges, Jochen; Achenbach, Stephan; et al. (Clinical Research in Cardiology, 2017)
BACKGROUND: Coronary computed tomography angiography (CTA) is increasingly used as a test to rule out coronary artery disease (CAD) in patients with a low to intermediate pre-test probability of the disease. We used the database of the German CT registry, collected between 2009 and 2014 in a broad patient population, to analyze contemporary radiation dose associated with coronary CTA in clinical practice. PATIENTS AND METHODS: The prospective observational registry included a total of 7061 patients ≥18 years, referred to 12 participating centers for a clinically indicated cardiac CT examination. All centers were cardiology units well experienced in CTA and used multi-slice CT scanners with at least 64 rows. Coronary CTA was performed in a subset of 5001 patients, 59.6 ± 11.8 years, body mass index (BMI) 26.9 ± 4.5 kg/m2, 38% females. Three time periods with approximately equal numbers of patients were created (01/09-03/10, 04/10-03/11, 04/11-07/14). The dose-length product of all examinations and derived effective dose in mSv (conversion factor k = 0.014) as well as the influence of patient characteristics on dose were compared for the three time periods. RESULTS: BMI and proportion of female patients remained stable over time, and mean heart rate decreased from 60.3 ± 9.0 to 58.5 ± 9.3 bpm from the first to the last time period (p < 0.001). Overall, the mean effective dose of coronary CTA was 3.6 mSv (Q1 1.8 mSv, Q3 7.4 mSv). Within the three time periods, it declined from 5.6 (2.7, 8.6) mSv during the first to 4.8 (2.1, 8.2) mSv during the second and 2.5 (1.3, 4.6) mSv during the last time period (p < 0.001). Paralleling the decline in radiation dose over time, the proportion of prospectively ECG-triggered examinations increased (68, 79, 83%; p < 0.001), and the proportion of examinations with retrospective gating and no tube current modulation decreased (5.3, 4.0, 1.6%; p < 0.001). Tube current (mAs) and voltage (kV) both decreased over time. In multivariable analysis, besides earlier time period, further independent predictors of an increased radiation dose were older age, higher heart rate, and higher BMI as well as the technical factors higher mAs, higher kV, and retrospective gating. At three sites, CT scanners with improved technology were installed during the last time period. CONCLUSIONS: In current clinical practice among German cardiology units with specific expertise in cross-sectional cardiovascular imaging, overall radiation dose of coronary CTA was comparably low. Over time, a decline in radiation dose was demonstrated, probably due to a combination of improvements in data acquisition protocols and patient preparation as well as installation of new CT scanners with advanced technology.
EVALuna2:33607

Deep learning-enabled coronary CT angiography for plaque and stenosis quantification and cardiac risk prediction: an international multicentre study - Lin, Andrew; Manral, Nipun; McElhinney, Priscilla; Killekar, Aditya; Matsumoto, Hidenari; Kwiecinski, Jacek; Pieszko, Konrad; Razipour, Aryabod; Grodecki, Kajetan; Park, Caroline; Otaki, Yuka; Doris, Mhairi; et al. (The Lancet Digital Health, 2022)
BACKGROUND: Atherosclerotic plaque quantification from coronary CT angiography (CCTA) enables accurate assessment of coronary artery disease burden and prognosis. We sought to develop and validate a deep learning system for CCTA-derived measures of plaque volume and stenosis severity. METHODS: This international, multicentre study included nine cohorts of patients undergoing CCTA at 11 sites, who were assigned into training and test sets. Data were retrospectively collected on patients with a wide range of clinical presentations of coronary artery disease who underwent CCTA between Nov 18, 2010, and Jan 25, 2019. A novel deep learning convolutional neural network was trained to segment coronary plaque in 921 patients (5045 lesions). The deep learning network was then applied to an independent test set, which included an external validation cohort of 175 patients (1081 lesions) and 50 patients (84 lesions) assessed by intravascular ultrasound within 1 month of CCTA. We evaluated the prognostic value of deep learning-based plaque measurements for fatal or non-fatal myocardial infarction (our primary outcome) in 1611 patients from the prospective SCOT-HEART trial, assessed as dichotomous variables using multivariable Cox regression analysis, with adjustment for the ASSIGN clinical risk score. FINDINGS: In the overall test set, there was excellent or good agreement, respectively, between deep learning and expert reader measurements of total plaque volume (intraclass correlation coefficient [ICC] 0·964) and percent diameter stenosis (ICC 0·879; both p<0·0001). When compared with intravascular ultrasound, there was excellent agreement for deep learning total plaque volume (ICC 0·949) and minimal luminal area (ICC 0·904). The mean per-patient deep learning plaque analysis time was 5·65 s (SD 1·87) versus 25·66 min (6·79) taken by experts. Over a median follow-up of 4·7 years (IQR 4·0-5·7), myocardial infarction occurred in 41 (2·5%) of 1611 patients from the SCOT-HEART trial. A deep learning-based total plaque volume of 238·5 mm3 or higher was associated with an increased risk of myocardial infarction (hazard ratio [HR] 5·36, 95% CI 1·70-16·86; p=0·0042) after adjustment for the presence of deep learning-based obstructive stenosis (HR 2·49, 1·07-5·50; p=0·0089) and the ASSIGN clinical risk score (HR 1·01, 0·99-1·04; p=0·35). INTERPRETATION: Our novel, externally validated deep learning system provides rapid measurements of plaque volume and stenosis severity from CCTA that agree closely with expert readers and intravascular ultrasound, and could have prognostic value for future myocardial infarction. FUNDING: National Heart, Lung, and Blood Institute and the Miriam & Sheldon G Adelson Medical Research Foundation.
CRIS-Team Scopus Importer:2022-04-08

Determination of optimal fluoroscopic angulations for aorto-coronary ostial interventions from coronary computed tomography angiography - Hell, Michaela; Schlundt, Christian; Bittner, Daniel O.; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2020)
Background: An optimal aorto-coronary angiographic projection, characterized by an orthogonal visualization of the proximal coronary artery, is crucial for interventional success. We determined the distribution of optimal C-arm positions and assessed their feasibility by invasive coronary angiography. Methods: Orthogonal aorto-coronary ostial angulations were determined in 310 CT data sets. In 100 patients undergoing subsequent invasive angiography, we assessed if the CT-predicted angulations were achievable by the C-arm system. If the predicted projection was not achievable due to mechanical constraints of the C-arm system, the most close, achievable angulation was determined. Patient characteristics were analyzed regarding the distribution of optimal angulations and its feasibility by the C-arm system. Results: For the left ostium, CT revealed a mean angulation of LAO 23 ​± ​21°/cranial 25 ​± ​23° (90% of patients with a LAO/cranial angulation, 3% LAO/caudal, 4% RAO/cranial, 3% RAO/caudal) and were achievable by the C-arm system in 87% of patients. For the right ostium, the mean CT-predicted orthogonal angulation was LAO 36 ​± ​37°/cranial 36 ​± ​51° (84% LAO/cranial, 2% LAO/caudal, 14% RAO/caudal) and achievable by the C-arm system in 45% of patients. For the left ostium, a higher body weight was associated with a steeper LAO/cranial angulation being less feasible by the C-arm system due to mechanical constraints. Conclusions: Orthogonal aorto-left coronary angulations show a relative narrow distribution predominately in LAO/cranial position whereas a wider range of angulations was found for the right coronary ostium. The feasibility of CT-predicted angulations by the C-arm system is more restricted for the right than the left coronary ostium.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Angulation; Computed tomography angiography; Coronary intervention; Ostial lesion

Diagnostic performance of noninvasive fractional flow reserve derived from coronary computed tomography angiography in suspected coronary artery disease: the NXT trial (Analysis of Coronary Blood Flow Using CT Angiography: Next Steps) - Norgaard, Bjarne L.; Leipsic, Jonathon; Gaur, Sara; Seneviratne, Sujith; Ko, Brian S.; Ito, Hiroshi; Jensen, Jesper M.; Mauri, Laura; De Bruyne, Bernard; Bezerra, Hiram; Osawa, Kazuhiro; Naber, Christoph; et al. (Journal of the American College of Cardiology, 2014)
The goal of this study was to determine the diagnostic performance of noninvasive fractional flow reserve (FFR) derived from standard acquired coronary computed tomography angiography (CTA) datasets (FFR(CT)) for the diagnosis of myocardial ischemia in patients with suspected stable coronary artery disease (CAD).FFR measured during invasive coronary angiography (ICA) is the gold standard for lesion-specific coronary revascularization decisions in patients with stable CAD. The potential for FFR(CT) to noninvasively identify ischemia in patients with suspected CAD has not been sufficiently investigated.This prospective multicenter trial included 254 patients scheduled to undergo clinically indicated ICA for suspected CAD. Coronary CTA was performed before ICA. Evaluation of stenosis (>50% lumen reduction) in coronary CTA was performed by local investigators and in ICA by an independent core laboratory. FFR(CT) was calculated and interpreted in a blinded fashion by an independent core laboratory. Results were compared with invasively measured FFR, with ischemia defined as FFR(CT) or FFR <=0.80.The area under the receiver-operating characteristic curve for FFR(CT) was 0.90 (95% confidence interval [CI]: 0.87 to 0.94) versus 0.81 (95% CI: 0.76 to 0.87) for coronary CTA (p = 0.0008). Per-patient sensitivity and specificity (95% CI) to identify myocardial ischemia were 86% (95% CI: 77% to 92%) and 79% (95% CI: 72% to 84%) for FFR(CT) versus 94% (86 to 97) and 34% (95% CI: 27% to 41%) for coronary CTA, and 64% (95% CI: 53% to 74%) and 83% (95% CI: 77% to 88%) for ICA, respectively. In patients (n = 235) with intermediate stenosis (95% CI: 30% to 70%), the diagnostic accuracy of FFR(CT) remained high.FFR(CT) provides high diagnostic accuracy and discrimination for the diagnosis of hemodynamically significant CAD with invasive FFR as the reference standard. When compared with anatomic testing by using coronary CTA, FFR(CT) led to a marked increase in specificity. (HeartFlowNXT-HeartFlow Analysis of Coronary Blood Flow Using Coronary CT Angiography [HFNXT]; NCT01757678).
EVALuna2:11982

Diagnostic Performance of Transluminal Attenuation Gradient and Noninvasive Fractional Flow Reserve Derived from 320-Detector Row CT Angiography to Diagnose Hemodynamically Significant Coronary Stenosis: An NXT Substudy - Ko, Brian S.; Wong, Dennis T. L.; Norgaard, Bjarne L.; Leong, Darryl P.; Cameron, James D.; Gaur, Sara; Achenbach, Stephan; Kuribayashi, Sachio; Kimura, Takeshi; Meredith, Ian T.; Seneviratne, Sujith K.; Marwan, Mohamed (Radiology, 2016)
PURPOSE: To compare the diagnostic performance of 320-detector row computed tomography (CT) coronary angiography-derived computed fractional flow reserve (FFR; FFRCT), transluminal attenuation gradient (TAG; TAG320), and CT coronary angiography alone to diagnose hemodynamically significant stenosis as determined by invasive FFR. MATERIALS AND METHODS: This substudy of the prospective NXT study (no. NCT01757678) was approved by each participating institution's review board, and informed consent was obtained from all participants. Fifty-one consecutive patients who underwent 320-detector row CT coronary angiographic examination and invasive coronary angiography with FFR measurement were included. Independent core laboratories determined coronary artery disease severity by using CT coronary angiography, TAG320, FFRCT, and FFR. TAG320 is defined as the linear regression coefficient between luminal attenuation and axial distance from the coronary ostium. FFRCT was computed from CT coronary angiography data by using computational fluid dynamics technology. Diagnostic performance was evaluated and compared on a per-vessel basis by the area under the receiver operating characteristic (ROC) curve (AUC). RESULTS: Among 82 vessels, 24 lesions (29%) had ischemia by FFR (FFR ≤ 0.80). FFRCT exhibited a stronger correlation with invasive FFR compared with TAG320 (Spearman ρ, 0.78 vs 0.47, respectively). Overall per-vessel accuracy, sensitivity, specificity, and positive and negative predictive values for TAG320 (<15.37) were 78%, 58%, 86%, 64%, and 83%, respectively; and those of FFRCT were 83%, 92%, 79%, 65%, and 96%, respectively. ROC curve analysis showed a significantly larger AUC for FFRCT (0.93) compared with that for TAG320 (0.72; P = .003) and CT coronary angiography alone (0.68; P = .008). CONCLUSION: FFRCT computed from 320-detector row CT coronary angiography provides better diagnostic performance for the diagnosis of hemodynamically significant coronary stenoses compared with CT coronary angiography and TAG320.
EVALuna2:12105

Differences of inflammatory cytokine profile in patients with vulnerable plaque: A coronary CTA study - Roesner, Caroline; Göller, Markus; Raaz-Schrauder, Dorette; Dey, Damini; Kilian, Tobias; Achenbach, Stephan; Marwan, Mohamed; Bittner, Daniel O. (Atherosclerosis, 2022)
Background and aims: Various pro-and anti-inflammatory biomarkers are involved in the process of atherosclerosis. We analyzed the association of different biomarkers with coronary plaque volume and vulnerable plaque subcomponents. Methods: In 301 patients undergoing coronary CT angiography (CTA), total coronary plaque volume (TPV) and subcomponents including non-calcified plaque volume (NCPV) and vulnerable plaque burden were quantified using semi-automated software. Serum was analyzed for various cytokines. Results: Out of 301 patients, 207 (69%) were male. The mean age was 59 +/- 10 years. Patients were divided using the median of TPV, NCPV and vulnerable plaque burden. In univariable analysis, patients with high TPV, high NCPV and high vulnerable plaque burden showed significant higher serum levels for IFN?, IL-1a,-2,-4,-10 and-17 and significant lower levels for IL-8 and MCP-1 (all p < 0.05). Multivariable analysis showed positive associations between high vulnerable plaque burden, IL-1a (OR 2.60, p = 0.001) and Eotaxin (OR 1.89, p = 0.020), and inverse association to MCP-1 (OR 0.33, p < 0.001), independent of age, gender and CVRF. In exploratory subanalyses, patients with presence of atherosclerosis (n = 247; 82%) showed significantly higher levels of IL-17 in all subgroups with high vulnerable plaque burden, irrespective of overall plaque volume (all p < 0.001). Conclusions: The cytokine profile significantly differs between patients with high and low coronary plaque volume. IL-1a and IL-17 seem to play a major proatherogenic role in vulnerable plaque formation, whereas MCP-1 paradoxically portends protective effects. Longitudinal studies with serial cytokine testing are needed to identify potential targets for therapeutic interventions.
CRIS-Team WoS Importer:2022-06-24
Keywords: Inflammatory biomarkers; Interleukin; Atherosclerosis; Coronary CT-angiography; Plaque volume; Vulnerable plaque

Direct head-to-head comparison of convolutional long short-term memory and transformer networks for artificial Intelligence-based quantification of atherosclerotic plaque and stenosis from coronary CT angiography - Manral, Nipun; Lin, Andrew; Park, Caroline; McElhinney, Priscilla; Killekar, Aditya; Matsumoto, Hidenari; Kwiecinski, Jacek; Pieszko, Konrad; Razipour, Aryabod; Grodecki, Kajetan; Doris, Mhairi; Kwan, Alan C.; et al. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2023)
Background: Coronary computed tomography angiography (CCTA) enables non-invasive assessment of luminal stenosis and coronary atherosclerotic plaque. We aimed to directly compare the performance of 2 novel deep learning networks—convolutional long short-term memory and transformer network—for artificial intelligence-based quantification of plaque volume and stenosis severity from CCTA. Methods: This was an international multicenter study of patients undergoing CCTA at 11 sites. The deep learning (DL) convolutional neural networks were trained to segment coronary plaque in 921 patients (5,045 lesions). The training dataset was further split temporally into training (80%) and internal validation (20%) datasets. The primary DL architecture was a hierarchical convolutional long short- term memory (ConvLSTM) network. This was compared against a TransUNet network, which combines the abilities of Vision Transformer with U-Net, enabling the capture of in-depth localization information while modeling long-range dependencies. Following training and internal validation, the both DL networks were applied to an external validation cohort of 162 patients (1,468 lesions) from the SCOT-HEART trial. Results: In the external validation cohort, agreement between DL and expert reader measurements was stronger when using the ConvLSTM network than with TransUNet, for both per-lesion total plaque volume (ICC 0·953 vs 0.830) and percent diameter stenosis (ICC 0·882 vs 0.735; both p<0.001). The ConvLSTM network showed higher per-cross-section overlap with expert reader segmentations (as measured by the Dice coefficient) compared to TransUnet, for vessel wall (0.947 vs 0.946), lumen (0.93 vs 0.92), and calcified plaque (0.87 vs 0.86; p<0.0001 for all), with similar execution times. Conclusions: In a direct comparison with external validation, the ConvLSTM network yielded higher agreement with expert readers for quantification of total plaque volume and stenosis severity compared to TransUnet, with faster execution times.
CRIS-Team Scopus Importer:2023-06-02
Keywords: artificial intelligence; atherosclerosis; convolutional long short-term memory network; coronary computed tomography angiography; deep learning; transformers

Double kissing - crush technique to treat coronary bifurcation lesions: analysis of success rate, procedural times and device usage - Schacher, Nora; Ferstl, Paul; Weidinger, Franz; Achenbach, Stephan; Tröbs, Monique; Marwan, Mohamed; Gaede, Luise (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Early-onset coronary atherosclerosis in patients with low levels of omega-3 fatty acids - Bittner, D. O.; Göller, Markus; Zopf, Yurdagül; Achenbach, Stephan; Marwan, Mohamed (European Journal of Clinical Nutrition, 2020)
Objectives: Coronary artery calcification (CAC) can reliably predict cardiovascular events. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are thought to inhibit vascular calcification on a cellular level and in animal models, however, the correlation in humans is controversial. Methods: In symptomatic patients, CAC was quantified according to Agatstons’ method using non-contrast coronary CT. We assessed the association of EPA and DHA with early-onset coronary atherosclerosis, defined as presence of CAC above the 75th Agatston-Score (AS) percentile in sex adjusted age categories. Erythrocyte fatty acid composition was analyzed with a standardized methodology. The percentage of EPA and DHA in relation to all fatty acids present in the erythrocyte membrane is regarded the Omega-3 Index®. Results: Among 71 patients, 51 were below and 20 were above the 75th AS-percentile. No differences were seen in age, gender, cardiovascular risk factors, and relevant medication. In univariable analysis, significantly lower values for EPA (0.77%[0.63; 0.97] vs. 0.93%[0.72; 1.21]; p = 0.045), DHA (4.90%[4.12; 5.57] vs. 5.50%[4.58; 6.52]; p = 0.038) and the Omega-3 Index (5.73%[4.75; 6.35] vs. 6.22%[5.46; 7.71]; p = 0.034) were seen in patients above the 75th AS-percentile. All other fatty acids showed no significant differences. In multivariable analysis, the Omega-3 Index showed a significant inverse association with early onset of CAC (OR: 0.533 (95%CI: 0.303–0.938; p = 0.029)), independent of age, gender, statin use, and creatinine level (all p > 0.05). Conclusions: Low levels of EPA and DHA (Omega-3 Index) are associated with early-onset coronary atherosclerosis. This finding needs to be validated in larger cohorts and might help understand the beneficial cardiovascular effects of omega-3 fatty acids.
CRIS-Team Scopus Importer:2020-01-21

Early single center experience with a novel transcatheter anuloplasty system for the treatment of functional tricuspid regurgitation - Landendinger, M.; Smolka, S.; Tröbs, Monique; Anneken, Lars; Gaede, L.; Achenbach, Stephan; Arnold, Martin; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Effect of non-compliant balloon postdilatation on magnesium-based bioresorbable vascular scaffolds - Blachutzik, Florian; Achenbach, Stephan; Tröbs, Monique; Weissner, Melissa; Nef, Holger; Schlundt, Christian; Marwan, Mohamed (Catheterization and Cardiovascular Interventions, 2019)
Background: Optimal implantation results of bioresorbable scaffolds (BRS) are typically assumed to require postdilatation with non-compliant (NC) balloons to achieve full scaffold apposition and minimize event rates. We systematically evaluated the mechanical effect of NC balloon postdilatation on magnesium-based BRS (Magmaris (R), Biotronik AG, Bulach, Switzerland) in vivo.
CRIS-Team WoS Importer:2019-03-08

Effects of high- versus low-intensity lipid-lowering treatment in patients undergoing serial coronary computed tomography angiography: results of the multi-center LOCATE study - Weichsel, Loris; André, Florian; Renker, Matthias; Breitbart, Philipp; Overhoff, Daniel; Beer, Meinrad; Giesen, Alexander; Vattay, Borbála; Buß, Sebastian J.; Marwan, Mohamed; Schlett, Christopher L.; Giannopoulos, Andreas A.; et al. (Clinical Research in Cardiology, 2024)
Aim: To evaluate the effects of lipid-lowering medications of different intensities on total, calcified, and non-calcified plaque volumes in patients undergoing serial cardiac computed tomography angiography (CCTA). Methods: Individuals with chronic coronary syndromes from 11 centers were included in a retrospective registry. Total, calcified, and non-calcified plaque volumes were quantified and the relative difference in plaque volumes between baseline and follow-up CCTA was calculated. The intensity of lipid-lowering treatment was designated as low, moderate, or high, based on current recommendations. Results: Of 216 patients (mean age 63.1 ± 9.7 years), undergoing serial CCTA (median timespan = 824.5 [IQR = 463.0–1323.0] days), 89 (41.2%) received no or low-intensity lipid-lowering medications, and 80 (37.0%) and 47 (21.8%) moderate- and high-intensity lipid-lowering agents, respectively. Progression of total and non-calcified plaque was attenuated in patients on moderate-/high- versus those on no/low-intensity treatment and arrested in patients treated with high-intensity statins or PCSK9 inhibitors (p < 0.001). Halted increase of non-calcified plaque was associated with LDL-cholesterol reduction (p < 0.001), whereas calcified plaque mass and Agatston score increased irrespective of the lipid-lowering treatment (p = NS). The intensity of lipid-lowering therapy robustly predicted attenuation of non-calcified plaque progression as a function of the time duration between the two CCTA scans, and this was independent of age and cardiovascular risk factors (HR = 3.83, 95% CI = 1.81–8.05, p < 0.001). Conclusion: The LOCATE multi-center observational study shows that progression of non-calcified plaques, which have been previously described as precursors of acute coronary syndromes, can be attenuated with moderate-intensity, and arrested with high-intensity lipid-lowering therapy. German clinical trials register: DRKS00031954. Graphical abstract: High-intensity lipid-lowering agents, including potent statins and PCSK9 inhibitors induce intense LDL-cholesterol reduction and arrest of non-calcified plaque. (Figure presented.)
CRIS-Team Scopus Importer:2024-08-09
Keywords: Agatston score; Atherosclerosis; Coronary artery disease; Low/high intensity lipid-lowering treatment; Multi-center; Non-calcified plaque; Serial plaque quantification

Epicardial adipose tissue density and volume are related to subclinical atherosclerosis, inflammation and major adverse cardiac events in asymptomatic subjects - Goeller, Markus; Achenbach, Stephan; Doris, Mhairi K.; Cadet, Sebastien; Commandeur, Frederic; Chen, Xi; Slomka, Piotr J.; Gransar, Heidi; Cao, J. Jane; Wong, Nathan D.; Albrecht, Moritz H.; Rozanski, Alan; et al. (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: We investigated whether epicardial adipose tissue (EAT) volume and density are related to early atherosclerosis, plaque inflammation and major adverse cardiac events (MACE, cardiac death and myocardial infarction) in asymptomatic subjects. METHODS: EAT volume and density were quantified from non-contrast cardiac CT in 456 asymptomatic individuals (age 60.3 ± 8.3; 68% with CCS>0) from the prospective EISNER trial. EAT volume and density were examined in relation to coronary calcium score (CCS), inflammatory biomarkers and MACE. RESULTS: EAT volume was higher and EAT density lower in subjects with coronary calcium compared to subjects without [89 vs 74 cm3, p < 0.001] [-76.9 vs -75.7 HU,p = 0.024]. EAT volume was lowest in individuals with no coronary calcium and was significant higher in subjects with early atherosclerosis (CCS 1-99) [74 vs 87 cm3,p = 0.016] and in subjects with more advanced atherosclerosis (CCS≥100) [89 cm3,p = 0.002]). EAT volume was independently related to serum levels of PAI-1, and MCP-1 and inversely related to adiponectin and HDL-cholesterol (p < 0.05). EAT density was inversely related to PAI-1 and LDL-cholesterol and positively associated to adiponectin, sICAM-1 and HDL-cholesterol (p < 0.05). EAT density was more significantly associated with MACE [(HR 0.8, 95%CI:0.7-0.98), p = 0.029] than EAT volume or CCS. CONCLUSION: EAT volume was higher and density lower in subjects with coronary calcium compared to subjects with CCS = 0, with similar EAT volume in CCS<100 and CCS≥100. Lower EAT density and increased EAT volume were associated with coronary calcification, serum levels of plaque inflammatory markers and MACE, suggesting that dysfunctional EAT may be linked to early plaque formation and inflammation.
EVALuna2:33591

Epicardial adipose tissue volume but not density is an independent predictor for myocardial ischemia - Hell, Michaela M.; Ding, Xiaowei; Rubeaux, Mathieu; Slomka, Piotr; Gransar, Heidi; Terzopoulos, Demetri; Hayes, Sean; Achenbach, Stephan; Berman, Daniel S.; Dey, Damini; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2016)
BACKGROUND: Epicardial adipose tissue (EAT) volume is associated with plaque formation and cardiovascular event risk, its density may reflect tissue composition and metabolic activity. OBJECTIVES: Global and regional associations between EAT volume and density, ischemia and coronary calcium were investigated using a novel automatic quantitative measurement software. METHODS: 71 patients with an intermediate pre-test probability for coronary artery disease and inducible ischemia by SPECT were matched to two same-gender controls (total of 213 patients, 90% male, age 60 ± 10 years). Non-contrast CT for assessment of EAT volume, density (in Hounsfield Unit [HU]) and coronary calcium score (CCS) was performed. RESULTS: Global EAT volume was significantly increased in ischemic patients compared to controls (96 ± 49 vs. 82 ± 36 cm(3), p = 0.04), density showed no significant difference (-75.6 ± 4.3 vs. -75.1 ± 4.1HU, p = 0.63). EAT volume and density differed significantly between coronary territories (LAD: 37 ± 18 cm(3), -77.8 ± 4.5HU; LCx: 16 ± 9 cm(3), -73.9 ± 4.1HU; RCA: 36 ± 17 cm(3), -71.7 ± 4.8HU, p < 0.001). For regional ischemia, only LCx territory showed a significantly higher EAT volume (18 ± 8 vs. 16 ± 9 cm(3), p = 0.048). Multivariable logistic regression revealed a significant association with ischemia for EAT volume (OR 2.09 (1.0; 4.3), p = 0.049) and CCS (OR 1.43 (1.1; 1.9), p = 0.006). EAT volume significantly improved discrimination of ischemia over CCS (Integrated Discrimination Improvement: 3.5%, 95%CI: 1.1-6.1%, p = 0.004). Hypertension was the only risk factor significantly influencing EAT volume and density (98 ± 48 vs. 78 ± 31 cm(3), p = 0.002, -76.0 ± 4.1 vs. -74.5 ± 4.1 HU, p = 0.01). CONCLUSIONS: EAT volume is associated with myocardial ischemia and improves the discriminative power for independent ischemia prediction over CCS. In hypertensive patients, EAT is characterized by lower density and higher volumes.
EVALuna2:12102

Epicardial fat and coronary artery calcification in patients on long-term hemodialysis - Gauss, Soeren; Klinghammer, Lutz; Jahn, Daniela; Schuhbaeck, Annika; Achenbach, Stephan; Marwan, Mohamed (Journal of Computer Assisted Tomography, 2014)
Introduction: Recent studies have shown a significant correlation between increased epicardial fat volume (EFV) andmortality, coronary artery disease events, andmeasures of coronary atherosclerotic burden, for example, coronary calcium. Patients with chronic kidney disease on hemodialysis have an increased prevalence of coronary atherosclerosis and coronary calcium. The mechanisms underlying both may differ from patients with normal kidney function. Only limited data are available on the relationship between epicardial fat and coronary calcium in these patients.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac CT; Coronary artery calcification; Dialysis; Epicardial fat

Epicardial fat, cardiovascular risk factors and calcifications in patients with chronic kidney disease - Saritas, Turgay; Reinartz, Sebastian Daniel; Nadal, Jennifer; Schmoee, Jonas; Schmid, Matthias; Achenbach, Stephan; Stoerk, Stefan; Wanner, Christoph; Floege, Jurgen; Schneider, Markus; Schlieper, Georg; Marwan, Mohamed; et al. (Clinical Kidney Journal, 2020)
Background. Epicardial adipose tissue (EAT) exerts cardiopathogenic effects, but the independent association between EAT and cardiovascular (CV) calcification in patients with chronic kidney disease (CKD) remains controversial. We therefore assessed the association between EAT, CV risk factors and CV calcifications.
CRIS-Team WoS Importer:2020-10-30

Fractional flow reserve derived from coronary computed tomography angiography: diagnostic performance in hypertensive and diabetic patients - Eftekhari, Ashkan; Min, James; Achenbach, Stephan; Budoff, Matthew; Leipsic, Jonathon; Gaur, Sara; Jensen, Jesper Moller; Ko, Brian S.; Christiansen, Evald Hoj; Kaltoft, Anne; Botker, Hans Erik; Jensen, Jens Flensted; et al. (European Heart Journal - Cardiovascular Imaging, 2017)
Aims: Fractional flow reserve (FFR) derived from coronary computed tomography (FFRCT) has high diagnostic performance in stable coronary artery disease (CAD). The diagnostic performance of FFRCT in patients with hypertension (HTN) and diabetes (DM), who are at risk of microvascular impairment, is not known. Methods and results: We analysed the diagnostic performance of FFRCT, in patients (vessels) with DM (n = 16), HTN (n = 186), DM + HTN (n = 58) vs. controls (n = 107) with or with suspected CAD. Patients (vessels) were further divided according to left ventricular mass index (LVMI) tertiles. Reference standard was invasively measured FFR ≤0.80. Per-patient diagnostic accuracy (95% CI) in control patients was 71.7% (61.6-81.8) vs. 79.3 (74.0-85.0) (P = 0.12), 75.0% (47.6-92.7) (P = 0.52), and 75.9% (62.8-86.1) (P = 0.39) in patients with HTN, DM, and HTM + DM, respectively. There was no difference in discrimination of ischaemia by FFRCT between groups. On a per-vessel level, there was no significant difference in diagnostic performance or discrimination of ischaemia by FFRCT between groups. There was a decline in both per-patient and -vessel diagnostic specificity of FFRCT in the upper LVMI tertile when compared with lower tertiles; however, discrimination of ischaemia by FFRCT was unaltered across LVMI tertiles. Conclusion: The diagnostic performance of FFRCT is independent of the presence of HTN and DM. FFRCT is a robust method in a broad stable CAD population, including patients at high risk for microvascular disease.
EVALuna2:33598

Fully automated CT quantification of Epicardial adipose tissue by deep learning: A multicenter study - Commandeur, Frederic; Göller, Markus; Razipour, Aryabod; Cadet, Sebastien; Hell, Michaela; Kwiecinski, Jacek; Chen, Xi; Chang, Hyuk-Jae; Marwan, Mohamed; Achenbach, Stephan; Berman, Daniel S.; Slomka, Piotr J.; et al. (Radiology: Artificial Intelligence, 2019)
Purpose: To evaluate the performance of deep learning for robust and fully automated quantification of epicardial adipose tissue (EAT) from multicenter cardiac CT data. Materials and Methods: In this multicenter study, a convolutional neural network approach was trained to quantify EAT on non-contrast material-enhanced calcium-scoring CT scans from multiple cohorts, scanners, and protocols (n = 850). Deep learning performance was compared with the performance of three expert readers and with interobserver variability in a subset of 141 scans. The deep learning algorithm was incorporated into research software. Automated EAT progression was compared with expert measurements for 70 patients with baseline and follow-up scans. Results: Automated quantification was performed in a mean (6 standard deviation) time of 1.57 seconds 6 0.49, compared with 15 minutes for experts. Deep learning provided high agreement with expert manual quantification for all scans (R = 0.974; P, 001), with no significant bias (0.53 cm3; P =. 13). Manual EAT volumes measured by two experienced readers were highly correlated (R = 0.984; P, 001) but with a bias of 4.35 cm3 (P, 001). Deep learning quantifications were highly correlated with the measurements of both experts (R = 0.973 and R = 0.979; P, 001), with significant bias for reader 1 (5.11 cm3; P, 001) but not for reader 2 (0.88 cm3; P =. 26). EAT progression by deep learning correlated strongly with manual EAT progression (R = 0.905; P, 001) in 70 patients, with no significant bias (0.64 cm3; P =. 43), and was related to an increased noncalcified plaque burden quantified from coronary CT angiography (5.7% vs 1.8%; P =. 026). Conclusion: Deep learning allows rapid, robust, and fully automated quantification of EAT from calcium scoring CT. It performs as well as an expert reader and can be implemented for routine cardiovascular risk assessment.
CRIS-Team Scopus Importer:2023-03-08

German cardiac CT registry: indications, procedural data and clinical consequences in 7061 patients undergoing cardiac computed tomography - Achenbach, Stephan; Korosoglou, Grigorios; Schmermund, Axel; Schneider, Steffen; Bruder, Oliver; Hausleiter, Joerg; Schroeder, Stephen; Barth, Sebastian; Kerber, Sebastian; Leber, Alexander; Moshage, Werner; Senges, Jochen; et al. (International Journal of Cardiovascular Imaging, 2018)
Cardiac computed tomography permits quantification of coronary calcification as well as detection of coronary artery stenoses after contrast enhancement. Moreover, cardiac CT offers high-resolution morphologic and functional imaging of cardiac structures which is valuable for various structural heart disease interventions and electrophysiology procedures. So far, only limited data exist regarding the spectrum of indications, image acquisition parameters as well as results and clinical consequences of cardiac CT examinations using state-of-the-art CT systems in experienced centers. Twelve cardiology centers with profound expertise in cardiovascular imaging participated in the German Cardiac CT Registry. Criteria for participation included adequate experience in cardiac CT as well of the availability of a 64-slice or newer CT system. Between 2009 and 2014, 7061 patients were prospectively enrolled. For all cardiac CT examinations, patient parameters, procedural data, indication and clinical consequences of the examination were documented. Mean patient age was 61 ± 12 years, 63% were males. The majority (63%) of all cardiac CT examinations were performed in an outpatient setting, 37% were performed during an inpatient stay. 91% were elective and 9% were scheduled in an acute setting. In most examinations (48%), reporting was performed by cardiologists, in 4% by radiologists and in 47% of the cases as a consensus reading. Cardiac CT was limited to native acquisitions for assessment of coronary artery calcification in 9% of patients, only contrast-enhanced coronary CT angiography was performed in 16.6% and combined native and contrast-enhanced coronary CT angiography was performed in 57.7% of patients. Non-coronary cardiac CT examinations constituted 16.6% of all cases. Coronary artery calcification assessment was performed using prospectively ECG-triggered acquisition in 76.9% of all cases. The median dose length product (DLP) was 42 mGy cm (estimated effective radiation dose of 0.6 mSv). Coronary CT angiography was performed using prospectively ECG-triggered acquisition in 77.3% of all cases. Tube voltage was 120 kV in 67.8% of patients and 100 kV in 30.7% of patients, with a resultant median DLP of 256 mGy cm (estimated effective dose of 3.6 mSv). Clinical consequences of cardiac CT were as follows: in 46.8% of the cases, invasive coronary angiography could be avoided; ischemia testing was recommended in 4.7% of the cases, invasive coronary angiography was recommended in 16.4% of the cases and change in medication in 21.6% of the examinations. Cardiac CT is performed in the majority of patients for non-invasive evaluation of the coronary arteries. CT frequently resulted in medication change, and otherwise planned downstream testing including invasive angiography could be avoided in a high percentage of patients. Radiation exposure in experienced centers is relatively low.
EVALuna2:35998

High-degree atrioventricular block after valve-in-valve transcatheter aortic valve implantation: incidence and predictors - Jung, Susanne; Marwan, Mohamed; Kondruweit, Markus; Achenbach, Stephan; Arnold, Martin (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

High level of EPA is associated with lower perivascular coronary attenuation as measured by coronary CTA - Bittner, D. O.; Göller, Markus; Zopf, Yurdagül; Achenbach, Stephan; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

High levels of eicosapentaenoic acid are associated with lower pericoronary adipose tissue attenuation as measured by coronary CTA - Bittner, Daniel O.; Göller, Markus; Dey, Damini; Zopf, Yurdagül; Achenbach, Stephan; Marwan, Mohamed (Atherosclerosis, 2020)
Background and aims: Higher pericoronary adipose tissue (PCAT) attenuation, a novel marker of inflammation in coronary CT angiography (CTA), has been shown to indicate increased cardiac mortality. Supplementation of eicosapentaenoic acid (EPA) has been shown to decrease cardiovascular death. Whether blood levels of n-3 fatty acids are associated with differences in PCAT attenuation is unknown. Methods: This is a cross-sectional analysis including 64 symptomatic patients who underwent coronary CTA. PCAT attenuation was measured in Hounsfield Units (HU) around the proximal 40 mm of the right coronary artery using semi-automated software. Erythrocyte membrane fatty acid composition was analyzed using gas chromatography. Individual fatty acids were expressed as a percentage of total identified fatty acids. Results: The patient cohort was divided into two groups using the median PCAT attenuation of −78.1 HU (each n = 32). No differences were seen in age, sex, BMI or traditional cardiovascular risk factors (CVRF) between groups (all p > 0.05). In univariable analysis, significantly higher values of EPA (1.00% [0.78; 1.26] vs. 0.78% [0.63; 0.99]; p = 0.02) were seen in patients with lower PCAT attenuation. All other fatty acids showed no differences (all p > 0.05). Moreover, a significant negative correlation was seen between PCAT attenuation and EPA (CC: 0.38; p = 0.002). In multivariable analysis, an inverse association of EPA with PCAT attenuation existed (ß = −0.31, p = 0.017), independent of age, gender, BMI and number of CVRF (all p > 0.1). Conclusions: High levels of EPA are associated with lower PCAT attenuation on coronary CTA. This may indicate a different composition of pericoronary adipose tissue, potentially caused by a lower degree of coronary inflammation.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Coronary CT-Angiography; Eicosapentaenoic acid; Omega-3 fatty acids; Perivascular coronary inflammation

Imaging of the Pericoronary Adipose Tissue (PCAT) Using Cardiac Computed Tomography: Modern Clinical Implications - Göller, Markus; Achenbach, Stephan; Duncker, Hendrik; Dey, Damini; Marwan, Mohamed (Journal of Thoracic Imaging, 2021)
Modern coronary computed tomography angiography (CTA) is the gold standard to visualize the epicardial adipose tissue (EAT) and pericoronary adipose tissue (PCAT). The EAT is a metabolic active fat depot enclosed by the visceral pericardium and surrounds the coronary arteries. In disease states with increased EAT volume and dysfunctional adipocytes, EAT secretes an increased amount of adipocytokines and the resulting imbalance of proinflammatory and anti-inflammatory mediators potentially causes atherogenic effects on the coronary vessel wall in a paracrine way ("outside-to-inside" signaling). These EAT-induced atherogenic effects are reported to increase the risk for the development of coronary artery disease, myocardial ischemia, high-risk plaque features, and future major adverse cardiac events. Coronary inflammation plays a key role in the development and progression of coronary artery disease; however, its noninvasive detection remains challenging. In future, this clinical dilemma might be changed by the CTA-derived analysis of the PCAT. On the basis of the concept of an "inside-to-outside" signaling between the inflamed coronary vessel wall and the surrounding PCAT recent evidence demonstrates that PCAT computed tomography attenuation especially around the right coronary artery derived from routine CTA is a promising imaging biomarker and "sensor" to noninvasively detect coronary inflammation. This review summarizes the biological and technical principles of CTA-derived PCAT analysis and highlights its clinical implications to improve modern cardiovascular prevention strategies.
CRIS-Team Scopus Importer:2021-05-21
Keywords: atherosclerosis; computed tomography attenuation; computed tomography imaging; inflammation; pericoronary adipose tissue

Impact of COVID-19 lockdown on the procedural and intra-hospital outcome of STEMI patients - Gaede, Luise; Rittger, H.; Gerrens, H.; Achajew, A.; Schacher, Nora; Ferstl, Paul; Tröbs, Monique; Arnold, Martin; Marwan, Mohamed; Achenbach, Stephan (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

IMPROVED CARDIAC RISK STRATIFICATION IN INDIVIDUALS WITH HIGH RISK PLAQUE FEATURES USING THE PERIVASCULAR FAT ATTENUATION INDEX ON CCTA - Kotanidis, Christos P.; Oikonomou, Evangelos K.; Kluener, Laura; Thomas, Katharine E.; Alashi, Alaa; Antonopoulos, Alexios S.; Shirodaria, Cheerag; Neubauer, Stefan; Channon, Keith M.; Achenbach, Stephan; Desai, Milind Y.; Antoniades, Charalambos; et al. (HEART, 2020)
CRIS-Team WoS Importer:2021-01-29

Independent predictors of major cardiovascular events as quantitatively assessed by coronary CT-angiography: a long-term follow-up analysis - Bittner, Daniel O.; Roesner, C.; Kilian, Tobias; Göller, Markus; Dey, D.; Raaz-Schrauder, Dorette; Achenbach, Stephan; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Indications, procedural parameters, complications and consequences of fractional flow reserve measurements in a multicenter cohort - Tröbs, Monique; Gaede, L.; Feyrer, J.; Nazli, B.; Moellmann, H.; Giesler, T.; Rittger, H.; Pauschinger, M.; Rudolph, T.; Moshage, W.; Brueck, M.; Achenbach, Stephan; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Influence of Cardiovascular Risk Factors on the Prevalence of Coronary Atherosclerosis in Patients with Angiographically Normal Coronary Arteries - Bittner, Daniel O.; Klinghammer, Lutz; Schmid, Jasmin; Layritz, Christian; Hoffmann, Udo; Achenbach, Stephan; Pflederer, Tobias; Marwan, Mohamed (Academic Radiology, 2017)
RATIONALE AND OBJECTIVES: Cardiovascular (CV) disease is predominately influenced by CV risk factors and coronary computed tomography angiography (CTA) is capable of detecting early-stage coronary artery disease. We sought to determine the influence of CV risk factors on the prevalence of nonobstructive atherosclerosis in patients with normal-appearing coronary arteries in invasive coronary angiography (ICA). MATERIALS AND METHODS: In this retrospective analysis, we included 60 consecutive symptomatic patients, having undergone ICA and coronary CTA. Coronary dual source CTA was performed using electrocardiogram-triggered retrospective gated image acquisition at 40%-70% of RR interval (tube voltage 100-120 kV, tube current time product 320-440 mAs, 60 mL contrast, and flow rate 6 mL/s). RESULTS: Out of 60 patients (32 men, mean age 61 ± 11 years) with a normal coronary artery appearance in ICA, 45 (75%) patients showed atherosclerotic plaque in CTA. Plaque was present in 14 of 60 (23%) left main, 41 of 60 (68%) left anterior descending, 21 of 60 (35%) circumflex coronary arteries, and 24 of 60 (40%) right coronary arteries. More than 15% of all coronary artery segments showed detectable plaques. Interobserver agreement ranged from good to very good on a per-patient, per-vessel, and per-segment level. Patients with presence of plaque were significantly older (P = 0.005) and showed higher incidence of arterial hypertension (P = 0.019) as compared to individuals without coronary plaque in dual source computed tomography. CONCLUSIONS: The prevalence of coronary atherosclerosis by CTA is substantial in symptomatic patients with normal invasive coronary angiogram. Hypertension and older age significantly influence the prevalence of atherosclerotic plaque and highlight the importance of risk-modifying therapy.
EVALuna:33640

Influence of gender on coronary atherosclerosis and inflammatory biomarker profile: a CT angiographic study - Bittner, Daniel O.; Rösner, Caroline; Göller, Markus; Raaz-Schrauder, Dorette; Dey, D.; Kilian, Tobias; Achenbach, Susanne; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Influence of image reconstruction parameters on diagnostic performance of on-site CT-derived FFR: Comparison with invasively measured FFR - Ammon, Fabian; Röther, Jens; Hell, M.; Schuhbaeck, A.; Achenbach, Stephan; Schlundt, Christian; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Influence of irregular heart rhythm on radiation exposure, image quality and diagnostic impact of cardiac computed tomography angiography in 4,339 patients. Data from the German Cardiac Computed Tomography Registry - Korosoglou, Grigorios; Giusca, Sorin; Schmermund, Axel; Schneider, Steffen; Bruder, Oliver; Hausleiter, Joerg; Schroeder, Stephen; Leber, Alexander; Limbourg, Tobias; Gitsioudis, Gitsios; Rixe, Johannes; Zahn, Ralf; et al. (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: Coronary computed tomography angiography (coronary CTA) provides non-invasive evaluation of the coronary arteries with high precision for the detection of significant coronary artery disease (CAD). AIM: To investigate whether irregular heart rhythm including atrial fibrillation and premature beats during data acquisition influences (i) radiation and contrast media exposure, (ii) number of non-evaluable coronary segments and (iii) diagnostic impact of coronary CTA. METHODS: Twelve tertiary care centers with ≥64 slice CT scanners and ≥5 years of experience with cardiovascular imaging participated in this registry. Between 2009 and 2014, 4339 examinations were analysed in patients who underwent clinically indicated coronary CTA for suspected CAD. Clinical and epidemiologic data were gathered from all patients. In addition, clinical presentation, heart rate and rhythm during the scan, Agatston score, radiation and contrast media exposure and the diagnostic impact of coronary CTA were systematically analysed. RESULTS: Of 4339 patients in total, 260 (6.0%) had irregular heart rhythm, whereas the remaining 4079 (94.0%) had stable sinus rhythm. Patients with irregular heart rhythm were older (63.2 ± 12.5yrs versus 58.6 ± 11.4yrs. p < 0.001), exhibited a higher rate of pathologic stress tests before CTA (37.1% versus 26.1%, p < 0.01) and higher heart rates during CTA compared to those with sinus rhythm (62.5 ± 11.6bpm versus 58.9 ± 8.5bpm, p < 0.001). Both contrast media exposure and radiation exposure were significantly higher in patients with irregular heart rhythm (90 mL (95%CI = 80-110 mL) versus 80 mL (95%CI = 70-90 mL) and 6.2 mSv (95%CI = 2.5-11.7) versus 3.3 mSv (95%CI = 1.7-6.9), p < 0.001 for both). Coronary CTA excluded significant CAD less frequently in patients with irregular heart rhythm (32.9% versus 44.8%, p < 0.001). This was attributed to the higher rate of examinations with at least one non-diagnostic coronary segment in patients with irregular heart rhythm (10.8% versus 4.6%, p < 0.001). Subsequent invasive angiography could be avoided in 47.2% of patients with irregular heart rhythm compared to 52.9% of patients with sinus rhythm (p = NS), whereas downstream stress testing was recommended in 3.2% of patients with irregular heart rhythm versus 4.0% of patients with sinus rhythm (p = NS). CONCLUSION: A significant number of patients scheduled for coronary CTA have irregular heart rhythm in a real-world clinical setting. In such patients, heart rate during coronary CTA is higher, possibly resulting in (i) higher radiation and contrast agent exposure and (ii) more frequent coronary CTA examinations with at least one non-diagnostic coronary artery segment. However, this does not seem to lead to increased downstream stress testing or subsequent invasive procedures.
EVALuna2:33590

Influence of irregular heart rhythm on radiation exposure, image quality and diagnostic impact of cardiac computed tomography angiography in 4,767 patients - Korosoglou, G.; Schmermund, A.; Schneider, S.; Giusca, S.; Gitsioudis, Gitsios; Bruders, O.; Hausleiter, J.; Schroeder, S.; Leber, A.; Rixe, J.; Katus, H. A.; Achenbach, Stephan; et al. (2017)
EVALuna2:36026

Influence of lesion location on the accuracy of CT derived FFR: head-to-head comparison with invasive FFR - Moshage, Maximilian; Smolka, S.; Achenbach, Stephan; Ammon, Fabian; Ferstl, Paul; Göller, Markus; Bittner, Daniel O.; Uehlein, Sabrina; Bal, Zeynep; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Influence of reconstruction kernels on the accuracy of CT-derived fractional flow reserve - Ammon, Fabian; Moshage, Maximilian; Smolka, Silvia; Göller, Markus; Bittner, Daniel O.; Achenbach, Stephan; Marwan, Mohamed (European Radiology, 2021)
Objectives: We evaluated the influence of image reconstruction kernels on the diagnostic accuracy of CT-derived fractional flow reserve (FFRCT) compared to invasive FFR in patients with coronary artery disease. Methods: Sixty-nine patients, in whom coronary CT angiography was performed and who were further referred for invasive coronary angiography with FFR measurement via pressure wire, were retrospectively included. CT data sets were acquired using a third-generation dual-source CT system and rendered with medium smooth (Bv40) and sharp (Bv49) reconstruction kernels. FFRCT was calculated on-site using prototype software. Coronary stenoses with invasive FFR ≤ 0.80 were classified as significant. Agreement between FFRCT and invasive FFR was determined for both reconstruction kernels. Results: One hundred analyzed vessels in 69 patients were included. Twenty-five vessels were significantly stenosed according to invasive FFR. Using a sharp reconstruction kernel for FFRCT resulted in a significantly higher correlation with invasive FFR (r = 0.74, p < 0.01 vs. r = 0.58, p < 0.01; p = 0.04) and a higher AUC in ROC curve analysis to correctly identify/exclude significant stenosis (AUC = 0.92 vs. AUC = 0.82 for sharp vs. medium smooth kernel, respectively, p = 0.02). A FFRCT value of ≤ 0.8 using a sharp reconstruction kernel showed a sensitivity of 88% and a specificity of 92% for detecting ischemia-causing lesions, resulting in a diagnostic accuracy of 91%. The medium smooth reconstruction kernel performed worse (sensitivity 60%, specificity 89%, accuracy 82%). Conclusion: Compared to invasively measured FFR, FFRCT using a sharp image reconstruction kernel shows higher diagnostic accuracy for detecting lesions causing ischemia, potentially altering decision-making in a clinical setting. Key Points: • Image reconstruction parameters influence the diagnostic accuracy of simulated fractional flow reserve derived from coronary computed tomography angiography. • Using a sharp kernel image reconstruction algorithm delivers higher diagnostic accuracy compared to medium smooth kernel image reconstruction (gold standard invasive fractional flow reserve).
CRIS-Team Scopus Importer:2021-11-12
Keywords: Computed tomography angiography; Coronary artery disease; Fractional flow reserve; myocardial; Image processing; computer-assisted

Influence of sex on results and consequences of coronary fractional flow reserve in clinical practice: results of a prospective large-scale multicenter registry - Tröbs, Monique; Marwan, Mohamed; Gaede, Luise; Moellmann, H.; Giesler, T.; Rittger, H.; Rudolph, T.; Pauschinger, M.; Moshage, W.; Brueck, M.; Achenbach, Susanne (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Influence of the coronary calcium score on the ability to rule out coronary artery stenoses by coronary CT angiography in patients with suspected coronary artery disease - Schuhbaeck, Annika; Schmid, Jasmin; Zimmer, Thomas; Muschiol, Gerd; Hell, Michaela M.; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2016)
BACKGROUND: Recent guidelines for the workup of patients with chest pain and suspected coronary artery disease include coronary computed tomography angiography (CTA). However, its diagnostic value may be limited in patients with severe coronary calcification. OBJECTIVE: We investigated the relationship between the extent of coronary calcium and the ability of coronary CTA to rule out significant stenoses in a series of consecutive patients with suspected coronary artery disease. METHODS: 2614 consecutive patients with suspected coronary artery disease in whom coronary calcium scoring and coronary CTA had been performed by Dual Source CT were analyzed. The ability of coronary CTA to rule out coronary artery stenoses (fully evaluable coronary arteries and absence of any luminal stenosis >75%) was analyzed relative to the coronary calcium score. RESULTS: The median coronary calcium score was 12, with calcium present in 60.5% of all patients. Coronary CTA ruled out stenoses in 82% of patients, while in 18% of patients at least one stenosis was found or could not be excluded. The threshold above which coronary CTA permitted to rule out stenoses in less than 50% of patients was an "Agatston Score" of 287. This threshold was significantly lower for male patients (213 vs. 330), for patients with a heart rate >65 beats/min (157 vs. 317) and for patients with a body mass index ≥25 kg/m(2) (208 vs. 392). The evaluability of coronary arteries decreased with increasing amounts of calcium and differed significantly between heart rates ≤65 beats/min and >65 beats/min (p < 0.0001). CONCLUSION: In the largest patient series evaluated so far, we identified an "Agatston Score" of 287 to represent a threshold above which coronary CTA permits to rule out coronary artery stenoses in less than 50% of cases.
EVALuna2:33681

Initial Multicenter Experience With a Novel Self-Expanding TAVR System in Patients With Aortic Valve Stenosis - Tamm, Alexander R.; Wienemann, Hendrik; Treede, Hendrik; Geyer, Martin; Arnold, Martin; Marwan, Mohamed; Theiss, Hans; Braun, Daniel; Bleiziffer, Sabine; Goncharov, Arseniy; Kuhn, Elmar; von Bardeleben, Ralph Stephan; et al. (Jacc-Cardiovascular Interventions, 2025)
Background: As transcatheter aortic valve replacement is performed increasingly in younger, low-risk patients, the need for commissural alignment and coronary access has increased. Design elements of the JenaValve Trilogy (JVT) transcatheter heart valve (THV) ensure both. Objectives: This study sought to evaluate the outcome of patients with aortic stenosis (AS) treated with this novel transfemoral, self-expanding THV. Methods: We included 43 consecutive patients with severe AS treated with the JVT system at 5 German sites. The primary endpoint of the study was technical success of the procedure. Procedural outcomes, hemodynamic valve performance, and clinical outcomes at 30 days were evaluated according to the Valve Academic Research Consortium-3 criteria. Results: The median age was 81 years (Q1-Q3: 77.0-83.9 years) with a median Society of Thoracic Surgeons Risk Score of 3.1% (Q1-Q3: 2.1%-5.9%). Technical success was achieved in 98% (n = 42 of 43). One patient was converted to open surgery. The median aortic gradient was 5.0 mm Hg (Q1-Q3: 4.0-7.0 mm Hg), and no patient had moderate or greater paravalvular regurgitation (88% [n = 37 of 42] with none or trace paravalvular regurgitation). At 30 days, major vascular complications and stroke each occurred in 1 (2.3%) patient, 2 (4.7%) patients had died, and permanent pacemaker implantation was needed in 4.9% (n = 2 of 41). Overall, early safety at 30 days was achieved in 82% (n = 27 of 33) of patients. Conclusions: Treatment of AS patients with this novel transfemoral THV system is safe and effective. The JVT offers an excellent alternative to established transcatheter aortic valve replacement prostheses for patients with AS.
CRIS-Team Scopus Importer:2025-01-31
Keywords: aortic stenosis; commissural alignment; paravalvular regurgitation; permanent pacemaker implantation; TAVR; trilogy

Is PCAT CT Attenuation the ‘Game Changer’ in the Prediction of Death and Myocardial Infarction? - Göller, Markus; Marwan, Mohamed (Journal of the American College of Cardiology : Cardiovascular imaging, 2021)
CRIS-Team Scopus Importer:2021-07-30
Keywords: coronary CT angiography; CT attenuation; myocardial infarction; pericoronary adipose tissue

Leaflet thrombosis following transcatheter aortic valve implantation - Mekkhala, N.; Göller, Markus; Röther, Jens; Bittner, D.; Schuhbaeck, A.; Hell, M.; Muschiol, G.; Kolwelter, Julie; Feyrer, R.; Schlundt, Christian; Achenbach, Stephan; Arnold, M.; et al. (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: Transcatheter aortic valve implantation (TAVI) is increasingly being offered to high-risk patients with symptomatic aortic valve stenosis. Recent reports have suggested a high incidence of subclinical leaflet thrombosis following bioprosthestic aortic valve replacement. We report the frequency and clinical presentation of leaflet thrombosis identified by cardiac CT in patients referred for follow-up contrast enhanced CT angiography following TAVI. METHODS: 91 consecutive patients referred for follow-up contrast-enhanced CT angiography following TAVI were screened for inclusion in this analysis. Out of these, 13 patients were excluded. All CT examinations were performed using a 2nd or a 3rd generation dual-source system (Somatom Definition Flash/Force, Forchheim, Germany). In all patients, retrospectively ECG-gated spiral acquisition with tube modulation was performed to allow for assessment of leaflet motion. All prostheses were analyzed for presence of leaflet thrombosis defined as hypo-attenuated leaflet thickening with or without leaflet restriction. Post-procedural antithrombotic regimen as well as symptom status was documented in all patients. RESULTS: 78 consecutive patients (35 males, 81 ± 4 years) were analyzed. TAVI had been performed in all patients (76 transfemoral access, 2 transapical access) with either balloon-expandable prostheses (4 Sapien XT, 64 Sapien 3) or self-expandable prostheses (5 SJM Portico, 5 Symetis Acurate). Follow-up CT angiography was performed at a median of 4 months following index procedure (Interquartile range 1 month). Leaflet thrombosis was detected in 18 patients (23%, 14 Sapien 3, 1 Sapien XT, 2 SJM Portico, 1 Symetis Acurate). In patients with leaflet thickening on CT, only 11% were on either oral anticoagulation or new oral anticoagulants versus 50% for patients with no leaflet thickening (p 0.002). In patients with leaflet thrombosis, 3 leaflets were affected in 5 patients, 2 leaflets in 5 patients and in 8 patient only 1 leaflet was affected. Clinical symptoms (angina, dyspnea or both) were reported in 2/18 patients with leaflet thrombosis (11%) and in both patients a significant increase of the mean echocardiographic gradient over the prosthesis was documented. The peak and mean echocardiographic gradients obtained at the day of CT examination was significantly higher in symptomatic patients versus asymptomatic patients (peak 46 ± 7 vs. 23 ± 11 mmHg, mean 29 ± 7 vs. 12 ± 6 mmHg, p = 0.01 and 0.002, respectively). Follow-up CT was available for 4 patients with complete resolution of the hypo-attenuated leaflet thickening following treatment. CONCLUSION: Leaflet thrombosis following TAVI is a relatively frequent finding in patients referred for contrast enhanced CT angiography following TAVI. In the majority of patients it follows a subclinical course and is substantially more frequent in individuals who are not on oral anticoagulation. However, in patients with relevant increase in prosthetic gradients, symptomatic presentations are possible.
EVALuna2:33589

Leaflet thrombosis following transcatheter aortic valve implantation: insights from a single center experience - Achenbach, Stephan; Göller, Markus; Loders, Sabrina; Schuhbaeck, A.; Hell, M.; Marwan, Mohamed; Arnold, Martin (2016)
EVALuna2:33690

Left ventricular contraction patterns in Takotsubo Syndrome and their correlation with long-term clinical outcome - Gaede, Luise; Herchenbach, Amanda; Tröbs, Monique; Achenbach, Stephan; Marwan, Mohamed (IJC Heart & Vasculature, 2021)
Background: Takotsubo Syndrome (TTS) is diagnosed in 1–2% of all patients presenting with acute coronary syndrome. Next to the typical apical manifestation, other locations of left ventricular contraction abnormality are possible, but their relationship to patient characteristics, clinical correlates as well as long-term outcome are poorly understood. Methods & results: We retrospectively analyzed 126 patients presenting TTS. Cases were categorized according to left ventricular contraction abnormality patterns: typical apical pattern (71%, n = 89) vs. atypical patterns (29%, n = 37). Cases with typical TTS showed significantly higher levels of troponin I (3.12 ng/ml vs. 1.32 ng/ml, p = 0.013) and creatin kinase (CK) on admission (461 (±1207)U/l vs. 173 (±177) U/l, p = 0.03) as well as peak CK (973 (±2860)U/l vs. 301 (±328) U/l, p = 0.03) and more often ischemia related ECG changes (p = 0.02). Follow-up data was available for 85% of the patients. Median FU time was 4.4 years (IQR 1.4–7.7 years). All-cause mortality during follow-up was 39%, with no significant difference between patients with typical or atypical TTS (43% vs. 29%, p = 0.17). In multivariate logistic regression analysis, only anemia was predictive for long-term mortality (OR 3.93, 95%CI 1.02–2.08, p = 0.015). The majority of surviving patients (69%) reported good quality of life, even though only 56% reported being symptom-free. Conclusion: Patients with TTS have poor long-term prognosis with an overall mortality of 39.1% within 4 years and nearly half of all patients report persisting symptoms. Even though the apical contraction pattern is associated with higher elevation of serum markers for myocardial damage, it was not associated with higher long-term mortality.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Broken heart syndrome; Contraction pattern; Stress cardiomyopathy; Takotsubo cardiomyopathy; Takotsubo Syndrome

Localization of the femoral artery bifurcation: hips don't lie - in at least 97% of cases - Uehlein, Sabrina; Smolka, S.; Arnold, Martin; Marwan, Mohamed; Achenbach, Stephan (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Major coronary evaginations following implantation of bioresorbable vascular scaffolds: clinical and OCT characteristics - Blachutzik, F.; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, R.; Weissner, M.; Schlundt, Christian; Marwan, Mohamed (2017)
EVALuna2:36025

Major coronary evaginations following implantation of bioresorbable vascular scaffolds - Clinical and OCT characteristics - Blachutzik, Florian; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, Reinhard; Nef, Holger; Weissner, Melissa; Schlundt, Christian; Marwan, Mohamed (Cardiovascular Revascularization Medicine, 2019)
Background: Coronary evaginations can occur after implantation of bioresorbable vascular scaffolds (BRS) and may be associated with scaffold thrombosis. Aim of this study was to clarify the clinical manifestation, extent and time course of coronary artery remodeling in vessel segments that develop angiographically detectable evaginations following BRS implantation through optical coherence tomography (OCT) analysis.
CRIS-Team WoS Importer:2019-06-18

Membranous septum length as predictor for permanent pacemaker implantation after TAVI - Jung, Susan; Ammon, Fabian; Smolka, Silvia; Moshage, Maximilian; Marwan, Mohamed; Achenbach, Susanne (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Meta-Analysis of Bioprosthetic Valve Thrombosis After Transcatheter Aortic Valve Implantation - Rheude, Tobias; Pellegrini, Costanza; Stortecky, Stefan; Xhepa, Erion; Ammon, Fabian; Pilgrim, Thomas; Mayr, N. Patrick; Husser, Oliver; Achenbach, Stephan; Windecker, Stephan; Cassese, Salvatore; Joner, Michael; et al. (American Journal of Cardiology, 2020)
Bioprosthetic valve thrombosis may complicate transcatheter aortic valve implantation (TAVI). This meta-analysis sought to evaluate the prevalence and clinical impact of subclinical leaflet thrombosis (SLT) and clinical valve thrombosis (CVT) after TAVI. We summarized diagnostic strategies, prevalence of SLT and/or CVT and estimated their impact on the risk of all-cause death and stroke. Twenty studies with 12,128 patients were included. The prevalence of SLT and CVT was 15.1% and 1.2%, respectively. The risk of all-cause death was not significantly different between patients with SLT (relative risk [RR] 0.77; p = 0.22) and CVT (RR 1.29; p = 0.68) compared with patients without. The risk of stroke was higher in patients with CVT (RR 7.51; p <0.001) as compared with patients without, while patients with SLT showed no significant increase in the risk of stroke (RR 1.81; p = 0.17). Reduced left ventricular function was associated with increased prevalence, while oral anticoagulation was associated with reduced prevalence of bioprosthetic valve thrombosis. Bioprosthetic valve thrombosis is frequent after TAVI, but does not increase the risk of death. Clinical valve thrombosis is associated with a significantly increased risk of stroke. Future studies should focus on prevention and treatment of bioprosthetic valve thrombosis.
CRIS-Team Scopus Importer:2020-11-06

Multicenter Evaluation Of Coronary Dual-Source CT angiography in patients with intermediate Risk of Coronary Artery Stenoses (MEDIC): study design and rationale - Hausleiter, Jörg; Abbara, Suhny; Hoffmann, Udo; Becker, Christoph; Ovrehus, Kristian; Ropers, Dieter; Bathina, Ravi; Berman, Dan; Anders, Katharina; Uder, Michael; Meave, Aloha; Alexánderson, Erick; et al. (Journal of Cardiovascular Computed Tomography, 2014)
The diagnostic performance of multidetector row CT to detect coronary artery stenosis has been evaluated in numerous single-center studies, with only limited data from large cohorts with low-to-intermediate likelihood of coronary disease and in multicenter trials. The Multicenter Evaluation of Coronary Dual-Source CT Angiography in Patients with Intermediate Risk of Coronary Artery Stenoses (MEDIC) trial determines the accuracy of dual-source CT (DSCT) to identify persons with at least 1 coronary artery stenosis among patients with low-to-intermediate pretest likelihood of disease.The MEDIC trial was designed as a prospective, multicenter, international trial to evaluate the diagnostic performance of DSCT for the detection of coronary artery stenosis compared with invasive coronary angiography. The study includes 8 sites in Germany, India, Mexico, the United States, and Denmark. The study population comprises patients referred for a diagnostic coronary angiogram because of suspected coronary artery disease with an intermediate pretest likelihood as determined by sex, age, and symptoms. All evaluations are performed by blinded core laboratory readers.The primary outcome of the MEDIC trial is the accuracy of DSCT to identify the presence of coronary artery stenoses with a luminal diameter narrowing of 50% or more on a per-vessel basis. Secondary outcome parameters include per-patient and per-segment diagnostic accuracy for 50% stenoses and accuracy to identify stenoses of 70% or more. Furthermore, secondary outcome parameters include the influence of heart rate, Agatston score, body weight, body mass index, image quality, and diagnostic confidence on the accuracy to detect coronary artery stenoses >50% on a per-vessel basis.The results of the MEDIC trial will assess the clinical utility of coronary CT angiography in the evaluation of patients with intermediate pretest likelihood of coronary artery disease.
EVALuna2:14371

Non-invasive cardiac Imaging in the Diagnosis of CAD - Marwan, Mohamed (Deutsche Medizinische Wochenschrift, 2021)
CRIS-Team WoS Importer:2021-09-03

Non-invasive detection of coronary inflammation using computed tomography and prediction of residual cardiovascular risk (the CRISP CT study): a post-hoc analysis of prospective outcome data - Oikonomou, Evangelos K.; Desai, Milind Y.; Mancio, Jennifer; Alashi, Alaa; Centeno, Erika Hutt; Thomas, Sheena; Herdman, Laura; Kotanidis, Christos P.; Thomas, Katharine E.; Griffin, Brian P.; Flamm, Scott D.; Antonopoulos, Alexios S.; et al. (Lancet, 2018)
BACKGROUND: Coronary artery inflammation inhibits adipogenesis in adjacent perivascular fat. A novel imaging biomarker-the perivascular fat attenuation index (FAI)-captures coronary inflammation by mapping spatial changes of perivascular fat attenuation on coronary computed tomography angiography (CTA). However, the ability of the perivascular FAI to predict clinical outcomes is unknown. METHODS: In the Cardiovascular RISk Prediction using Computed Tomography (CRISP-CT) study, we did a post-hoc analysis of outcome data gathered prospectively from two independent cohorts of consecutive patients undergoing coronary CTA in Erlangen, Germany (derivation cohort) and Cleveland, OH, USA (validation cohort). Perivascular fat attenuation mapping was done around the three major coronary arteries-the proximal right coronary artery, the left anterior descending artery, and the left circumflex artery. We assessed the prognostic value of perivascular fat attenuation mapping for all-cause and cardiac mortality in Cox regression models, adjusted for age, sex, cardiovascular risk factors, tube voltage, modified Duke coronary artery disease index, and number of coronary CTA-derived high-risk plaque features. FINDINGS: Between 2005 and 2009, 1872 participants in the derivation cohort underwent coronary CTA (median age 62 years [range 17-89]). Between 2008 and 2016, 2040 patients in the validation cohort had coronary CTA (median age 53 years [range 19-87]). Median follow-up was 72 months (range 51-109) in the derivation cohort and 54 months (range 4-105) in the validation cohort. In both cohorts, high perivascular FAI values around the proximal right coronary artery and left anterior descending artery (but not around the left circumflex artery) were predictive of all-cause and cardiac mortality and correlated strongly with each other. Therefore, the perivascular FAI measured around the right coronary artery was used as a representative biomarker of global coronary inflammation (for prediction of cardiac mortality, hazard ratio [HR] 2·15, 95% CI 1·33-3·48; p=0·0017 in the derivation cohort, and 2·06, 1·50-2·83; p<0·0001 in the validation cohort). The optimum cutoff for the perivascular FAI, above which there is a steep increase in cardiac mortality, was ascertained as -70·1 Hounsfield units (HU) or higher in the derivation cohort (HR 9·04, 95% CI 3·35-24·40; p<0·0001 for cardiac mortality; 2·55, 1·65-3·92; p<0·0001 for all-cause mortality). This cutoff was confirmed in the validation cohort (HR 5·62, 95% CI 2·90-10·88; p<0·0001 for cardiac mortality; 3·69, 2·26-6·02; p<0·0001 for all-cause mortality). Perivascular FAI improved risk discrimination in both cohorts, leading to significant reclassification for all-cause and cardiac mortality. INTERPRETATION: The perivascular FAI enhances cardiac risk prediction and restratification over and above current state-of-the-art assessment in coronary CTA by providing a quantitative measure of coronary inflammation. High perivascular FAI values (cutoff ≥-70·1 HU) are an indicator of increased cardiac mortality and, therefore, could guide early targeted primary prevention and intensive secondary prevention in patients. FUNDING: British Heart Foundation, and the National Institute of Health Research Oxford Biomedical Research Centre.
EVALuna2:35969

Non-invasive prediction of hemodynamically significant coronary artery stenoses by contrast density difference in coronary CT angiography - Hell, Michaela M.; Dey, Damini; Achenbach, Stephan; Schmid, Jasmin; Schuhbaeck, Annika; Marwan, Mohamed (European Journal of Radiology, 2015)
Coronary computed tomography angiography (CTA) allows the detection of obstructive coronary artery disease. However, its ability to predict the hemodynamic significance of stenoses is limited. We assessed differences in plaque characteristics and contrast density difference between hemodynamically significant and non-significant stenoses, as defined by invasive fractional flow reserve (FFR).Lesion characteristics of 59 consecutive patients (72 lesions) in whom invasive FFR was performed in at least one coronary artery with moderate to high-grade stenoses in coronary CTA were evaluated by two experienced readers. Coronary CTA data sets were acquired on a second-generation dual-source CT scanner using retrospectively ECG-gated spiral acquisition or prospectively ECG-triggered axial acquisition mode. Plaque volume and composition (non-calcified, calcified), remodeling index as well as contrast density difference (defined as the percentage decline in luminal CT attenuation/cross-sectional area over the lesion) were assessed using a semi-automatic software tool (Autoplaq). Additionally, the transluminal attenuation gradient (defined as the linear regression coefficient between intraluminal CT attenuation and length from the ostium) was determined. Differences in lesion characteristics between hemodynamically significant (invasively measured FFR <=0.80) and non-significant lesions (FFR >0.80) were determined.Mean patient age was 64±11 years with 44 males (75%). 21 out of 72 coronary artery lesions (29%) were hemodynamically significant according to invasive FFR. Mean invasive FFR was 0.66±0.12 vs. 0.91±0.05 for hemodynamically significant versus non-significant lesions. Hemodynamically significant lesions showed a significantly greater percentage of non-calcified plaque compared to non-hemodynamically relevant lesions (51.3±15.3% vs. 43.6±16.5%, p=0.021). Contrast density difference was significantly increased in hemodynamically relevant lesions (26.0±20.2% vs. 16.6±10.9% for non-significant lesions; p=0.013). At a threshold of >=24%, the contrast density difference predicted hemodynamically significant lesions with a specificity of 75%, sensitivity of 33%, PPV of 35% and NPV of 73%. The transluminal attenuation gradient showed no significant difference between hemodynamically significant and non-significant lesions (-1.4±1.4HU/mm vs. -1.1±1.3HU/mm, p=n.s.).Quantitative contrast density difference across coronary lesions in coronary CTA data sets may be applied as a non-invasive tool to identify hemodynamically significant stenoses.
EVALuna2:12090

OCT-assessment of scaffold resorption: Analysis of strut intensity by a new resorption index for poly-l-lactic acid bioresorbable vascular scaffolds - Blachutzik, Florian; Achenbach, Stephan; Tröbs, Monique; Boeder, Niklas; Doerr, Oliver; Weissner, Melissa; Bauer, Timm; Nef, Holger; Hamm, Christian; Schlundt, Christian; Marwan, Mohamed (Catheterization and Cardiovascular Interventions, 2019)
Background: The aim of this study was to analyze individual differences in resorption of bioresorbable vascular scaffolds (BRS) through optical coherence tomography (OCT) analysis and to identify factors potentially influencing the resorption process. Methods: Between April 2016 and July 2017 clinically driven invasive coronary angiography and OCT examinations were performed in 36 patients who had previously been treated with a total of 48 BRS (ABSORB BVS, Abbott Vascular, Santa Clara, CA). For each scaffold, a new BRS-RESORB-INDEX (BRI) was calculated. Results: The mean time interval since implantation was 789 ± 321 days. In OCT, BRS struts remained detectable in all 48 BRS. Normalized light intensity as a marker for the resorption of BRS struts increased with time in a linear fashion (Spearman Rho: p <.001, correlation coefficient =.90; R 2 [linear] =.91). Multivariable analysis identified diabetes (BRI of patients with diabetes vs. patients without diabetes: 0.34 ± 0.13 vs. 0.58 ± 0.22; p =.002) and presence of Peri-strut low intensity areas (PSLIA, BRI of 10 patients with PSLIA vs. 26 patients without PSLIA: 0.44 ± 0.21 vs. 0.61 ± 18; p =.027) as independent predictors for a prolonged BRS resorption, whereas the resorption rate in ACS patients (STEMI, NSTEMI, and unstable angina; n = 13) was significantly higher as compared to patients without ACS (0.62 ± 0.17 vs. 0.43 ± 0.24; p =.012). Conclusion: In humans, BRS resorption rate is significantly influenced by numerous factors. Our data suggest that diabetes and PSLIA are associated with a prolonged resorption process, whereas in ACS patients, BRS resorption appears to be significantly faster.
CRIS-Team Scopus Importer:2019-12-13
Keywords: bioresorbable vascular scaffolds; optical coherence tomography; percutaneous coronary intervention

OCT-assessment of scaffold resorption: analysis of strut intensity via the brs-resorb-index for poly-L-lactic acid bioresorbable vascular scaffolds - Blachutzik, F.; Achenbach, Stephan; Tröbs, Monique; Weissner, M.; Nef, H.; Schlundt, Christian; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Optical coherence tomography: influence of contrast concentration on image quality and diagnostic confidence - Blachutzik, Florian; Achenbach, Stephan; Nef, Holger; Hamm, Christian; Dorr, Oliver; Boeder, Niklas; Tröbs, Monique; Schneider, Reinhard; Röther, Jens; Schlundt, Christian; Marwan, Mohamed (Heart and Vessels, 2017)
OCT requires intracoronary injection of contrast agent to remove blood from the coronary lumen during data acquisition, which is a possible limitation of this method. Aim of this study was to analyze the influence of iodine concentration on image quality and diagnostic certainty of optical coherence tomography (OCT). OCT sequences acquired using contrast agent with a reduced concentration of 150 mg iodine/ml and a standard concentration of 350 mg iodine/ml were analyzed. Cross-sectional images with a spacing of 10 mm were evaluated regarding image quality and diagnostic confidence. A total of 67 OCT sequences acquired in 24 patients were analyzed. 31 sequences were acquired using contrast agent with a concentration of 150 mg iodine/ml and 36 sequences with a concentration of 350 mg iodine/ml. The percentage of remaining blood streaks in the cross sections was significantly lower for 350 mg iodine/ml compared to 150 mg iodine/ml (19 ± 21 vs. 34 ± 26%, p = 0.013). Contrast with 350 mg iodine/ml showed a significantly higher percentage of completely flushed pullback length as compared to 150 mg iodine/ml (78 ± 24 vs. 58 ± 27%, p = 0.004). Diagnostic certainty was significantly higher for 350 mg iodine/ml than for 150 mg iodine/ml (Likert scale average 1.4 ± 0.7 vs. 2.1 ± 1.2, p < 0.001; Likert scale: 1 = absolutely confident, 2 = confident with slight doubts, 3 = doubtful/not confident, 4 = non-diagnostic). Regarding image quality and diagnostic certainty, contrast agent with a concentration of 350 mg iodine/ml is superior to 150 mg iodine/ml.
EVALuna2:33638

Patient-Specific Myocardial Infarction Risk Thresholds from AI-Enabled Coronary Plaque Analysis - Miller, Robert J.H.; Manral, Nipun; Lin, Andrew; Shanbhag, Aakash; Park, Caroline; Kwiecinski, Jacek; Killekar, Aditya; McElhinney, Priscilla; Matsumoto, Hidenari; Razipour, Aryabod; Grodecki, Kajetan; Kwan, Alan C.; et al. (Circulation: Cardiovascular Imaging, 2024)
BACKGROUND: Plaque quantification from coronary computed tomography angiography has emerged as a valuable predictor of cardiovascular risk. Deep learning can provide automated quantification of coronary plaque from computed tomography angiography. We determined per-patient age- and sex-specific distributions of deep learning-based plaque measurements and further evaluated their risk prediction for myocardial infarction in external samples. METHODS: In this international, multicenter study of 2803 patients, a previously validated deep learning system was used to quantify coronary plaque from computed tomography angiography. Age- and sex-specific distributions of coronary plaque volume were determined from 956 patients undergoing computed tomography angiography for stable coronary artery disease from 5 cohorts. Multicenter external samples were used to evaluate associations between coronary plaque percentiles and myocardial infarction. RESULTS: Quantitative deep learning plaque volumes increased with age and were higher in male patients. In the combined external sample (n=1847), patients in the ≥75th percentile of total plaque volume (unadjusted hazard ratio, 2.65 [95% CI, 1.47-4.78]; P=0.001) were at increased risk of myocardial infarction compared with patients below the 50th percentile. Similar relationships were seen for most plaque volumes and persisted in multivariable analyses adjusting for clinical characteristics, coronary artery calcium, stenosis, and plaque volume, with adjusted hazard ratios ranging from 2.38 to 2.50 for patients in the ≥75th percentile of total plaque volume. CONCLUSIONS: Per-patient age- and sex-specific distributions for deep learning-based coronary plaque volumes are strongly predictive of myocardial infarction, with the highest risk seen in patients with coronary plaque volumes in the ≥75th percentile. 2024 American Heart Association, Inc.
CRIS-Team Scopus Importer:2024-10-25
Keywords: cardiac imaging techniques; coronary artery disease; deep learning; myocardial infarction; plaque; atherosclerotic

Patient-specific predictors of image noise in coronary CT angiography - Schuhbaeck, Annika; Schäfer, Marcella; Marwan, Mohamed; Gauss, Soeren; Muschiol, Gerd; Lell, Michael; Pflederer, Tobias; Ropers, Dieter; Rixe, Johannes; Hamm, Christian; Daniel, Werner G.; Achenbach, Stephan (Journal of Cardiovascular Computed Tomography, 2013)
Background: Coronary computed tomography (CT) angiography can be associated with high radiation exposure. Reduction of tube voltage from 120 kV to 100 kV can reduce the dose by up to 40%, but it also increases image noise. Objective: We aimed to find a patient-specific predictor of image noise to determine the use of reduced tube voltage. Methods: Contrast-enhanced coronary dual-source CT angiography data sets [prospectively electrocardiogram (ECG)-triggered axial and retrospectively ECG-gated spiral acquisition, rotation of 280 milliseconds, 2 × 128 × 0.6 mm collimation, 100 kV, 320 mAs] of 165 patients (age, 54 ± 13 years) for the detection of coronary artery stenoses were analyzed. Image noise was measured in the aortic root. Influence of body weight, height, body mass index, thoracic cross sectional area, as well as the area of the thoracic solid tissue were analyzed. Results: Mean image noise in the aorta was 35.1 ± 8.9 HU. Mean dose length product was 207 ± 184 cm · cGy with an average effective dose of 2.9 ± 2.6 mSv. The patient cohort was divided into tertiles according to image noise. Numerous parameters, including BMI and body weight, were significantly different between the highest and lowest tertiles. In multivariable regression analysis, the area of the thoracic solid tissue was the only independent predictor of image noise (P < 0.0001). Conclusions: The area of the thoracic solid tissue at the level of the aortic root predicts image noise and may hence be used for the decision to reduce tube voltage from 120 kV to 100 kV. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Coronary CT angiography; Dual-source CT; Image noise; Tube voltage

Percutaneous coronary intervention of unprotected left main stenoses - Procedural data and outcome depending on SYNTAX I Score - Blachutzik, Florian; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, Reinhard; Schlundt, Christian; Marwan, Mohamed (Cardiovascular Revascularization Medicine, 2018)
BACKGROUND: We hypothesized that SYNTAX I score is a predictor for procedure complexity in left main PCI. Procedure complexity, duration and contrast load may contribute to adverse outcome of complex left main percutaneous coronary intervention (PCI). METHODS: In 105 consecutive patients who underwent PCI of unprotected left main coronary artery stenoses between 2014 and 2016, clinical parameters as well as PCI characteristics and follow-up data were analyzed. RESULTS: The mean SYNTAX I score was 29 ± 12, with 66 patients having a SYNTAX I score ≤ 32 and 39 patients a SYNTAX I score > 32. In patients with high SYNTAX I score vs. low-to-intermediate SYNTAX I score, single stent techniques were performed significantly less frequently (18% vs. 68%; p < 0.001), while Crush (44% vs. 5%; p < 0.001) and Culotte techniques (20% vs. 5%; p = 0.003) were performed significantly more frequently. Procedural success was achieved in all 105 cases without periprocedural mortality. During follow up, repeat PCI was necessary significantly more frequently in patients with high compared to patients with low-to-intermediate SYNTAX I score (34% vs.13%; p = 0.003). Nevertheless, overall mortality did not differ between patients with high vs. low-to-intermediate SYNTAX I score (20% vs. 18%). CONCLUSIONS: PCI strategies for the treatment of left main coronary artery stenoses get significantly more complex with increasing SYNTAX I scores. While this translates into a significantly longer procedure duration and contrast load, short-term outcome seems not to be influenced by the SYNTAX I score.
EVALuna2:213082

Pericoronary adipose tissue and quantitative global non-calcified plaque characteristics from CT angiography do not differ in matched South Asian, East Asian and European-origin Caucasian patients with stable chest pain - Göller, Markus; Rahman Ihdayhid, Abdul; Cadet, Sebastien; Lin, Andrew; Adams, Daniel; Thakur, Udit; Yap, Grace; Achenbach, Stephan; Dey, Damini; Ko, Brian; Marwan, Mohamed (European Journal of Radiology, 2020)
Purpose: South Asian (SA) have been observed to have higher cardiovascular mortality rates compared to East Asians (EA) and Caucasians. Pericoronary adipose tissue (PCAT) attenuation around the right coronary artery (RCA) from coronary CT angiography (CTA) has been associated with coronary inflammation and cardiac death. We aimed to investigate i) the relationship between plaque characteristics and PCAT attenuation and ii) to assess gender and ethnic differences in PCAT attenuation using a matched cohort of SA, EA and Caucasians. Method: Three-hundred symptomatic patients who underwent CTA were matched for age, gender, BMI and diabetes (100 in each ethnic group). Semi-automated software was used to quantify the total volumes and burden of non-calcified plaque (NCP), low-density non-calcified plaque (LD-NCP) and calcified plaque (CP) in blinded core-lab analysis. PCAT CT attenuation was measured around the RCA (10–50 mm from RCA ostium), the most standardized model for PCAT analysis. Results: The total volumes and burden of NCP, LD-NCP and CP were comparable in the ethnic groups (each p > 0.05). PCAT attenuation was higher in patients with coronary plaque. PCAT attenuation correlated with the total volumes and burden of NCP, LD-NCP and CP (r>0.17; p < 0.003). Within the RCA this correlation persisted only for NCP features (r>0.39;p < 0.001). Males showed higher PCAT attenuation (p < 0.001). PCAT attenuation was similar between Caucasian, EA and SA (p = 0.32). Conclusions: PCAT CT attenuation correlated most with its surrounded NCP features further highlighting its role as surrogate measure of coronary inflammation. As coronary plaque burden and RCA PCAT attenuation did not differ between ethnic groups, causes of increased cardiac mortality in South Asians needs further investigations.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Atherosclerosis; Computerized tomography (CT); Pericoronary adipose tissue; Race and ethnicity

Pericoronary Adipose Tissue Computed Tomography Attenuation and High-Risk Plaque Characteristics in Acute Coronary Syndrome Compared With Stable Coronary Artery Disease - Goeller, Markus; Achenbach, Stephan; Cadet, Sebastien; Kwan, Alan C.; Commandeur, Frederic; Slomka, Piotr J.; Gransar, Heidi; Albrecht, Moritz H.; Tamarappoo, Balaji K.; Berman, Daniel S.; Dey, Damini; Marwan, Mohamed (JAMA Cardiology, 2018)
Importance: Pericoronary adipose tissue (PCAT) computed tomography (CT) attenuation measured from coronary CT angiography (CTA) may be a promising metric in identifying high-risk plaques. Objective: To determine whether high-risk plaque characteristics from coronary CTA are associated with PCAT CT attenuation in patients with a first acute coronary syndrome (ACS) and matched controls with stable coronary artery disease (CAD). Design, Setting, and Participants: This retrospective, single-center case-control study (data were acquired at the University of Erlangen from 2009-2010) analyzed the CTA data sets of 19 patients who presented with ACS and 16 controls with stable CAD who were matched based on sex, age, and risk factors. Study observers were blinded to patients' clinical data. Semiautomated software was used to quantify and characterize plaques. The CT attenuation (Hounsfield unit [HU]) of PCAT was automatically measured around all lesions. Main Outcomes and Measures: To investigate the association between high-risk plaque characteristics from CTA and PCAT CT attenuation as a novel surrogate measure of coronary inflammation. Results: A total of 35 patients (mean [SD] age, 59.5 [11.3] years; 30 men [86%] and 5 women [14%]) were included in the analysis. Low- and intermediate-attenuation noncalcified plaque (NCP) burden were increased in culprit lesions (n = 19) compared with both nonculprit lesions (n = 55) in patients with ACS (12.6% vs 3.6%; P < .001; 38.4% vs 19.4%; P < .001) and the control group's highest-grade stenosis lesions (n = 16) (12.6% vs 5.6%; P = .002; 38.4% vs 22.1%; P < .001). Pericoronary adipose tissue attenuation was increased around culprit lesions (n = 19) compared with nonculprit lesions (n = 55) in patients with ACS (-69.1 HU vs -74.8 HU; P = .01) and highest-grade stenosis lesions in control patients (n = 16) (-69.1 HU vs -76.4 HU; P = .01). Pericoronary adipose tissue CT attenuation of all lesions in patients with ACS (n = 74) correlated more strongly with intermediate-attenuation (r = 0.393; P = .001) over low-attenuation (r = 0.221; P = .06) and high-attenuation NCP burden (r = -0.103; P = .38). In a multivariable analysis, low- and intermediate-attenuation NCP burden and PCAT CT attenuation were independently associated with the presence of culprit lesions (P < .05). Conclusions and Relevance: Pericoronary CT attenuation was increased around culprit lesions compared with nonculprit lesions of patients with ACS and the lesions of matched controls. Combined quantitative high-risk plaque features and PCAT CT attenuation may allow for a more reliable identification of vulnerable plaques.
EVALuna2:35975

Pericoronary adipose tissue CT attenuation and its association with serum levels of atherosclerosis-relevant inflammatory mediators, coronary calcification and major adverse cardiac events - Göller, Markus; Achenbach, Stephan; Herrmann, Nicolai; Bittner, Daniel O.; Kilian, Tobias; Dey, Damini; Raaz-Schrauder, Dorette; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2021)
Background: Increased attenuation of pericoronary adipose tissue (PCAT) around the right coronary artery (RCA) derived from coronary CTA might detect coronary inflammation. We investigated a potential association between RCA PCAT attenuation and serum levels of atherosclerosis-relevant cytokines and MACE (coronary revascularization, myocardial infarction and/or cardiac death). Methods: Blood samples of 293 clinically stable individuals (59.0 ​± ​9.8 years, 69% males) were analyzed for atherosclerosis-relevant cytokines including interleukin (IL)-2, IL- 4, IL-6, IL-7, IL-8, IL-10, IL-13, IL-15, IL-17, TNF-a, IP-10, CRP, MCP-1, MIP-1a, Eotaxin and GM-CSF. Subjects also underwent coronary calcium scoring (CCS) followed by CTA. PCAT CT attenuation was measured around the RCA using semi-automated software. Increased RCA PCAT attenuation was defined as PCAT attenuation above the 75th percentile (>−73.5 HU). To assess MACE, 232 individuals were followed for a mean duration of 9.6 ​± ​2.1 years. Results: In patients with increased RCA PCAT attenuation the serum levels of MCP-1 were increased (p ​< ​0.01), whereas levels of anti-inflammatory mediators IL-4 and -13 were significantly reduced (each p ​< ​0.05). Adipocytokine MCP-1 (r ​= ​0.23, p ​< ​0.01) and pro-inflammatory mediator IL-7 (r ​= ​0.12, p ​= ​0.04) showed a mild positive correlation with RCA PCAT attenuation, whereas anti-inflammatory mediators Il-4, -10 and -13 correlated inversely (each r < −0.12, each p ​< ​0.05). 40/232 patients experienced MACE during follow-up. In multivariable Cox regression analysis increased RCA PCAT attenuation was shown to be an independent predictor of MACE (HR 2.01, p ​= ​0.044). Conclusions: Increased RCA PCAT CT attenuation shows a weak association with serum levels of selected atherosclerosis-relevant inflammatory biomarkers. Increased RCA PCAT attenuation is an independent predictor of MACE and may potentially guide future prevention strategies in stable patients.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Atherosclerosis-relevant inflammatory biomarkers; Coronary calcium score; CT attenuation; Inflammation; MACE; Pericoronary adipose tissue

PERIVASCULAR FAT ATTENUATION INDEX MAPPING AROUND THE RIGHT AND LEFT CORONARY ARTERY INDEPENDENTLY PREDICT CARDIAC MORTALITY - Kotanidis, Christos P.; Oikonomou, Evangelos K.; Thomas, Katharine E.; Alashi, Alaa; Antonopoulos, Alexios S.; Shirodaria, Cheerag; Neubauer, Stefan; Channon, Keith M.; Achenbach, Stephan; Desai, Milind Y.; Antoniades, Charalambos; Marwan, Mohamed (HEART, 2020)
CRIS-Team WoS Importer:2021-01-29

Perivascular fat attenuation index stratifies the cardiac risk associated with high-risk plaque features on coronary computed tomography angiography - Oikonomou, E. K.; Mancio, J.; Kotanidis, C. K.; Thomas, K. E.; Alashi, A.; Centeno, E. Hutt; Antonopoulos, A. S.; Shirodaria, C.; Neubauer, S.; Channon, K. M.; Achenbach, Stephan; Desai, M. Y.; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Predictors of CT-derived FFR in patients with suspected CAD beyond severity of coronary stenosis - Smolka, S.; Fava, A.; Moshage, Maximilian; Marwan, Mohamed; Achenbach, Stephan; Desai, M. Y. (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Predictors of Technical Failure in Transradial Coronary Angiography and Intervention - Tröbs, Monique; Achenbach, Stephan; Plank, Pia Maria; Röther, Jens; Klinghammer, Lutz; Blachutzik, Florian; Schlundt, Christian; Marwan, Mohamed (American Journal of Cardiology, 2017)
Transradial access for coronary angiography and intervention is preferred over the femoral approach but can be technically challenging. Identification of predictors of transradial access failure is important, especially in the context of acute coronary syndromes. We therefore retrospectively analyzed 13,095 consecutive patients (66 ± 12 years, 64% male) in whom transradial access was attempted for coronary angiography or intervention to identify predictors of transradial access failure. Angiograms and patient files were systematically reviewed to analyze patient characteristics associated with failure. Transradial access failure rate was 6.8% (909 of 13,095). Patients with transradial access failure were more frequently female (9.5% vs 5.5%; p <0.001), significantly older (68 ± 12 vs 66 ± 12 years, p <0.001), and had a smaller body surface area (1.89 ± 0.21 vs 1.94 ± 0.2 m2; p <0.001). Transradial failure was not significantly more frequent in ST-elevation myocardial infarction versus other patients (8.1% vs 6.9%, p = 0.195). After multivariable adjustment, only female sex (odds ratio [OR] 1.44, p <0.001), higher patient age (OR 1.01/year, p = 0.002), and lower height (OR 0.98/cm, p = 0.004) independently predicted transradial access failure. In conclusion, female sex, higher age, and smaller height independently predict transradial access failure in coronary angiography and intervention. Failure rate in ST-elevation myocardial infarction is not significantly increased.
EVALuna2:33605

Prospectively ECG-triggered high-pitch coronary angiography with third-generation dual-source CT at 70 kVp tube voltage: Feasibility, image quality, radiation dose, and effect of iterative reconstruction - Hell, Michaela M.; Bittner, Daniel; Schuhbaeck, Annika; Muschiol, Gerd; Brand, Michael; Lell, Michael; Uder, Michael; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2014)
Low tube voltage reduces radiation exposure in coronary CT angiography (CTA). Using 70 kVp tube potential has so far not been possible because CT systems were unable to provide sufficiently high tube current with low voltage.We evaluated feasibility, image quality (IQ), and radiation dose of coronary CTA using a third-generation dual-source CT system capable of producing 450 mAs tube current at 70 kVp tube voltage.Coronary CTA was performed in 26 consecutive patients with suspected coronary artery disease, selected for body weight <100 kg and heart rate <60 beats/min. High-pitch spiral acquisition was used. Filtered back projection (FBP) and iterative reconstruction (IR) algorithms were applied. IQ was assessed using a 4-point rating scale (1 = excellent, 4 = nondiagnostic) and objective parameters.Mean age was 62 ± 9 years (46% males; mean body mass index, 27.7 ± 3.8 kg/m(2); mean heart rate, 54 ± 5 beats/min). Mean dose-length product was 20.6 ± 1.9 mGy × cm; mean estimated effective radiation dose was 0.3 ± 0.03 mSv. Diagnostic IQ was found in 365 of 367 (FBP) and 366 of 367 (IR) segments (P nonsignificant). IQ was rated "excellent" in 53% (FBP) and 86% (IR) segments (P = .001) and "nondiagnostic" in 2 (FBP) and 1 segment (IR) (P nonsignificant). Mean IQ score was lesser in FBP vs IR (1.5 ± 0.4 vs 1.1 ± 0.2; P < .001). Image noise was lower in IR vs FBP (60 ± 10 HU vs 74 ± 8 HU; P < .001).In patients <100 kg and with a regular heart rate <60 beats/min, third-generation dual-source CT using high-pitch spiral acquisition and 70 kVp tube voltage is feasible and provides both robust IQ and very low radiation exposure.
EVALuna2:11954

Quantification of epicardial adipose tissue by cardiac CT: Influence of acquisition parameters and contrast enhancement - Koenig, Susanna; Schreiber, Kirsten; Ammon, Fabian; Göller, Markus; Bittner, Daniel; Achenbach, Stephan; Hell, Michaela; Marwan, Mohamed (European Journal of Radiology, 2019)
Purpose: While computed tomography (CT) is frequently used to quantify epicardial adipose tissue (EAT), the effect of different acquisition parameters on EAT volume has not been systematically reported. We assessed the influence of low-voltage acquisition and contrast enhancement on EAT quantification. Method: Two independent cohorts (100 and 127 patients) referred for routine coronary CT were included. One cohort received a low-voltage and a standard voltage non-contrast acquisition (120 and 100 kV), the other cohort underwent non-contrast and contrast-enhanced CT. EAT volume was quantified using a semi-automated analysis software. Whereas the lower EAT threshold was consistently set at -190 Hounsfield Units (HU), different upper thresholds for EAT were analyzed. Bland-Altman analysis was used to analyze the agreement of EAT volume between scans with different acquisition parameters. We referred to a non-enhanced 120 kV acquisition with an upper threshold of -30 HU. Results: Mean EAT volume was 159 ± 76 ml as measured in 120 kV non-contrast data sets with an upper threshold of -30 HU. For 100 kV data sets, an upper threshold of -40 HU showed the best correlation (r = 0.961, p < 0.05). Significant overestimation was found for upper thresholds of -20 and -30 HU and significant underestimation for -50 HU. In non-contrast vs. contrast-enhanced acquisitions, there was a significant underestimation of EAT volume for contrast-enhanced scans (mean difference 31 ml, 95% limits of agreement 27 to −89 ml). Conclusions: CT-based EAT volume quantification in low-voltage and contrast-enhanced images is feasible. However, adjustment of the upper threshold for detection of fat is mandatory.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Cardiac computed tomography; Contrast-enhanced imaging; Epicardial adipose tissue; Low-dose acquisition

Quantification of epicardial fat by computed tomography: Why, when and how? - Marwan, Mohamed; Achenbach, Stephan (Journal of Cardiovascular Computed Tomography, 2013)
In the past decade, interest has grown in the relation between epicardial fat and cardiovascular disease. Several imaging modalities such as echocardiography, computed tomography, and magnetic resonance imaging can be used to quantify epicardial adipose tissue. Computed tomography provides high spatial resolution and true volume coverage of the heart; therefore, it constitutes an attractive approach to quantifying epicardial fat. An increasing body of evidence has been accumulated which shows a relation between epicardial fat volume and coronary atherosclerosis, cardiovascular outcomes, and even non-atherosclerotic heart disease such as atrial fibrillation. The association of increased epicardial fat volume with cardiac disease remains significant even after correction for weight, body mass index, and traditional cardiovascular risk factors. The mechanisms have not been reliably identified, but metabolic properties of epicardial fat may play a role. At the present time, epicardial fat quantification is not included in recommended algorithms for risk stratification. However, the available data are intriguing enough to warrant further research. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: CT; Epicardial fat

Radial versus femoral approach for rotational atherectomy - technical aspects and procedural outcomes - Bargon, Sophie; Achenbach, Stephan; Gaede, Luise; Tröbs, Monique; Marwan, Mohamed; Ammon, Fabian; Ferstl, Paul; Schacher, Nora (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Radiation exposure during transcatheter aortic valve implantation (TAVI): comparison of balloon-expandable versus self-expandable prostheses - Arnold, Martin; Nemec, S.; Kondruweit, Markus; Marwan, Mohamed; Achenbach, Stephan (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Radiomics-Based Precision Phenotyping Identifies Unstable Coronary Plaques From Computed Tomography Angiography - Lin, Andrew; Kolossváry, Márton; Cadet, Sebastien; McElhinney, Priscilla; Göller, Markus; Han, Donghee; Yuvaraj, Jeremy; Nerlekar, Nitesh; Slomka, Piotr J.; Marwan, Mohamed; Nicholls, Stephen J.; Achenbach, Stephan; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2022)
Objectives: The aim of this study was to precisely phenotype culprit and nonculprit lesions in myocardial infarction (MI) and lesions in stable coronary artery disease (CAD) using coronary computed tomography angiography (CTA)-based radiomic analysis. Background: It remains debated whether any single coronary atherosclerotic plaque within the vulnerable patient exhibits unique morphology conferring an increased risk of clinical events. Methods: A total of 60 patients with acute MI prospectively underwent coronary CTA before invasive angiography and were matched to 60 patients with stable CAD. For all coronary lesions, high-risk plaque (HRP) characteristics were qualitatively assessed, followed by semiautomated plaque quantification and extraction of 1,103 radiomic features. Machine learning models were built to examine the additive value of radiomic features for discriminating culprit lesions over and above HRP and plaque volumes. Results: Culprit lesions had higher mean volumes of noncalcified plaque (NCP) and low-density noncalcified plaque (LDNCP) compared with the highest-grade stenosis nonculprits and highest-grade stenosis stable CAD lesions (NCP: 138.1 mm3 vs 110.7 mm3 vs 102.7 mm3; LDNCP: 14.2 mm3 vs 9.8 mm3 vs 8.4 mm3; both Ptrend < 0.01). In multivariable linear regression adjusted for NCP and LDNCP volumes, 14.9% (164 of 1,103) of radiomic features were associated with culprits and 9.7% (107 of 1,103) were associated with the highest-grade stenosis nonculprits (critical P < 0.0007) when compared with highest-grade stenosis stable CAD lesions as reference. Hierarchical clustering of significant radiomic features identified 9 unique data clusters (latent phenotypes): 5 contained radiomic features specific to culprits, 1 contained features specific to highest-grade stenosis nonculprits, and 3 contained features associated with either lesion type. Radiomic features provided incremental value for discriminating culprit lesions when added to a machine learning model containing HRP and plaque volumes (area under the receiver-operating characteristic curve 0.86 vs 0.76; P = 0.004). Conclusions: Culprit lesions and highest-grade stenosis nonculprit lesions in MI have distinct radiomic signatures compared with lesions in stable CAD. Within the vulnerable patient may exist individual vulnerable plaques identifiable by coronary CTA-based precision phenotyping.
CRIS-Team Scopus Importer:2022-05-06
Keywords: coronary computed tomography angiography; coronary plaque; machine learning; myocardial infarction; radiomics

Rapidly growing cardiac myxoma diagnosed within 1 year after unremarkable prior cardiac imaging - Strecker, Thomas; Nooh, Ehab; Agaimy, Abbas; Marwan, Mohamed (Journal of Cardiac Surgery, 2019)
CRIS-Team Scopus Importer:2019-11-26
Keywords: cardiac surgery; cardiac tumors; computed tomography; echocardiography; myxoma; pathology

Relationship between changes in pericoronary adipose tissue attenuation and coronary plaque burden quantified from coronary computed tomography angiography - Goeller, Markus; Tamarappoo, Balaji K.; Kwan, Alan C.; Cadet, Sebastien; Commandeur, Frederic; Razipour, Aryabod; Slomka, Piotr J.; Gransar, Heidi; Chen, Xi; Otaki, Yuka; Friedman, John D.; Cao, J. Jane; et al. (European Heart Journal - Cardiovascular Imaging, 2019)
AIMS: Increased attenuation of pericoronary adipose tissue (PCAT) around the proximal right coronary artery (RCA) from coronary computed tomography angiography (CTA) has been shown to be associated with coronary inflammation and improved prediction of cardiac death over plaque features. Our aim was to investigate whether PCAT CT attenuation is related to progression of coronary plaque burden. METHODS AND RESULTS: We analysed CTA studies of 111 stable patients (age 59.2 ± 9.8 years, 77% male) who underwent sequential CTA (3.4 ± 1.6 years between scans) with identical acquisition protocols. Total plaque (TP), calcified plaque (CP), non-calcified plaque (NCP), and low-density non-calcified plaque (LD-NCP) volumes and corresponding burden (plaque volume × 100%/vessel volume) were quantified using semi-automated software. PCAT CT attenuation (HU) was measured around the proximal RCA, the most standardized method for PCAT analysis. Patients with an increase in NCP burden (n = 51) showed an increase in PCAT attenuation, whereas patients with a decrease in NCP burden (n = 60) showed a decrease 4.4 [95% confidence interval (CI) 2.6-6.2] vs. -2.78 (95% CI -4.6 to -1.0) HU, P < 0.0001. Changes in PCAT attenuation correlated with changes in the burden of NCP (r = 0.55, P < 0.001) and LD-NCP (r = 0.24, P = 0.01); but not CP burden (P = 0.3). Increased baseline PCAT attenuation ≥-75 HU was independently associated with increase in NCP (odds ratio 3.07, 95% CI 1.4-7.0; P < 0.008) and TP burden on follow-up CTA. CONCLUSION: PCAT attenuation measured from routine CTA is related to the progression of NCP and TP burden. This imaging biomarker may help to identify patients at increased risk of high-risk plaque progression and allow monitoring of beneficial changes from medical therapy.
CRIS-Team Scopus Importer:2019-07-09
Keywords: coronary CT angiography; coronary plaque progression; CT attenuation; inflammation; pericoronary adipose tissue

Reply: Leaflet thrombosis following transcatheter aortic valve implantation - Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2018)
EVALuna2:35995

Reproducibility of aortic annulus measurements by computed tomography - Schuhbaeck, Annika; Achenbach, Stephan; Pflederer, Tobias; Schmid, Julia; Nef, Holger; Rixe, Johannes; Hecker, Franziska; Schneider, Christian; Lell, Michael; Uder, Michael; Arnold, Martin; Marwan, Mohamed (European Radiology, 2014)
To evaluate a systematic approach for measurement of aortic annulus dimensions by cardiac computed tomography.CT data sets of 64 patients were evaluated. An oblique cross-section aligned with the aortic root was created by systematically identifying the caudal insertion points of the three aortic cusps and sequentially aligning them in a double oblique plane. Aortic annulus dimensions, distances of coronary ostia and a suitable fluoroscopic projection angle were independently determined by two observers.Interobserver intraclass correlation coefficients (ICC) for aortic annulus diameters were excellent (ICC 0.89-0.93). Agreement for prosthesis size selection was excellent (? = 0.86 for mean, ? = 0.84 for area-derived and ? = 0.91 for circumference-derived diameter). Mean distances of the left/right coronary ostium were 13.4 ± 2.4/14.4 ± 2.8 mm for observer 1 and 13.2 ± 2.7/13.5 ± 3.2 mm for observer 2 (p = 0.30 and p = 0.0001, respectively; ICC 0.76/0.77 for left/right coronary artery). A difference of less than 10° for fluoroscopic projection angle was achieved in 84.3% of patients.A systematic approach to generate a double oblique imaging plane exactly aligned with the aortic annulus demonstrates high interobserver and intraobserver agreements for derived measurements which are not influenced by aortic root calcification.o Systematic approach to generate a double oblique imaging plane for TAVI evaluation. o This method is straightforward and software independent. o An approach with high reproducibility, not influenced by aortic root calcification.
EVALuna2:11952

Reproducibility of semi-automatic coronary plaque quantification in coronary CT angiography with sub-mSv radiation dose - Ovrehus, Kristian Altern; Schuhbaeck, Annika; Achenbach, Stephan; Norgaard, Bjarne Linde; Botker, Hans Erik; Dey, Damini; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2016)
INTRODUCTION: Coronary computed tomographic angiography (CTA) can characterize coronary atherosclerotic plaque components as calcified and non-calcified. Quantitative measurements of coronary plaque burden by coronary CTA may play a role in serial studies to determine disease progression or response to medical therapies. The reproducibility from repeated assessment of such quantitative measurements from low-radiation dose coronary CTA has not been previously assessed. PURPOSE: To evaluate the interscan, interobserver and intraobserver reproducibility for coronary plaque volume assessment using semi-automatic plaque analyses algorithm in low radiation dose coronary CTA. METHODS: In 50 consecutive patients undergoing two 128-slice dual source CT scans within 12 days with a mean radiation dose of 0.7 mSv per coronary CTA, the interscan, interobserver and intraobserver reproducibility of coronary plaque assessment using validated software (AutoPlaq) were evaluated. RESULTS: Interscan, interobserver and intraobserver agreement for non-calcified and calcified plaque volumes were excellent (Spearman rho 0.87-0.99). Interscan mean percentage difference in non-calcified and calcified plaque volumes were 0.1% (p = 0.8) and 1.9% (p = 0.19) with limits of agreement of ±11% and ±48.5%; per inter- and intraobserver mean percentage differences were 0.1% (p = 0.25) and 0.3% (p = 0.001), and 0.3% (p = 0.33) and 0.4% (p = 0.59) with limits of agreement of ±7% and ±32.9%, and ±6.6% and ±32.1%, respectively. CONCLUSION: A semi-automatic plaque assessment algorithm in repeated low radiation dose coronary CTA allows for high reproducibility of coronary plaque characterization and quantification measures.
EVALuna2:33994

Resolution of leaflet thrombosis under anticoagulant therapy in patients after transcatheter aortic valve implantation: influence of prosthesis type and size - Ferstl, Paul; Arnold, Martin; Göller, Markus; Ammon, Fabian; Smolka, S.; Moshage, Maximilian; Uehlein, Sabrina; Achenbach, Stephan; Bittner, Daniel O.; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Risk Assessment of Coronary Obstruction During Transcatheter Aortic Valve Replacement: Insights From Post-BASILICA Computed Tomography - Kitamura, Mitsunobu; Wilde, Johannes; Dumpies, Oliver; Richter, Ines; Obradovic, Danilo; Krieghoff, Christian; Gohmann, Robin F.; Majunke, Nicolas; Desch, Steffen; Gutberlet, Matthias; Borger, Michael; Marwan, Mohamed; et al. (Jacc-Cardiovascular Interventions, 2022)
Objectives: The aim of this study was to examine the predictive value of preprocedural computed tomography (CT)–based risk stratification of coronary obstruction during transcatheter aortic valve replacement (TAVR) on the basis of geometric measurements on postprocedural CT. Background: Proper patient selection for additional procedures to prevent coronary obstruction during TAVR has not been adequately evaluated. Methods: Pre- and postprocedural computed tomographic scans of 28 patients treated using bioprosthetic or native aortic scallop intentional laceration to prevent iatrogenic coronary artery obstruction (BASILICA) and TAVR were analyzed. Using the postprocedural computed tomographic images, threatened coronary obstruction (TCO) was defined as: 1) ostial obstruction (adherence of the transcatheter heart valve [THV] to the coronary ostium with leaflet extension above the ostium); and/or 2) sinus sequestration (THV adherence to the sinotubular junction [STJ] with leaflet extension above the STJ) and was substratified into complete and incomplete types. Results: A total of 51 leaflets were evaluated (88% surgical tissue valves) after excluding leaflets not visible on CT (n = 5). On postprocedural CT, complete TCO was observed in 25.4% (13 of 51 leaflets). On preprocedural CT, leaflets were at high risk for complete TCO (incidence 53%) if the virtual THV–to–coronary distance (VTC) was <3.0 mm, or if the virtual THV–to–STJ distance (VTSTJ) was <1.0 mm with STJ height − leaflet length <0 mm (leaflet-STJ mismatch). Leaflets were at low risk (incidence 0%) if the VTC was ≥3 mm and VTSTJ was ≥3.0 mm or STJ height − leaflet length was ≥+2.0 mm. Of 28 leaflets treated using BASILICA, complete TCO was seen in 35.7% (n = 10), due to sinus sequestration (100%) with coexisting ostial obstruction (30%). Actual coronary events occurred in 7.1% (n = 2) because of leaflet prolapse, corresponding to an absolute risk reduction by BASILICA of 29% (P = 0.021). Conclusions: Risk assessment of coronary obstruction after TAVR may improve with a multiparametric approach incorporating VTC, VTSTJ, and leaflet-STJ mismatch. BASILICA appeared to reduce actual coronary events even in leaflets with anticipated coronary obstruction.
CRIS-Team Scopus Importer:2022-03-11
Keywords: BASILICA; computed tomography; coronary obstruction; transcatheter aortic valve replacement

Role of Cardiac CT Before Transcatheter Aortic Valve Implantation (TAVI) - Achenbach, Stephan; Marwan, Mohamed (Current Cardiology Reports, 2016)
Catheter-based aortic valve implantation is increasingly being performed in high-risk patients with symptomatic aortic valve stenosis. For successful planning of the procedure, CT has been shown to provide crucial information concerning the aortic root as well as the peripheral access vessels. This article illustrates the increasing role of CT before transcatheter aortic valve implantation.
EVALuna2:12078

Role of CT Imaging for Coronary and Non-coronary Interventions - Marwan, Mohamed; Achenbach, Stephan (Current Cardiovascular Imaging Reports, 2017)
Purpose of Review: Pre-procedural imaging is essential for successful planning and performance of several cardiac interventions. Cardiac computed tomography (CT) is a non-invasive imaging modality capable of providing precise information required for different coronary and non-coronary interventions. The role of cardiac CT for the guidance of different cardiac interventions will be described in this review. Recent Findings: Contrast-enhanced computed tomography imaging is increasingly being used for guiding transcatheter cardiac interventions. Anatomical and functional information provided by CT helps in successful planning and performance of several cardiac interventions. Summary: Over the last decade, the continuous growth of interventional cardiology has been associated with widespread acknowledgment that CT is particularly useful for pre-interventional imaging with increasing implementation in clinical routine.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac CT; Chronic total occlusion; Chronic total occlusions; Coronary interventions; Left atrial appendage; Structural heart disease; TAVI

Rotational atherectomy via the transradial access: success rates, procedural parameters and complications - Ferstl, Paul; Drentwett, Anne-Sophie; Bargon, Sophie; Schacher, Nora; Tröbs, Monique; Marwan, Mohamed; Achenbach, Stephan; Gaede, Luise (Heart and Vessels, 2022)
Radial access is recommended for percutaneous coronary intervention (PCI), but rotational atherectomy remains frequently performed via femoral access. Analyzing the procedural parameters, success rate and complications of rotational atherectomy, performed via radial in comparison to femoral access. We retrospectively analyzed 427 consecutive patients undergoing rotational atherectomy. Procedural parameters and outcome were determined in 171 patients, scheduled for radial and compared to 256 patients with femoral access use. In the radial access group (74 ± 9 years, 84% male), the LAD was most frequently treated (49%). Sheath size was 7F in 59% and 6F in 41%, burr size was 1.5 mm in 46% and 1.25 mm in 14% of patients. A temporary pacemaker was inserted in 14%. Procedural success rate stood at 97%. Access site complications occurred in 4% of patients, which was significantly less frequent than in in 256 patients treated via femoral access (13% p = 0.003). Compared to radial access, femoral access was associated with the use of larger sheaths (p < 0.001), more frequent treatment of non-LAD vessels (58.2% vs. 44.4%, p = 0.013) and a higher rate of temporary pacemaker use (27%; p = 0.001). No differences could be seen in procedural success (p = 0.83) and burr size (p = 0.51). Femoral access (OR 3.33; 95% CI 1.40–7.93), and female sex (OR3.40 95% CI 1.69–6.63) were independent predictors for access site complications. For coronary rotational atherectomy, radial access has a high success rate with overall use of smaller sheaths, but of equally sized burrs as well as a significant lower rate of access site-related complications than femoral access.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Percutaneous coronary intervention; Radial access; Rotational atherectomy; Transradial

SCCT guidelines for the performance and acquisition of coronary computed tomographic angiography: A report of the society of Cardiovascular Computed Tomography Guidelines Committee: Endorsed by the North American Society for Cardiovascular Imaging (NASCI) - Abbara, Suhny; Blanke, Philipp; Maroules, Christopher D.; Cheezum, Michael; Choi, Andrew D.; Han, B. Kelly; Naoum, Chris; Norgaard, Bjarne L.; Rubinshtein, Ronen; Schoenhagen, Paul; Villines, Todd; Leipsic, Jonathon; et al. (Journal of Cardiovascular Computed Tomography, 2016)
In response to recent technological advancements in acquisition techniques as well as a growing body of evidence regarding the optimal performance of coronary computed tomography angiography (coronary CTA), the Society of Cardiovascular Computed Tomography Guidelines Committee has produced this update to its previously established 2009 "Guidelines for the Performance of Coronary CTA" (1). The purpose of this document is to provide standards meant to ensure reliable practice methods and quality outcomes based on the best available data in order to improve the diagnostic care of patients. Society of Cardiovascular Computed Tomography Guidelines for the Interpretation is published separately (2). The Society of Cardiovascular Computed Tomography Guidelines Committee ensures compliance with all existing standards for the declaration of conflict of interest by all authors and reviewers for the purpose ofclarity and transparency.
EVALuna2:33668

Side effects and major adverse cardiac events caused by fractional flow reserve measurement: a systematic review and meta-analysis of 12,215 patients - Altstidl, Johannes Michael; Gaede, Luise; Tröbs, Monique; Marwan, Mohamed; Achenbach, Susanne (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Software-based automated CT analysis for planning TAVI-Procedures: Systematic validation against expert and novice human interpretation - Weber, J.; Göller, Markus; Smolka, S.; Bittner, D. O.; Gaede, L.; Tröbs, Monique; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Software innovations in computed tomography for structural heart disease interventions - Hell, Michaela; Gaede, Luise; Achenbach, Stephan; Marwan, Mohamed (EuroIntervention, 2016)
Computed tomography (CT) provides high, isotropic spatial resolution and has become firmly established in pre-procedural imaging for structural heart disease interventions. It allows determination of the exact dimensions of the target structure, provides information regarding the access route and permits identification of fluoroscopic projection angles to provide optimal visualisation for device placement. Several software solutions are available and have been systematically evaluated in the context of transcatheter aortic valve implantation (TAVI). The use of software products to perform automated measurements can be useful, especially when the experience and expertise regarding evaluation of CT in the context of structural heart disease are limited. In scientific studies, software has been demonstrated to provide accurate support for annulus sizing and prosthesis selection, to aid in reliably identifying patients in whom a transfemoral access may be problematic, and to suggest suitable angulations for fluoroscopic imaging to achieve an orthogonal view onto the aortic valve during implantation.
EVALuna2:12098

Standardized measurement of coronary inflammation using cardiovascular computed tomography: integration in clinical care as a prognostic medical device - Oikonomou, Evangelos K.; Antonopoulos, Alexios S.; Schottlander, David; Marwan, Mohamed; Mathers, Chris; Tomlins, Pete; Siddique, Muhammad; Kluner, Laura; Shirodaria, Cheerag; Mavrogiannis, Michail C.; Thomas, Sheena; Fava, Agostina; et al. (Cardiovascular Research, 2021)
Aims Coronary computed tomography angiography (CCTA) is a first-line modality in the investigation of suspected coronary artery disease (CAD). Mapping of perivascular fat attenuation index (FAI) on routine CCTA enables the non-invasive detection of coronary artery inflammation by quantifying spatial changes in perivascular fat composition. We now report the performance of a new medical device, CaRi-Heart (R), which integrates standardized FAI mapping together with clinical risk factors and plaque metrics to provide individualized cardiovascular risk prediction.
CRIS-Team WoS Importer:2021-12-17

Tako-Tsubo Cardiomyopathy: clinical correlations of typical and atypical left ventricular contraction patterns - Gaede, L.; Herchenbach, A.; Tröbs, Monique; Achenbach, Stephan; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

The association of pericoronary adipose tissue attenuation with major adverse cardiac events (MACE) and atherosclerosis-relevant inflammatory mediators - Göller, Markus; Achenbach, Stephan; Herrmann, N.; Bittner, Daniel O.; Ammon, Fabian; Kilian, Tobias; Smolka, S.; Uehlein, Sabrina; Moshage, Maximilian; Raaz-Schrauder, Dorette; Dey, D.; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

The ISCHEMIA trial: Implications for non-invasive imaging - Rakisheva, Amina; Achenbach, Stephan; Marwan, Mohamed (Anatolian Journal of Cardiology, 2020)
Coronary artery disease (CAD) is highly prevalent and constitutes the single most common cause of death worldwide. However, the diagnosis of CAD remains challenging. There are two ways to approach the diagnosis of CAD, namely (1) by a functional non-invasive stress test to detect ischemia (stress echocardiography, stress cardiovascular magnetic resonance, single-photon emission computed tomography, positron emission tomography) or (2) by imaging for stenosis visualization (coronary computed tomography angiography or invasive coronary angiography). There are also two approaches for treatment: medical treatment and revascularization. The International Study of Comparative Health Effectiveness with Medical and Invasive Approaches (ISCHEMIA) trial investigated the outcome differences of patients who had moderate to severe ischemia on stress testing and who, after CT angiography, had ruled out left main stenosis and demonstrated at least 1 coronary artery stenosis exceeding 50%. The patients were randomized to an initially conservative treatment versus immediate revascularization. No difference in hard outcomes was found, but angina relief was more effective in the revascularization group. In this article, we explore the implications of the ISCHEMIA trial for non-invasive testing in suspected CAD.
CRIS-Team WoS Importer:2020-07-24

The Journal of Cardiovascular Computed Tomography: 2020 Year in review - Villines, Todd C.; Al'Aref, Subhi J.; Andreini, Daniele; Chen, Marcus Y.; Choi, Andrew D.; De Cecco, Carlo N.; Dey, Damini; Earls, James P.; Ferencik, Maros; Gransar, Heidi; Hecht, Harvey; Leipsic, Jonathon A.; et al. (Journal of Cardiovascular Computed Tomography, 2021)
The purpose of this review is to highlight the most impactful, educational, and frequently downloaded articles published in the Journal of Cardiovascular Computed Tomography (JCCT) for the year 2020. The JCCT reached new records in 2020 for the number of research submissions, published manuscripts, article downloads and social media impressions. The articles in this review were selected by the Editorial Board of the JCCT and are comprised predominately of original research publications in the following categories: Coronavirus disease 2019 (COVID-19), coronary artery disease, coronary physiology, structural heart disease, and technical advances. The Editorial Board would like to thank each of the authors, peer-reviewers and the readers of JCCT for making 2020 one of the most successful years in its history, despite the challenging circumstances of the global COVID-19 pandemic.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Cardiac computed tomography; Cardiac CT; Coronary artery calcium; Coronary CT angiography; COVID-19; Journal of cardiovascular computed tomography; Structural heart disease

The journal of cardiovascular computed tomography: A year in review: 2022 - Pontone, Gianluca; Mushtaq, Saima; Al'Aref, Subhi J.; Andreini, Daniele; Baggiano, Andrea; Canan, Arzu; Cavalcante, Joao L.; Chelliah, Anjali; Chen, Marcus; Choi, Andrew; Damini, Dey; De Cecco, Carlo Nicola; et al. (Journal of Cardiovascular Computed Tomography, 2023)
This review aims to summarize key articles published in the Journal of Cardiovascular Computed Tomography (JCCT) in 2022, focusing on those that had the most scientific and educational impact. The JCCT continues to expand; the number of submissions, published manuscripts, cited articles, article downloads, social media presence, and impact factor continues to grow. The articles selected by the Editorial Board of the JCCT in this review highlight the role of cardiovascular computed tomography (CCT) to detect subclinical atherosclerosis, assess the functional relevance of stenoses, and plan invasive coronary and valve procedures. A section is dedicated to CCT in infants and other patients with congenital heart disease, in women, and to the importance of training in CT. In addition, we highlight key consensus documents and guidelines published in JCCT last year. The Journal values the tremendous work by authors, reviewers, and editors to accomplish these contributions.
CRIS-Team Scopus Importer:2023-05-05
Keywords: CTA=coronary CT angiography; HRP=high risk plaques; TAVR=Transcatheter aortic valve replacement

The relation of aortic dimensions and obesity in adults with Marfan or Loeys-Dietz syndrome - Suleiman, Mathieu; Freilinger, Sebastian; Meierhofer, Christian; May, Matthias; Bischoff, Gert; Ewert, Peter; Freiberger, Annika; Huntgeburth, Michael; Kaemmerer, Ann-Sophie; Marwan, Mohamed; Nagdyman, Nicole; Roth, Jan-Peter; et al. (Cardiovascular Diagnosis and Therapy, 2022)
Background: Aortic aneurysm and aortic dissection can have a major impact on the life expectancy of Marfan syndrome (MFS) or Loeys-Dietz syndrome (LDS) patients. Although obesity can influence the development of aortic complications, evidence on whether obesity influences the development of aortic aneurysm or dissection in MFS and LDS is limited. The aim of the present study was to elucidate the relationship between aortic size and body composition, assessed by modern bioelectrical impedance analysis (BIA) in MFS/LDS-patients.Methods: In this exploratory cross-sectional study in MFS or LDS patients, enrolled between June 2020 and May 2022, 34 patients received modern BIA and magnetic resonance imaging (MRI) (n=32) or computed tomography (CT) imaging (n=2) of the entire aorta. A P value of <0.05 was considered significant.Results: Fifty-one patients (66% female; mean age: 37.7 +/- 11.7; range, 17-68 years) with MFS or LDS were enrolled; 34 patients, 27 with MFS and 7 with LDS, underwent aortic MRI or CT scanning. The mean aortic length was 503.7 +/- 58.7 mm, and the mean thoracic aortic length and abdominal aortic length were 351.5 +/- 52.4 and 152.2 +/- 27.4 mm, respectively. The aortic bulb and the ascending aorta were measured only in the non-surgically repaired patients. Fifteen MFS (88.2%) and two LDS (40.0%) patients had an aortic aneurysm. In these, the aortic bulb tended to be larger in MFS than in LDS patients [42.6x41.9x41.2 vs. 37.8x37.4x36.8 mm; P=0.07 (-1.1; 9.1); P=0.07 (-1.2; 8.4); P=0.07 (-1.5; 7.9)]. BIA revealed mean body fat levels of 31.6%+/- 8.7% (range, 9.5-53.5%), indicating that 18 patients (52.9%) were obese. There was a significant correlation between body fat content and thoracic aortic length (R=-0.377; P=0.02), muscle mass and total aortic length (R=0.359; P=0.03), thoracic aortic length (R=0.399; P=0.02), extracellular mass (ECM), and total aortic length (R=0.354; P=0.04) , connective tissue and aortic diameters at the aortic arch (R=0.511; P=0.002), aortic isthmus (R=0.565; P<0.001), and abdominal aorta (R=0.486; P=0.004). Older age was correlated with wider aortic arch, isthmus, and abdominal aorta. Male patients had a longer aorta.Conclusions: While a slender habitus is commonly known for MFS and LDS patients, our data show that many MFS and LDS patients (especially female) do not fit this phenotypic characteristic and are obese, which is associated with a more severe aortic phenotype. This topic should be included in the clinical assessment of affected MFS and LDS patients, in addition to measurement of the aortic diameters. Physicians should systematically screen MFS and LDS patients for obesity, educate them about the potential risk of resulting aortic complications, and encourage them to adopt a healthy lifestyle, that includes (mild) exercise and a balanced diet.
CRIS-Team WoS Importer:2023-02-03
Keywords: Adults with connective tissue disease; Marfan syndrome (MFS); Loeys-Dietz syndrome (LDS); body composition; obesity

Transcatheter Aortic Valve Replacement for Isolated Aortic Regurgitation Using a New Self-Expanding TAVR System - Adam, Matti; Tamm, Alexander; Wienemann, Hendrik; Unbehaun, Axel; Klein, Christoph; Arnold, Martin; Marwan, Mohamed; Theiss, Hans; Braun, Daniel; Bleiziffer, Sabine; Geyer, Martin; Goncharov, Arseniy; et al. (Jacc-Cardiovascular Interventions, 2023)
Background: Patients with severe aortic regurgitation (AR) are often not considered for surgery because of increased surgical risk. Because of unique anatomical characteristics among patients with AR, interventional treatment options are limited, and implantation results are inconsistent compared with those among patients with aortic stenosis. Objectives: The authors describe the initial commercial experience of the first Conformité Européenne–marked transfemoral transcatheter aortic valve replacement system (JenaValve Trilogy [JV]) for the treatment of patients with AR. Methods: This multicenter registry included 58 consecutive patients from 6 centers across Germany. Transcatheter aortic valve replacement was performed with the JV system for isolated severe and symptomatic AR. Patient characteristics, primary implantation outcomes, and valve performance up to 30 days were analyzed using Valve Academic Research Consortium 3 definitions. Results: The mean patient age was 76.5 ± 9 years, with a mean Society of Thoracic Surgeons score of 4.2% ± 4.3%. Device success was achieved in 98% of patients. The mean gradient was 4.3 ± 1.6 mm Hg, and no moderate or severe paravalvular regurgitation occurred. No conversion to open heart surgery or valve embolization was reported. There were no major vascular complications or bleeding events. The rate of new permanent pacemaker implantation was 19.6%. At 30 days, 92% of the patients were in NYHA functional class I or II, and the 30-day mortality rate was 1.7%. Conclusions: Treatment of patients with severe symptomatic AR using the transfemoral JV system is safe and effective. Given its favorable hemodynamic performance and low complication rates, this system may offer a new treatment option for patients with AR not suitable for surgery.
CRIS-Team Scopus Importer:2023-09-01
Keywords: aortic regurgitation; JenaValve; paravalvular regurgitation; TAVR

Ultra-low dose comprehensive cardiac CT imaging in a patient with acute myocarditis - Tröbs, Monique; Brand, Michael; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2014)
The ability of contrast-enhanced CT to detect "late enhancement" in a fashion similar to magnetic resonance imaging has been previously reported. We report a case of acute myocarditis with coronary CT angiography as well as "late enhancement" imaging with ultra-low effective radiation dose.
EVALuna2:11957

Use of coronary physiology to guide revascularization in clinical practice: results of the F(FR)2 registry - Altstidl, Johannes Michael; Achenbach, Stephan; Feyrer, Johannes; Nazli, J. Benedikt; Marwan, Mohamed; Gaede, Luise; Möllmann, Helge; Giesler, Tom; Rittger, Harald; Pauschinger, Matthias; Rudolph, Tanja K.; Moshage, Werner; et al. (Clinical Research in Cardiology, 2024)
Background: Despite the recommendation of coronary physiology to guide revascularization in angiographically intermediate stenoses without established correlation to ischemia, its uptake in clinical practice is slow. Aims: This study aimed to analyze the use of coronary physiology in clinical practice. Methods: Based on a multicenter registry (Fractional Flow Reserve Fax Registry, F(FR)2, ClinicalTrials.gov identifier NCT03055910), clinical use, consequences, and complications of coronary physiology were systematically analyzed. Results: F(FR)2 enrolled 2,000 patients with 3,378 intracoronary pressure measurements. Most measurements (96.8%) were performed in angiographically intermediate stenoses. Out of 3,238 lesions in which coronary physiology was used to guide revascularization, revascularization was deferred in 2,643 (78.2%) cases. Fractional flow reserve (FFR) was the most common pressure index used (87.6%), with hyperemia induced by an intracoronary bolus of adenosine in 2,556 lesions (86.4%) and intravenous adenosine used for 384 measurements (13.0%). The route of adenosine administration did not influence FFR results (change-in-estimate -3.1% for regression model predicting FFR from diameter stenosis). Agreement with the subsequent revascularization decision was 93.4% for intravenous and 95.0% for intracoronary adenosine (p = 0.261). Coronary artery occlusion caused by the pressure wire was reported in two cases (0.1%) and dissection in three cases (0.2%), which was fatal once (0.1%). Conclusions: In clinical practice, intracoronary pressure measurements are mostly used to guide revascularization decisions in angiographically intermediate stenoses. Intracoronary and intravenous administration of adenosine seem equally suited. While the rate of serious complications of wire-based intracoronary pressure measurements in clinical practice seems to be low, it is not negligible. Graphical abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-06-14
Keywords: Complications; Coronary artery disease; Coronary physiology; Fractional flow reserve (FFR); Registry

Very low-dose coronary artery calcium scanning with high-pitch spiral acquisition mode: Comparison between 120-kV and 100-kV tube voltage protocols - Marwan, Mohamed; Mettin, Carina; Pflederer, Tobias; Seltmann, Martin; Schuhbaeck, Annika; Muschiol, Gerd; Ropers, Dieter; Daniel, Werner; Achenbach, Stephan (Journal of Cardiovascular Computed Tomography, 2013)
Background: Effective radiation dose from a single coronary artery calcification CT scan can range from 0.8 to 10.5 mSv, depending on the protocol. Reducing the effective radiation dose to reasonable levels without affecting diagnostic image quality can result in substantial dose reduction in CT. Objectives: We prospectively compared tube voltages of 120 and 100 kV in a low-dose CT acquisition protocol for measuring coronary artery calcified plaque with prospectively electrocardiogram (ECG)-triggered high-pitch spiral acquisition. Methods: In 150 consecutive patients, measurement of coronary artery calcified plaque was performed with prospectively ECG-triggered high-pitch spiral acquisition. Imaging was first done with tube voltage of 120 kV voltage and subsequently repeated with 100 kV and otherwise unchanged parameters. CT was performed with a dual-source CT system with 280 milliseconds of rotation time, 2 × 128 slices, pitch of 3.4, triggered at 60% of the R-R interval. Tube current for both protocols was set at 80 mAs. With the use of a medium sharp reconstruction kernel (Siemens B35f), cross-sectional images were reconstructed with 3.0-mm slice thickness and 1.5-mm increment. Agatston scores were determined per patient for both scan settings by 2 independent readers with the use of a standard threshold of 130 HU for calcium detection. In addition, the Agatston score was calculated with a previously proposed threshold of 147 HU for 100-kV acquisitions. Results: Mean image noise was 20 ± 5 and 27 ± 7 for 120 and 100 kV, respectively (P < 0.0001). Mean dose length product was 24 ± 6 cm · cGy for the 120-kV protocol and 14 ± 4 cm · cGy for the 100-kV protocol, corresponding to average estimated effective doses of 0.3 and 0.2 mSv (P < 0.0001). Five patients were excluded from the analysis. In the remaining 145 patients, using the standard tube voltage of 120 kV, any coronary calcium was detected in 76 identical patients by both observers. In 75 of these patients, calcium was also identified by both observers in 100-kV data sets, whereas 1 patient was scored negative by 1 reader and was assigned an Agatston score of 0.7 (threshold, 130 HU) and 0.2 (threshold, 147 HU) by the other. Interobserver disagreement for assigning a patient a zero Agatston score was the same for both scan settings (each 4 patients). The mean Agatston scores for 120-kV and 100-kV (threshold, 147 HU) scans were 105 ± 245 (range, 0-1865) and 116 ± 261 (range, 0-1917), respectively (P < 0.0001). Bland-Altman analysis indicated a systematic overestimation of the Agatston score with tube voltage of 100 kV and threshold of 147 HU (mean difference, 11; 95% limits of agreement, 62 to -40). Similar results were observed for coronary calcium volume scores. Conclusion: High-pitch spiral acquisition allows coronary calcium scoring with effective doses below 0.5 mSv. The use of 100-kV tube voltage further reduces effective radiation dose compared with the standard of 120 kV; however, it leads to significant overestimation of the Agatston score when the standard threshold of 130 HU is used. Adjusting the threshold to 147 HU leads to a better agreement compared with standard 120 kV protocols yet with a remaining systematic bias toward overestimation of the Agatston score. For high-pitch spiral acquisition mode, effective radiation dose reduction when using a 100-kV setting is minimal compared with the standard 120-kV setting and may be considered nonsignificant in a clinical setting. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Calcium score; CT; Low-dose protocols

White Matter Lesions, Carotid and Coronary Atherosclerosis in Late-Onset Depression and Healthy Controls - Devantier, Torben Albert; Norgaard, Bjarne Linde; Poulsen, Mikael Kjaer; Garde, Ellen; Ovrehus, Kristian Altern; Achenbach, Stephan; Dey, Damini; Sorensen, Leif Hougaard; Videbech, Poul; Marwan, Mohamed (Psychosomatics, 2016)
BACKGROUND: Cerebral white matter lesions (WMLs) are more common in individuals with late-onset or late-life depression. It has been proposed that carotid atherosclerosis may predispose to WMLs by inducing cerebral hypoperfusion. This hemodynamic effect of carotid atherosclerosis could be important for the formation of WMLs in depression. METHODS: The case-control study included 29 patients with late-onset major depressive disorder and 27 controls matched for sex, age, and tobacco use. WML volume, carotid intima-media thickness, and coronary plaque volume were assessed using magnetic resonance imaging, ultrasound scan, and coronary computed tomography (CT) angiography, respectively. RESULTS: The mean age for the total sample was 59.7 ± 4.7 years. There was no difference in carotid intima-media thickness between patients and controls (p = 0.164), whereas a higher WML volume in the patients was found (p = 0.051). In both patients and controls, WML volume was associated with carotid but not with coronary atherosclerosis. In adjusted multiple linear regression, a 0.1mm increase in averaged carotid intima-media thickness was associated with a 52% (95% CI: 8.4-112, p = 0.032) increase in WML volume. The association between carotid intima-media thickness and WML volume was, however, similar in patients and controls. CONCLUSIONS: In older persons aged between 50 and 70 years, WMLs do not seem to be a part of generalized atherosclerotic disease, but seem to be dependent on atherosclerosis in the carotid arteries. Carotid atherosclerosis, however, could not explain the higher WML load observed in the depressed patients, and thus, studies are needed to establish the mechanisms linking depression and WMLs.
EVALuna2:12104